High-salinity composite organic wastewater electrochemical treatment: A Janus system coupling high-valent iron oxidation with atomic hydrogen-mediated reductive detoxification - Jiayi He; Ge Song; Guanyu Liu; Chaohui Zhang; Jiangli Sun; Jiatong Zhang; Minghua Zhou (Water Research, 2026)

Simultaneous study on flame propagation behavior and pollutant formation characteristics of ammonia premixed combustion ignited by a methanol ignition chamber - Chunyang Xie; Mingfei Lu; Yangyang Zhang; Zhenyu Sun; Pengbo Dong; Wuqiang Long; Peng Wang; Yang Wang; Ge Xiao; Hua Tian (Fuel, 2026)

Human YTHDC2 mutations disturb RNA homeostasis of oocytes and early embryos - Wei Su; Yang Wang; Jiaqi Sun; Changlong Zhang; Changjian Yin; Ying Cui; Xiaolei Chen; Bohan Yang; Shigang Zhao; Keliang Wu; Ge Lin; Zi-Jiang Chen; et al. (Human Genetics, 2026)

A pH-responsive, kojic acid-based amphiphilic polymer as a nanocarrier for targeted herbicide delivery - Yuying Xie; Yangchun Ge; Zhuochao Shen; Yupeng Qiu; Haohua Zhang; Changmeng Sun; Jiangkuan Tang; Bingke Li; Junran Xu; Ping Liang; Yubang Tao; Shengtian Wang; et al. (Crop Protection, 2026)

Apatite geochemistry of granites from the Xiaolonghe Tin deposit, Western Yunnan: Implications for petrogenesis and mineralization - Kun Ge; Xiang Sun; Yong Fu; Yaqi Ye; Yingjie Wang; Xianyi Huang; Xiaobo Si; Mingjun Zheng (Journal of Geochemical Exploration, 2026)

Exploring the impact of urban emissions on elevated HONO in suburban mountain areas - Mingzhu Zhai; Shengrui Tong; Hailiang Zhang; Wenqian Zhang; Xu Sun; Heshan Ning; Chunyan Zhang; Jun Liu; Maofa Ge (Journal of Environmental Sciences, 2026)

Elevated contaminations and risks of novel organophosphate esters and their transformation products in paddy soils - Zixiao Zhao; Meng Gao; Mohan Ma; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; Hongwen Sun (Journal of Environmental Sciences, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Sea cucumber viscera-derived antifreeze peptides: identification, ice recrystallization inhibition activity, and ice-binding mechanism - Richeng Yu; Yang Zhao; Linnan Wang; Peng Ge; Zhupeng Zhang; Yuejuan Jia; Qianyun Ma; Wenxiu Wang; Jianfeng Sun (Food Research International, 2026)

Research on the wind-induced internal and net pressure with openings on the cylindrical roof based on the covariance integration method - Ying Sun; Yuhang Ge; Qiming Zhu; Zhenggang Cao (Engineering Structures, 2026)

A novel mycotoxin-degrading enzyme complex alleviates the combined toxicity of AFB1, DON, and ZEN in laying hens - Yan-Qi Ning; Yu Zhang; Yu-Hao Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun; Yu-Xuan Huang (Toxicon, 2026)

Phosphatidic acid mediates the crosstalk between ethylene and lipid metabolism to confer chilling tolerance - Ke Wang; Bei Zhou; Ge Zhu; Yue Sun; Xue-ren Yin; Qing-feng Niu (Postharvest Biology and Technology, 2026)

Thermal damage evolution and thermal Kaiser effect of red sandstone under monotonic and cyclic heating: Insights from acoustic emission monitoring - Shihao Yuan; Qiang Sun; Zhenlong Ge; Jishi Geng (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Interfacial polymerization for sustainable microencapsulation: Bio-based core/shell design, mechanistic principles, and emerging applications - Limin Gu; Xueqing Qin; Ziyan Ren; Yan Su; Shuai Li; Linya Zhang; Yanrui Ge; Fengxia Sun (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Interpretable and robust machine-learning prediction of CO2-H2O-coal wettability for deep CO2-enhanced coalbed methane and geological storage - Yunzhong Jia; Chenying Yu; Zhaolong Ge; Jiren Tang; Xiao Sun; Wenyu Fu (Gas Science and Engineering, 2026)

Analysis and design for ensuring release safety of Multi-Hydrogen cylinder bundles under real fire experiment - Jie Liu; Jianwei Li; Zhanxin Mao; Huanhuan Bao; Xiaocheng Ge; Xinming Wan; Hongwen He; Fengchun Sun (Fuel, 2026)

Endogenously modified multi-bioresponsive silk fibroin nanoparticles enhancing the cellular delivery and anti-inflammatory activity of curcumin - Sheliang Zhao; Yuwei Sun; Yuxuan Du; Mengjie Yang; Chenxu Gao; Yunshu Ge; Dongning Li; Yang Yang; Xuebo Liu (Food Research International, 2026)

Climate and soil properties drive microplastic enrichment patterns in agricultural soils across a multi-country survey - Martine Graf; Michaela K. Reay; Yingming Sun; Fan Ding; Siyang Ren; Kai Wang; Changrong Yan; Shitong Li; Tida Ge; Xuejun Liu; Ruimin Qi; Jixiao Cui; et al. (Environmental Pollution, 2026)

Quantification of ecological benefits of inter-basin water diversion projects based on ecosystem service value - Zongkun Li; Baoxing Sun; Yadong Zhang; Wei Ge; Fengxiang Zhang; Weibing Du (Ecosystem Services, 2026)

Construction of porous liquids based on carbon coated hierarchically porous TS-1 particles and deep eutectic solvents for SO2 selective separation - Shuaiyong Dou; Mengru Sun; Yameng Zhao; Yuheng Zhen; Xiaofei Du; Ao Zhang; Cunchao Yang; Guoquan Liu; Shixuan Wu; Meixuan Ge; Aibin Kang; Erhong Duan; et al. (Chemical Engineering Journal, 2026)

Targeting extracellular DNA for broad-spectrum biofilm eradication and efficient microbiologically influenced corrosion mitigation - Mingyue Sun; Anqing Li; Haonan Ge; Qinfang Wang; Jinlong Zhao; Zhong Li; Fuhui Wang; Dake Xu (Chemical Engineering Journal, 2026)

Breaking spatiotemporal mismatch via a dynamic buffering “ion-sponge” electrolyte additive for stable Zn anodes - Dan Li; Zhiye Yao; Guosheng Duan; Leilei Sun; Sinan Zheng; Zhean Bao; Hanwei Hu; Dinghao Chen; Xinyuan Kong; Ge Wang; Yang Wang; Zhizhen Ye; et al. (Chemical Engineering Journal, 2026)

pH-responsive microcapsules co-delivering radioprotectant and probiotics for synergistic mitigation of radiation-induced enteritis - Caifang Gao; Jiaxuan Ma; Luke Ge; Yongle Zhao; Ru Feng; Pengqi Zhu; Jinghua Sun; Ruiping Zhang (Chemical Engineering Journal, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Biochar enhances soil carbon in iron-rich red soil but fails in calcareous fluvo-aquic soil: Mineral protection outweighs microbial turnover - Wanyi Fang; Peipei Li; Ge Song; Na Deng; Siyi Liu; Tianran Sun; Limei Zhang (Agriculture, Ecosystems & Environment, 2026)

Pore fluid pH–salinity homogenization for sustained electroosmosis: Performance, energy efficiency and underlying mechanisms - Xiaojuan Yang; Ge Shi; Yuanqiang Cai; Ángel Yustres; Rubén López-Vizcaíno; Honglei Sun (Journal of Environmental Management, 2026)

‘From growth monitoring to berry quality prediction: Advances and challenges in UAV remote sensing for precision viticulture - Jinyu Yang; Mengyuan Wei; Qifan Chen; Tingting Ma; Qian Ge; Yue Yan; Jiming Li; Baofeng Su; Yulin Fang; Xiangyu Sun (Computers and Electronics in Agriculture, 2026)

Expression and functional role of NAD(P)H:quinone oxidoreductase 1 (NQO1) in glycidyl methacrylate-induced malignant transformation of lung epithelial cells - Xintong Liu; Hongjiao Wu; Yishuang Cui; Yexuan Liu; Ziqing Liu; Jiawen Sun; Yanlei Ge; Ye Jin; Junqing Gan; Weinan Yao; Yanna Bi; Guogui Sun (Toxicology and Applied Pharmacology, 2026)

Genome-wide identification and expression analysis of the homeodomain-leucine zipper gene family in quinoa during the grain filling stage - Wenxuan Ge; Xueying Li; Xiuzhang Wang; Jiayu Liu; Yanxia Sun; Xiaoyong Wu (South African Journal of Botany, 2026)

Purification characteristics and mechanisms of multiphase pollutants by an array needle–plate negative corona discharge plasma - Chuanshan Yue; Shaocheng Ge; Shuo Liu; Xingyu Pang; Weizhi Zhao; He Liu; Liying Sun (Process Safety and Environmental Protection, 2026)

1-Methylcyclopropene regulates ethylene and polyamine metabolism of fig fruit during cold storage - Jingyi Lv; Xin Sun; Sijie Dong; Siqi Yan; Yonghong Ge; Jianrong Li (Postharvest Biology and Technology, 2026)

Ice breaking and water entry by a rigid sphere - Liang Sun; Zhangguo Ge; Yiheng Zhang; Ying Tang; Yiquan Yu; Zheyu Liu; Daoxin Zhou (Ocean Engineering, 2026)

Integrating emergy accounting with ecosystem-based coastal defence: An eco-coastal engineering framework for sustainability assessment of hybrid infrastructure - Junxue Zhang; Moran Yu; Hairuo Wang; Yan Gong; Haobing Wang; Xiaoting Zhai; Ashish T. Asutosh; Yingnan Li; Ge Song; Weidong Wu; Ziyi Men; Minghui Yang; et al. (Ocean Engineering, 2026)

Functional differentiation of active hydrogen on Pd/Cu catalysts for efficient electrocatalytic nitrate reduction to ammonia - Chunhong Fu; Chaohui Zhang; Jiangli Sun; Huizhong Wu; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2026)

Neurotoxic effects of spirotetramat in zebrafish (Danio rerio): Brain injury, locomotor abnormalities, and altered visual-related pathways - Xunyue Liu; Peng Liu; Haojie Zhu; Junyao Ge; Qiong Rao; Jianqiang Sun (Journal of Hazardous Materials, 2026)

6PPD and 6PPD-Q driven phytotoxicity in Eichhornia crassipes: From molecular damages to ecological potential implications - Yichen Ge; Weitao Liu; Xiang Li; Jinzheng Liu; Ruiying Shi; Xinwei Shi; Aurang Zeb; Qi Wang; Jianling Wang; Cuihong Chen; Yuebing Sun (Journal of Environmental Sciences, 2026)

Effects of fruit bagging on pesticide fate and fruit quality in peach under mixed-pesticide applications - Jun Yu; Pei Wang; Xiaolong Chen; Xing Sun; Jing Ge; Xiangyang Yu (Food Research International, 2026)

Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Tandem mass tag-based quantitative proteomics reveals the relationship between protein changes and off-flavor in chilled fresh pork treated with electron beam irradiation - Lei Sun; Fengqin Ge; Leting Sun; Qizhen Guo; Feng Li; Dongxiao Sun-Waterhouse; Yongli Wang (Food Research International, 2026)

A multifunctional hybrid delivery system of sodium alginate-based nanoparticles-hydrogel beads “double fence” effect for pea peptide - Guocong Ma; Mingwu Qiao; Dan Hai; Yan Ma; Ge Bai; Peijun Zhao; Xianqing Huang; Xinyu Sun; Lianjun Song (Food Chemistry, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Unveiling the molecular interplay: phosvitin as a stabilizer of lactoferrin against thermal denaturation - Ling Zhang; Wenduo Han; Han Sun; Wenqi Ge; Jiawen Pei; Jiajing Liu; Shubo Luo; Xiang Duan; Xuebo Liu (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

A multi-responsive and self-healing konjac glucomannan hydrogel crosslinked by dual dynamic bonds for smart banana preservation - Yangchun Ge; Zhuochao Shen; Yuying Xie; Yupeng Qiu; Haohua Zhang; Changmeng Sun; Jiangkuan Tang; Bingke Li; Junran Xu; Xuqiang Peng; Lanlan Zhai; Zhongyu Li (Food Chemistry, 2026)

Cascaded catalytic amplification by a phenylboronate ester-based double-network hydrogel for synergistic eradication of multidrug-resistant bacteria and diabetic wound healing - Weiwei Zhang; Jiawen Shao; Xuanjun Zhang; Wanzhen Li; Longbao Zhu; Dongdong Sun; Lisandra L. Martin; Zuchun Zhao; Fei Ge (Chemical Engineering Journal, 2026)

pH-switchable polyoxometalate-loaded hydrogel with intrinsic oxygen-independent singlet oxygen generation and in situ nitric oxide production for infected wound management - Cantong Sun; Zhen Zhang; Zhen Li; Muhammad Adnan Younis; Hongyu Chen; Shujun Zhang; Junle Wu; Dehao Du; Haiyan Ge; Lehao Liu; Ruiheng Li; Shengyi Dongye; et al. (Chemical Engineering Journal, 2026)

Effects of starch degradation and starch-lipid complexes recombination on starch digestion under cold plasma regulation - Yuan Jiang; Xingrong Pan; Yuanfang Sun; Jingru He; Sihan Cheng; Zonnglin Guo; Kun Hu; Xiangzhen Ge (Carbohydrate Polymers, 2026)

Fine-scale mapping of built-environment carbon emissions: A multi-source data fusion and explainable machine learning framework for high-density urban regions - Ge Shi; Haoran Tang; Wei Wang; Chuang Chen; Jiantao Shi; Bo Wang; Lin Sun (Building and Environment, 2026)

Microbial biofilms succession of aquaculture fouled net under the UV-C antifouling technology - Ming-Shan Sun; Shan Ge; Liu-Yi Huang; Chun-Wei Bi; Xiao Liu (Aquacultural Engineering, 2026)

A Sea Surface Salinity error correction model integrating physical models and complex environmental influences - Yanling Han; Wenbin Zhao; Qinqin Sun; Ge Song; Ping Ma; Yun Zhang; Chuanxiang Hua; Shouqi Cao (International Journal of Remote Sensing, 2026)

Governing role of pore structure in solute transport processes in plain river network areas: Insights from CT imaging - Sun Xiaoqin; She Dongli; Pan Yongchun; Wang Hongde; Cao Taohong; Ge Jiamin; Ju Xinni (Soil and Tillage Research, 2026)

Retraction notice to “High-efficiency and low-carbon inactivation of UV resistant bacteria in reclaimed water by flow-through electrode system (FES)” [Sci. Total Environ. 904 (2023) 166297] - Yi-Ge Sun; Hao-Bin Wang; Yin-Hu Wu; Ke-Fan Cao; Zhuo Chen; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Science of The Total Environment, 2026)

Loss of eIF3m aggravates myocardial ischemia/reperfusion injury via enhancing nitrative damage and inhibiting glycolytic reprogramming - Zilun Wei; Yongchao Zhao; Daile Jia; Rifeng Gao; Weidong Xiong; Xiaolei Sun; Xinyu Weng; Bowen Liu; Shuai Song; Wei Luo; Jian Cui; Kai Hu; et al. (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Environmental eustress inhibits CCL2 to overcome doxorubicin-induced cardiotoxicity and alleviate tumor growth - Peiyuan Bai; Chaobao Liu; Ao Liu; Zehao Zhuang; Jinghong Zhang; Lu Tang; Naifu Wan; Runda Wu; Wuwei Rong; Siqin Chen; Jinglei Wan; Yang Yang; et al. (Science Bulletin, 2026)

Toward rational selection of surfactants for coal dust control: A molecular framework for hydrophilic group–coal compatibility - Weizhi Zhao; Shaocheng Ge; He Liu; Liying Sun; Tianyi Yang; Chuanshan Yue; Shuo Liu (Process Safety and Environmental Protection, 2026)

Climatic variability characteristics of the western coast of the Bohai Bay during the early-middle Holocene - Ran Zhang; Hanfei You; Ying Wang; Xiuyun Sun; Bing Li; Yawen Ge; Zhen Zhang; Hongyu Song; Yuecong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Leachate treatment reduces but does not eliminate antibiotic resistance gene contamination: Associations between Pseudomonadota and resistome persistence in treated leachate - Yue Sun; Xian-Ge Wang; Xiao-Jun Chen; Zhen Zhou; Yue-Jun Huang; De-Shuo Wang; Bei-Dou Xi; Xiao-Song He (Journal of Hazardous Materials, 2026)

Hydrogeochemical and isotopic insights into source and human health risk of nitrate in groundwater from China's largest freshwater lake basin - Chunyi Wei; Shengpin Yu; Ximin Bai; Haiyan Liu; Zhen Wang; Olivier Pourret; Qin Ge; Hui Gui; Zhongkui Zhou; Zhanxue Sun (Groundwater for Sustainable Development, 2026)

Association study on the regulation of muscle development-related genes, proteins, and metabolites in different tissues by gastrointestinal flora during various developmental stages of Liaoning cashmere goats - Yinggang Sun; Xingtang Dou; Qingyu Yuan; Ran Duan; Qiying Zhan; Taiyu Hui; Yanjun Qiao; Jiaqi Li; Wangshu Li; Yunlong Guo; Dakun Lyu; Jiaqi Ge; et al. (Food Chemistry, 2026)

Mineralogical fingerprints reveal the source-to-sink dynamics of the Yellow River and local sources in Laizhou Bay, Bohai Sea - Menglin Zhuo; Xiaoyuan Gu; Jianwei Sun; Qingtong Wang; Hengjian Li; Haigen Wang; Yuhai Chen; Chunhui Ma; Xiangwei Ge; Fengbin Zhu; Yadong Xu; Shixiong Yang (Estuarine, Coastal and Shelf Science, 2026)

Visible-light-driven photoelectrochemical platform based on pyrochlore Bi2Sn2O7-sensitized Sb1.75Bi0.25S3 solid solution for highly sensitive shikonin detection - Xiaoqian Sun; Shenyu Zhu; Linzi Huang; Caiyu Ge; Kunxiang Deng; Yilin Wang; Yixi Xie; Pengcheng Zhao; Junjie Fei (Chemical Engineering Journal, 2026)

Neuroprotective Effects of PNU-282,987, an α7-Nicotinic Receptor Agonist, on Sevoflurane-Induced Pyroptosis and Cognitive Impairment in Rats - Jun Xu; Xufang Sun; Dedong Xu; Yuan Ge; Lei Ming (Journal of Pharmaceutical Innovation, 2026)

Primer-programmed circular template generation enables padlock-free rolling circle amplification for low-background CRISPR-based pathogen detection - Yemin Han; Haotian Yu; Manman Lv; Mengqing Cheng; Weihao Li; Houyang Ge; Song Gao; Lu Yin; Qinyu Ge; Xinping Xu; Yan Huang; Longhua Sun; et al. (Analytica Chimica Acta, 2026)

The Impact of Assimilating Dense Smartphone Pressure Observations on a Hailstorm Simulation - Jiming Sun; Rumeng Li; Ge Qiao; Tianxiang Zang; Qinghong Zhang; Juanzhen Sun (Advances in Atmospheric Sciences, 2026)

TRMT10A maintains lipid homeostasis independently of its tRNA m1G9 methyltransferase activity - Huihui Sun; Yu Wang; Shanpeng Liu; Yan Jin; Jianyang Ge; Bowen Zhang; Yongteng Wang; Weifeng Sun; Yun Bai; Yuyong Tao; Yi Lu; Ru-Juan Liu; et al. (Science China Life Sciences, 2026)

Integrative multi-omics reveals NQO1-mediated airway epithelial injury as a key mechanism of bisphenol A–induced COPD - Rui Li; Shaobo Ge; Jin Liu; Yuer Li; Shiyuan Yao; Shuhan Ma; Yuanliang Sun; Xiao Li; Xia Yang; Jie Zhang; Ming Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Preparation of resin-coated dual controlled-release urea amended with nitrogen inhibitors and its effects on soil nitrogen supply and crop yield in wheat–maize rotation - Wenjing Yin; Yaru Ge; Guiyang Sun; Yuanjie Dong (Plant and Soil, 2026)

Genomic and genetic insights into the divergence between indica and japonica rice - Xiangxi Zhuansun; Wenlong Guo; Siqi Xia; Jun Shu; Kai Wang; Qiyu Zhang; Hao Wen; Lina Du; Siyu Wen; Ge Gao; Junran Wang; Dan Wang; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Flexotronic effect-triggered channel switching for high-sensitivity mechanical sensing - Jinwan Chen; Qing Zhao; Zhuangzhuang Zhang; Rui Ge; Hao Sun; Yongkang Zhang; Runze Yu; Longfei Wang; Shuhai Liu (Science Bulletin, 2026)

Study on temperature evolution and associated phase behavior inside an industrial-scale large-diameter test pipeline during liquid CO₂ discharge - Xin Ouyang; Zichao Hu; Tao Wang; Qiqi Liu; Sheng Sun; Ran Sun; Shiqi Ge; Zhenyi Liu (Process Safety and Environmental Protection, 2026)

Investigation on the explosion characteristics and mechanisms of methane blended with hydrogen/ammonia - Tao Wang; Qiqi Liu; Zhenyi Liu; Changqi Liu; Mingzhi Li; Ran Sun; Shiqi Ge; Tao Fan; Zihao Xiu (Process Safety and Environmental Protection, 2026)

Corrigendum to ‘Aeolian processes and their dynamics in the desert-loess transition zone of northwestern China since 20 ka: A synthesis of paleoenvironmental records’ [Quat. Sci. Rev. 382(2026) 109957] - Bing Liu; Hui Zhao; Yujie Xu; Aijun Sun; Jianhui Ge; Linhai Yang; Jun Peng; Zhengcai Zhang; Qinghe Niu; Xiaolei Liang (Quaternary Science Reviews, 2026)

The molecular sieve to component flow transition in oil expulsion from shales: insights from semi-confined pyrolysis of saline lacustrine shale - Zhushi Ge; Xiaoping Liu; Chang Chen; Xiaoguang Li; Yongcheng Chen; Xingzhou Liu; Zilong Zhang; Biao Sun; Yi Zhong; Na Gao; Wenhui Xie (Organic Geochemistry, 2026)

Occurrence and risk assessment of ethyl carbamate in Chinese Baijiu: precursor composition and formation during storage - Yiwen Ge; Bowen Wang; Baoguo Sun; Jungang Lv; Jinyuan Sun (Food Bioscience, 2026)

π-Bridge strategy in conjugated organic polymers activates charge- and energy-involved dual pathways for photocatalytic H₂O₂ production - Xin Sun; Tianyi Wang; Sharidya Rahman; Yuhui Ge; Jindi Yang; Chuanbiao Bie; Hao Zhang; Jacek J. Jasieniak; Xiwang Zhang; Thomas E. Rufford; Xiangkang Zeng (Chemical Engineering Journal, 2026)

Structure and hepatoprotective activity of autophagy-related Butyriboletus roseoflavus polysaccharide - Zhen Sun; Huan Zhang; Dilida Yeerkenbieke; Lu Wang; Yongfeng Zhang; Chunyue Wang; Fan'ge Kong; Yu Li; Di Wang; Lanzhou Li (Carbohydrate Polymers, 2026)

Lewis acid-mediated choline chloride-glycerol deep eutectic solvent pretreatment for Goji berry branches: Enhancing enzymatic saccharification and high-value utilization of lignin - Bingxue Sun; Huaitao Jiang; Guan-Ping Jin; Shi-Kui Han; Bolin Liu; Xiaoli Ge; Xiaoyou Xiu; Biaode Yang (Biomass and Bioenergy, 2026)

PM2.5-attributable chronic disease burden in BRICS–plus countries, 1990–2021: temporal trends and health benefits from optimal control - Jiachang Wei; Mengfei Yang; Yiyang Sun; Quanxi Ge; Sha Yang; Guanran Wang; Jing Ding; Sihan Sun; Li Li (Air Quality, Atmosphere & Health, 2026)

Crop rotation creates a trade-off between soil water storage and plant available silicon depletion - Meixia Wang; Xiaohu Xiong; Yue Sun; Ge Xu; Zimin Li; Weijian Zhou (Plant and Soil, 2026)

Hydraulic performance in low-pressure sprinkler based on droplet spectrum characteristics - Haoyu Zhao; Maosheng Ge; Qingyan Zhang; Xin Hui; Khudayberdi Nazarov; Pute Wu; Caihui Sun (Biosystems Engineering, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

An ovarian follicle-based angiogenesis microphysiological system for high-efficiency screening of anti-angiogenic drugs - Xuebing Yang; Jing Liang; Nan Sun; Lu Mu; Jinfeng Xiong; Ge Wang; Kaiying Geng; Xie’an Feng; Yibo Wang; Shuo Zhang; Xueqiang Xu; Yan Zhang; et al. (Science Bulletin, 2026)

Conversion of waste activated sludge into high-quality denitrification carbon source via moderate pretreatment: Performance, mechanisms, and environmental benefits evaluation - Yifan Sun; Ge Song; Shunan Zhao; Fangzhou Wang; Kai Zhao; Wenwei Li; Ruiping Liu (Resources, Conservation and Recycling, 2026)

Aeolian processes and their dynamics in the desert-loess transition zone of northwestern China since 20 ka: A synthesis of paleoenvironmental records - Bing Liu; Hui Zhao; Yujie Xu; Aijun Sun; Jianhui Ge; Linhai Yang; Jun Peng; Zhengcai Zhang; Qinghe Niu; Xiaolei Liang (Quaternary Science Reviews, 2026)

A Multi-Agent slotted cooperative MAC protocol with channel-Energy awareness for underwater sensor networks - Zhuoran Li; Wei Ge; Yao Sun; Li Wei; Jingwei Yin; Maochun Zheng (Ocean Engineering, 2026)

Automated lithological classification and boundary mapping from 3D point clouds - Zhongxu Wen; Yunfeng Ge; Zihao Li; Huiming Tang; Changyang Liu; Deyang Sun (Engineering Geology, 2026)

Nanocellulose-reinforced deep eutectic solvent-based smart hydrogel sensor for adaptive window regulation and machine learning-assisted low-temperature motion monitoring - Zhenchun Li; Yucong Sun; Jiarui Shen; Rongfeng Ge; Jieli Hua; Zhiyuan Zhao; Ning Li; Yunqi Peng; Jiaqi Hou; Hong Zhang; Lei Wang (Chemical Engineering Journal, 2026)

Pollen-based reconstruction of Anthropocene environmental changes in East Taihu Lake (Eastern China): Impacts of reclamation, agricultural expansion, and urbanization over the past century - Yucui Sun; Zekun Li; Yawen Ge; Mengdi Zhang; Chenlu Ma; Xiangdong Yang; Qinghui Zhang (CATENA, 2026)

Engineering a hybrid chemical-biological system for efficient de novo taurine production via computational enzyme design and pathway engineering - Lingcong Li; Congcong Li; Yanan Chen; Zhoutong Sun; Ge Qu; Liang Wei; Jun Liu (Bioresource Technology, 2026)

A Method for Calculating the Shortest Time Path for the Evacuation and Transfer of People at Risk of Flooding - Wei Ge; Heqiang Sun; Yutie Jiao; Laihong Jing; Yadong Zhang; Meimei Wu; Te Wang; Hua Zhang; Jianyou Wang; Yupan Qin; Fuheng Ma; Pieter van Gelder (Water Resources Management, 2026)

Diverse Neuronal Activity in Barrel Cortex During Self-Grooming and Whisking in Mice - Junye Ge; Baijun Chen; Jinwei Xu; Pengfei Ren; Jialong Li; Tangna Sun; Shengxi Wu; Ying Zang; Wenting Wang (Neuroscience Bulletin, 2026)

Arbuscular mycorrhizal fungi hypha shape atrazine degradation ability of microbiota by increasing soil aggregation - Yang Sun; Hongyang Pan; Ge Song; Sisi Chen; Alexander V. Kurakov; Fuqiang Song; Jing Wang; Xiaoxu Fan (Mycorrhiza, 2026)

Analysis of Blocking Slurry Diffusion Parameters for a New Self-Starting Drainage Anchor Cable - Xu Wang; Qi Ge; Chengcheng Lyu; Junwei Shu; Hongyue Sun (Journal of Earth Science, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

A Galactose-Modified Light-Activatable Persulfurated Arene Fluorescent Probe for Targeted Imaging of Polarity and Viscosity in Liver Cancer Cells - Pan-Xin Ge; Yan Rong; Lu-Lu Sun; Yuqing Hu; Xianzhi Chai; Hai-Hao Han; Liangliang Zhu (Journal of Fluorescence, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Local administration of polymyxin B-conjugated Akkermansia muciniphila outer membrane vesicles attenuate asthma by suppressing M2 macrophage polarization - Chenchen Hou; Wenhui Sun; Lina Wang; Xiahui Ge; Qiyun Tu; Huaqi Guo; Tianyu Zhou; Lifeng Yan; Weining Xiong (Science China Life Sciences, 2026)

Sex differences in neural stress responses over psychosocial stress exposure - Daifeng Dong; Chuting Li; Chang Cheng; Xiaoqiang Sun; Ge Xiong; Shuqiao Yao; Xiaocui Zhang; Xiang Wang (Brain Structure and Function, 2026)

Hydrophobic high-frequency vibration collaborative strategy for reducing resistance and soil adhesion of tillage tools in lime concretion black soil - Kuan Qin; Ding Zhang; Biao Ma; Weidong Gao; Chengmao Cao; Xu Zhu; Junjie Lu; Wei Wang; Jun Ge; Qichun Feng; Huaizhi Liu; Siliang Liu; et al. (Soil and Tillage Research, 2026)

Quantification method for comprehensive flood control benefits of an earth-rockfill dam reservoir considering dam break effects - Yadong Zhang; Jian Zhou; Yutie Jiao; Haoyuan Sun; Heqiang Sun; Wei Ge; Zongkun Li (Journal of Hydrology, 2026)

Scalable molten salt electrochemical siliconizing tailors texture in silicon steel for superior electromagnetic properties - Xinrui Wang; Zheng Huang; Junqing Zhang; Jingya Xu; Mingyong Wang; Jianbang Ge; Yiwa Luo; Dongbai Sun; Weili Song; Zhe Wang; Shuqiang Jiao (Journal of Cleaner Production, 2026)

Dietary goat milk extracellular vesicles remodel the microbiota–gut–brain axis to alleviate adolescent anxiety - Yuting Ye; Junlin Ge; Peiyi Yang; Xinran Liu; Danna Wang; Jingyu Hao; Sufang Duan; Lijun Sun; Guoqiang Zhang; Jian He; Xuebo Liu (Food Research International, 2026)

Carbohydrates: How structural features influence digestion-fermentation kinetic parameters - Ge Zhang; Li Cao; Zhiqiang Sun; Jingyi Huang; Qi Zhu; Lee J. Johnston; Zeyu Zhang; Junjun Wang; Jinbiao Zhao (Food Chemistry, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

Sturgeon peptide LLLE alleviates permethrin-induced obesity by modulating gut microbiota and liver transcriptome in high-fat diet-fed mice - Ge Chen; Ge Wang; Jiani Yang; Ting Gu; Quancai Sun; Ye Peng (Food Bioscience, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Intrinsic Brain Activity Alterations in Disorders of Consciousness: A Parallel Resting-State fMRI Analysis at 7 Tesla - Xufei Tan; Yuan Sun; Ge Li; Shanshan Song; Shanshan Wu; Jian Gao (Brain Topography, 2026)

3D Geometry Scanning and Structural Integrity Assessment to Advance Meniscus Allograft Transplantation - Shuchun Sun; Ge Pan; Jichao Zhao; William Michael Pullen; Jian Chen; Haiyang Ma; William C. Bridges; Dustin Mueller; Hai Yao; Shangping Wang (Annals of Biomedical Engineering, 2026)
Purpose Meniscal allograft transplantation can restore joint biomechanics and alleviate symptoms, but its clinical use is limited by the scarcity of size-matched, structurally intact grafts. Current two-dimensional sizing and subjective inspection in tissue banks fail to capture complex three-dimensional geometry and subtle surface defects, highlighting the need for an accurate, reliable, and practical solution for routine donor tissue evaluation. Methods We developed an integrated system combining optical 3D scanning with curvature-based analysis for 3D geometry capture and surface defect detection in meniscus allografts. System performance was validated in terms of scanner accuracy and tissue bank workflow feasibility. Results The system completes each scan within 2 versus ~ 60 min for micro-computed tomography (μCT). It demonstrated μCT-comparable accuracy (mean volume difference: 6.9%; surface deviation: 8.3%). Scanning through phosphate buffer saline (PBS)-immersed transparent bags yielded equivalent accuracy to scanning in air (mean volume difference: 7.2%; surface deviation: 12.5%). The workflow demonstrated high intra- and inter-operator reproducibility. Viability testing revealed PBS-preserved tissues maintained > 94% viability for 20 min, whereas air-exposed tissues dropped below 70% within 10 min. For defect assessment, curvature metrics reliably identified surface wear, longitudinal, and radial defects, with size measurements for wear and longitudinal tears showing equivalence (± 10% margin) to stereomicroscopy. Conclusion This portable system enables accurate and rapid 3D scanning under tissue banking conditions and quantitative surface defect detection. It supports improved graft shape matching and surface defect screening, offering a practical and scalable solution for tissue banks and clinical settings, potentially extendable to other fibrocartilaginous and osteochondral tissues.

Development and validation of an RPA-CRISPR/Cas12a based platform for rapid and sensitive detection of Anguillid herpesvirus 1 - Bin Sun; Qiang Chen; Jun-Qing Ge (Aquaculture, 2026)

Responses of ecological stability in subtropical coastal phytoplankton communities to varying N:P ratios under present and future scenarios - Jichen Chen; Yonglong Xiong; Jingke Ge; Xin Zhao; Yuan Feng; Xu Li; Chi Song; Xiao Yang; Rui Zhang; Jin-Yu Terence Yang; Wuchang Zhang; Shengyao Sun; et al. (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Numerical prediction on cavitation characteristics of a marine propeller in oblique flow without and with hull wake effects - Yu Sun; Shengyao Ge; Rui Wu; Wenyu Chen; Han Han; Depeng Ma; Huan Ping (Ocean Engineering, 2026)

Asynchronous Holocene moisture and precipitation variability in the Tibetan Plateau monsoon-westerlies transition zone - Tianlong Yan; Xiaomin Gao; Ge Shi; Chun Wang; Junjiang Dong; Qi Zhang; Xiaoru Zhang; Xiaoshuang Sun; Jinliang Liu; Can Zhang; Cheng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Enhanced dust removal with charged active water mist: Insights from macro-experiments and molecular simulations - Liying Sun; Shaocheng Ge; Jiace Guo; He Liu; Weizhi Zhao; Yongliang He; Jiacheng Nie (Journal of Environmental Chemical Engineering, 2026)

Co-gasification coupled with steam reforming of inseparable livestock biowastes for green hydrogen-rich syngas production - Jiarui Zhu; Qiuhan Pu; Liang Wang; Ge Kong; Zengjian Guo; Ru Sun; Guanyu Zhang; Xin Zhang; Xuesong Zhang; Lujia Han (Journal of Environmental Chemical Engineering, 2026)

Tracking viral variants by wastewater surveillance, from laboratory diagnosis towards on-site monitoring: lessons learned from the SARS-CoV-2 pandemic - Qifeng Zhang; Chuanzuo Gao; Xinyue Ge; Yuchen Sun; Peng Liu; Xu-Xiang Zhang (Journal of Environmental Management, 2026)

Multiscale investigation of oxidative aging on thiol–functionalized montmorillonite: Correlating structural and chemical degradation to the reduced affinity for Hg(II) and MeHg - Ning Wang; Penggang Pei; Ge Gao; Yundi Kan; Linna Zhou; Bozhen Yu; Yuebing Sun (Journal of Environmental Chemical Engineering, 2026)

Deep learning-based realtime multiload response prediction and inverse analysis of offshore bridges - Zhu-Yu Sun; Yu-Tao Guo; Kang Ge; Chao Hou; Zhen-Zhong Hu (Engineering Structures, 2026)

Behavior and evaluation of the lap splice for steel-FRP composite bars embedded in concrete beams - Yi Zheng; Zeyang Sun; Liuzhen Yao; Xin Wang; Yang Wei; Hanbin Ge (Engineering Structures, 2026)

Dilute-O2-flash-etching introduced eco-fabrication of high-plateau-capacity hard carbon for performance sodium-ion batteries - Haonan Zhang; Jianjun Zhao; Anuj Kumar; Xiujie Ge; Yanzhi Sun; Mohd Ubaidullah; Junqing Pan (Chemical Engineering Journal, 2026)

Synergistic promotion of diabetic wound healing by glucose-responsive functional chitosan-based composite nanohydrogels - Runze Yang; Jiale Sun; Guanglan Peng; Mingcai Wu; Chengen Guan; Jianping Yang; Zeyuan Wang; Wanzhen Li; Longbao Zhu; Jun Wang; Zuchun Zhao; WeiWei Zhang; et al. (Carbohydrate Polymers, 2026)

Tenuigenin exerts neuroprotective effects by activating the Nrf2/HO-1 pathway to perform antioxidant activity and inhibit neuronal ferroptosis, preventing epilepsy in immature mice - Qinyun Zhang; Lili Huang; Linling Zhou; Wenfeng Fang; Jie Xu; Siyuan Ma; Chun Ge; Lili Sun; Chen Bu; Weijiang Wu (Molecular & Cellular Toxicology, 2026)

Association of neural responses to acute psychosocial stress with relapse in depression - Daifeng Dong; Chuting Li; Chang Cheng; Xiaoqiang Sun; Ge Xiong; Shuqiao Yao; Xiaocui Zhang; Xiang Wang (Brain Imaging and Behavior, 2026)

MTA-SM: Multi-machine path planning and time-window scheduling joint optimization method in hilly safflower harvesting - Liwei Yang; Ping Li; Zhongshuo Ding; Chao Sun; Fei Chen; Yijiang Zheng; Yun Ge (Computers and Electronics in Agriculture, 2026)

Interfacial electron transfer facilitated the bioreduction of biochar-sorbed organic pollutants: Division-of-labor roles of electroactive structures - Jia Xing; Shaofeng Zhou; Meng Ge; Zhiqiang Sun; Shujie Cai; Yingying Li; Meiying Xu (Water Research, 2026)

Adversarial autoencoder enhanced evolutionary guidance for multi-objective multi-task optimization - Xia Wang; Hongwei Ge; Yaqing Hou; Liang Sun; Bin Li (Swarm and Evolutionary Computation, 2026)

Late Holocene temperature changes in eastern North China reconstructed from branched glycerol dialkyl glycerol tetraethers (brGDGTs) - Hongyu Song; Ying Wang; Huaying Wang; Can-Ge Li; Yuecong Li; Bing Li; Yawen Ge; Rongrong Wang; Xiuyun Sun; Ran Zhang; Hanfei You; Changhong Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Study on the migration mechanism of heavy metals in the supercritical water gasification of coal - Hao Sun; Jiayi Yu; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2026)

Enhancing electrochemical CO2 reduction with monoamino-functionalized cobalt tetraphenylporphyrin catalysts - Li-Yuan Zhao; Hui Wang; Hao Tan; Jie Chao; Zhi-Hang Lin; Ge-Chuan-Qi Pan; Xiao-Ji Wang; Qiang Sun (Fuel, 2026)

Preparation of responsive photonic crystals and their application in the detection of food hazards - Ting Li; Haihu Tan; Yang Liu; Chao Ge; Zhouyu Sun; Zengmin Tang; Ling Yang (Food Control, 2026)

Bacterial cellulose/tea polyphenol films from tea waste via anaerobic synthesis: A sustainable material for active food preservation - Ge Gao; Haolong Zheng; Shaofang Niu; Yi Wang; Xueqing Zhao; Yucheng Shi; Liyuan Sun; Mingchang Li; Guoqiang Li; Ting Ma (Food Packaging and Shelf Life, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

In-situ cultivation and process dynamics of algal-bacterial granular sludge in a continuous-flow self-circulation reactor - Wei-Kang Qi; Yu-Ge Sun; Ming-Ming Zhang; Rui Hu; Yong-Zhen Peng; Cong Wang (Bioresource Technology, 2026)

Correction to: Temporal dynamics of climate and needle litter chemistry in driving decomposition along the entire decomposition process for Norway spruce - Björn Berg; Tao Sun; Maj-Britt Johansson; Jielin Ge (Plant and Soil, 2026)

An approach for formulating dynamic irrigation schedules in alfalfa based on virtual-real fusion - Yongqi Ge; Rui Liu; Pengpeng Sun; Liguo Dong; Libo Liu (Plant and Soil, 2026)

Influences of Structural and Species Diversity on Forest Resistance to Drought - Erin T. H. Crockett; Qinfeng Guo; Jeff W. Atkins; Ge Sun; Kevin M. Potter; Jennifer K. Costanza; Scott V. Ollinger; Christopher W. Woodall; Steven McNulty; Carl Trettin; Justin Holgerson; Jingfeng Xiao (Ecology Letters, 2026)
Biodiversity can enhance forest resistance to drought, but the forms of diversity involved and conditions under which diversity confers resistance remain unclear. We used Forest Inventory and Analysis (FIA) plot data to examine whether four variables—structural richness (variation in tree heights, stand density, canopy cover and/or spatial heterogeneity), species richness (number of tree species), structural evenness and species evenness—are associated with the resistance of net primary productivity to drought and whether these relationships change with drought severity and by ecoregion. Structural richness was positively associated and species evenness was negatively associated with resistance, but the strength of these relationships varied by ecoregion. Relationships between structural richness and resistance and between species evenness and resistance became stronger under more severe droughts, supporting the stress gradient hypothesis. Forest managers cannot readily change abiotic conditions but could increase structural richness and select certain species to enhance forest resistance to drought.

PROSAIL-DNN: a fine-tuning transfer learning framework for field-scale oat leaf area index monitoring from UAV imagery - Pengpeng Zhang; Bing Lu; Jiali Shang; Shuaijie Shen; Junyong Ge; Xingyu Wang; Shuchang Sun; Yadong Yang; Huadong Zang; Zhaohai Zeng (Computers and Electronics in Agriculture, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Study on plasma-activated supersonic water fog atomization and dust suppression performance - Mu Xinsheng; Ge Shaocheng; Zhang Tian; Jing Deji; Liu Shuo; Sun Liying; Pang Xingyu (Process Safety and Environmental Protection, 2026)

Bio-inspired channel configuration derived from morphological traits of thoracic ribcage and dendritic branching for bipolar plates of the proton exchange membrane fuel cell - Jing Lv; Weiwei Ge; Weili Sun; Haoyan Fang; Yong Zhang; Qingshan Liu (Process Safety and Environmental Protection, 2026)

Energy-efficient chlorine-mediated paired electrocatalysis for simultaneous H2O2 production and coal chemical wastewater purification - Jiana Jing; Yingying Du; Chunhong Fu; Jiangli Sun; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2026)

Geochemical signatures, hydrocarbon generation kinetics, and oil-source correlation of the Es4 member source rocks in the Liaohe Western depression: implications for tight oil exploration in continental rift basins - Zhushi Ge; Xiaoping Liu; Xiaoguang Li; Yongcheng Chen; Chang Chen; Zilong Zhang; Biao Sun; Yi Zhong; Xueyou Tan; Gaohang Jia; Yu Xia; Zuowei Li; et al. (Fuel, 2026)

Molecular structure-based prediction of the effectiveness of surfactant wetting of coal surfaces: molecular simulations and quantum chemical calculations - He Liu; Shaocheng Ge; Weizhi Zhao; Liying Sun; Xi Chen; Xingyu Pang; Hongjie Zhang (Fuel, 2026)

Ultrasound-assisted extraction of peptidoglycan from Lactiplantibacillus plantarum: Structural characterization, anti-browning enhancement, and immunomodulatory effects - Yuwei Sun; Kemin Guo; Peiyun He; Dongning Li; Yunshu Ge; Guoqiang Zhang; Xuebo Liu (Food Chemistry, 2026)

Underlying mechanism and the effect of diacylglycerols on the protein structural stability and in vitro digestibility of pork meatballs - Xinxin Zhao; Yunling Jiang; Zixin Luo; Xiankun Sun; Jiangyu Zhu; Hai Yu; Xinyan Peng; Qingfeng Ge (Food Chemistry, 2026)

Impact of solid-state fermentation using Jiuqu microbiota on dietary fiber of wheat bran and textural properties of whole wheat products - Yaxuan Peng; Ao Wang; Ge Zhang; Rongjia Sun; Haoran Fan; Shiyi Lu; Hongyan Li; Jing Wang; Baoguo Sun (Food Bioscience, 2026)

Construction of 1D–2D/0D Co3O4/LaF3 heterojunction for integrated enhancement of capacity, rate capability, and voltage window in aqueous supercapacitors - Yin Sun; Haowei Wang; Maosheng Ge; Shuhuang Tan; Banglin Deng; Kun Zhang; Haibang Zhang; Shoujun Zhang; Chengqi Sun; Xinyu Wang (Chemical Engineering Journal, 2026)

Intestinal toxicity and microbiota dysbiosis in zebrafish exposed to spirotetramat - Xunyue Liu; Junyao Ge; Haojie Zhu; Peng Liu; Huidi Zhang; Qiong Rao; Wenze He; Jianqiang Sun (Aquatic Toxicology, 2026)

Correction to: Gastrodin alleviates loperamide-induced slow transit constipation in mice by modulating the MAPK signaling pathway - Xinyu Ge; Bozhao Wu; Xiaohui Dou; Mingchen Sun; Ji-ao Wu; Daqing Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Gastrodin alleviates loperamide-induced slow transit constipation in mice by modulating the MAPK signaling pathway - Xinyu Ge; Bozhao Wu; Xiaohui Dou; Mingchen Sun; Ji-ao Wu; Daqing Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Integrated items safety classification method considering risk evaluation for nuclear reactors - Ming Sun; Xiaoer He; Longlong Tao; Shaoxuan Wang; Daochuan Ge; Chenglong Cao; Zhongchang Zhang (Annals of Nuclear Energy, 2026)

Lower Cretaceous palynoflora from the Binggou Formation of Jianchang Basin, western Liaoning, NE China and its U–Pb zircon age - Xiao Tan; Yuhui Feng; Fei Liang; Yunfeng Li; Chunlin Sun; Ge Sun (Cretaceous Research, 2026)

Effects of Dietary Strontium Supplementation on Growth Performance, Strontium Enrichment, Muscle Nutrition, and Hepatic Lipid Metabolism in Juvenile Hybrid Sturgeon (Acipenser baerii ♀ × Acipenser schrenckii ♂) - Shilin Li; Qiang Zhao; Hang Chen; Yanhan Yang; Zhe Zhao; Jianxi Mei; Yuexin Sun; Li Peng; Hailong Ge; Fang Li; Zhijian Wang (Fishes, 2026)
To explore a safe and effective approach for producing strontium-enriched fish, in this study, we modified the feed for juvenile hybrid sturgeon (Acipenser baerii ♀ × Acipenser schrenckii ♂) and set three different levels of strontium chloride content in their diet (0 mg/kg (Sr0, control), 80 mg/kg (Sr80), and 160 mg/kg (Sr160)) for a period of 8 weeks, analyzing their growth performance, strontium enrichment, muscle nutrition, and hepatic physiological, biochemical, and transcriptomic characteristics. The results show that dietary strontium had no significant impact on sturgeon growth or survival rate (p > 0.05). The strontium content in tissues increased with dietary strontium levels, with the highest enrichment in bone plates (p

Dynamic characteristics analysis of pneumatic collection device for continuous harvesting of dry safflower based on CFD-DEM - Chao Sun; He Zhang; Yun Ge; Haifeng Zeng; Yijiang Zheng (Computers and Electronics in Agriculture, 2026)

Heavy metal pollution in the Jiaodong peninsula: Spatial patterns, elemental mobility, and source-derived ecological impacts - Yang Liu; Xiaoyuan Gu; Jianwei Sun; Haigen Wang; Qingtong Wang; Binghui Feng; Yuhai Chen; Chunhui Ma; Xiangwei Ge; Fengbin Zhu; Shixiong Yang (Marine Pollution Bulletin, 2026)

Identification of Aeromonas hydrophila PS-1 and GFP-labeled tracking of its infection in Pelodiscus sinensis - Fa Dai; Siyu Chen; Wei Sun; Jiehao Xu; Chutian Ge; Xiaodong Zhang (Aquaculture, 2026)

Copper exposure induces autophagy and angiogenesis in liver cell via ATF4 activation independent of TFEB - Meng Zhang; Yi-Ge Zhang; Yu-Tian Shi; Xiao-Chuan Qu; Yu-Heng Li; Ji-Xing Miao; Guo-Ming Sun; Peng Ge; Bao-Qin Liu (Toxicology, 2026)

Naringenin as a bioactive preservative: Coordinated suppression of ethylene biosynthesis and cell wall disassembly delays apple senescence during storage - Ming-Fei Qiao; Peng-Liang Han; Meng-Meng Wei; Zhao-Peng Nie; Song Zhang; Wen-Yan Wang; Hai-Bo Wang; Tian-Ge Chu; Ze Chen; Quan Sun; Da-Gang Hu (Postharvest Biology and Technology, 2026)

Ultraviolet-treated riboflavin induces ROS-mediated apoptosis via inhibiting mitochondrial complex I in acute myeloid leukemia - Ruining Liu; Shuang Ge; Jinyuan Sun; Yi Liu; Liping Sun; Yang Yu; Deqing Wang (Journal of Photochemistry and Photobiology B: Biology, 2026)

Uncovering ecological risks of pesticides: From parent compounds to unknown transformation products in soils from Dongting Lake Basin - Lu Liu; Pingping Wang; Feng Li; Xiaoxiao Li; Meng Gao; Yiming Yao; Yu Wang; Zhipeng Cheng; Fei Ge; Hongwen Sun (Journal of Hazardous Materials, 2026)

Impact of temperature on the biogenic volatile organic compound (BVOC) emissions in China: A review - Yiming Yang; Fengbin Sun; Yusheng Chen; Shiyue Yang; Yuan Dai; Yiming Qin; Ning Zhang; Zhifeng Shu; Han Yan; Xinlei Ge; Junfeng Wang (Journal of Environmental Sciences, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Nondestructive assessment of refrigerated quality attributes of kiwifruit via hyperspectral imaging coupled with a point-to-interval prediction model - Sunli Cong; Jun Sun; Lei Shi; Chunxia Dai; Xiaohong Wu; Bing Zhang; Kunshan Yao; Xiao Ge (Food Chemistry, 2026)

Mechanistic insight into curcumin-induced conjugative plasmid transfer acceleration: Role of intracellular arginine uptake - Min-ge Wang; Kai-di Liu; Wen-jie Jin; Run-bo Li; Jun-qi Liu; Liang-xing Fang; Jian Sun; Xiao-ping Liao (Food Microbiology, 2026)

Seasonal transmission characteristics, interconnections and risk assessment of bioaerosol-mediated ARGs and bacteria in the underground wastewater treatment plant - Jingyun Ge; Hongyu Tian; Jianwei Liu; Jianbin Sun; Yunping Han (Environmental Research, 2026)

Smart, tumor-targeted, and responsive intracellular delivery engineering (STRIDE) nanoplatform: co-delivery of siGLI1 and cisplatin prodrug to overcome lung adenocarcinoma chemoresistance - Ge Chen; Mengyang Liu; Yanan Sun; Shifei Zhang; Qingyi Liu; Yuxiang Liang; Kexin Cong; Meng Yan; Zhigan Zhang; Jinjiang Deng; Zongyu Wang; Ziqiang Li; et al. (Chemical Engineering Journal, 2026)

Refining the regionalization for debris flows along the eastern margin of the Qinghai-Tibet Plateau - Xinyue Liang; Yonggang Ge; Lu Zeng; Yuqing Sun; Liqun Lyu (CATENA, 2026)

Suppression of endothelial cell PANoptosis: qingyi decoction targets the TMAO-HMGB1 pathway to mitigate lung injury in acute pancreatitis rats - Jie Liu; Peng Ge; Zhenxuan Sun; Yalan Luo; Lu Xun; Huijuan Li; Xinyu Luo; Xuetao Zhang; Boliang Pei; Yinan Cao; Guanyu Wang; Hailong Chen (Apoptosis, 2026)

Ensemble Modelling Predicts Habitat Shifts for Portunus trituberculatus Under Climate Change in the East China Sea and the Yellow Sea of China - Fengqi Sun; Hongliang Zhang; Guoqiang Xu; Hui Ge; Lei Wu; Zhenhua Li; Shuwen Yu; Jiayi Zhou; Shihao Wang; Yongdong Zhou (Journal of Marine Science and Engineering, 2025)
This study systematically evaluated the dynamic habitat suitability of Portunus trituberculatus in the East China Sea and the Yellow Sea region (referred to herein as the East Yellow Sea region for brevity) under climate change impacts by integrating a species distribution model (Biomod2) with multi-source environmental data. Through the construction and evaluation of an ensemble model combining 10 algorithms, using the Area Under the Curve (AUC) and True Skill Statistic (TSS) for validation, we identified seabed temperature, seabed salinity, and chlorophyll as key environmental factors. Results showed that current high-suitability areas are concentrated in coastal Jiangsu, the Yangtze River estuary, and Zhoushan Archipelago waters, which overlap significantly with fishing hotspots. Under future climate scenarios, the species’ suitable habitat distribution is projected to shift significantly poleward: In the SSP5-8.5 scenario 2100, low/medium suitability areas increased by 38.2% and 88.2% respectively, while high-suitability areas decreased by 36.5%, with core spawning grounds (e.g., Zhoushan Archipelago waters) showing reduced suitability indices. The Bohai Sea’s summer water temperature unsuitability for Portunus trituberculatus migration creates an “ecological bottleneck” for northward expansion. The study proposes strengthening habitat management in Jiangsu coastal areas and integrating dynamic habitat prediction into fisheries policies to address climate-induced resource redistribution and ecosystem service changes. Our findings underscore the urgency of incorporating climate-driven habitat shifts into adaptive marine spatial planning and fisheries management frameworks.

Differential evolution with bi-strategy co-deployment framework and diversity improvement - Liangliang Sun; Zhenghao Song; Ge Guo; Yucheng Zhang; Natalja Matsveichuk; Yuri Sotskov (Swarm and Evolutionary Computation, 2025)

Corrigendum to “Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms” [Science of the Total Environment, 880 (2023) 163314] - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Shuangxi Li; Peng Li (Science of The Total Environment, 2025)

A novel deep learning system for STEMI prognostic prediction from multi-sequence cardiac magnetic resonance - Yifan Chen; Meng Jiang; Chao Xia; Hang Zhao; Panpan Ke; Sheng Chen; Heng Ge; Keran Li; Xu Wang; Yufei Wang; Yezi Chai; Qiming Liu; et al. (Science Bulletin, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

The sedimentary provenance of Upper Miocene Dongfang submarine fan, Yinggehai Basin: source-to-sink system unravelled through new detrital zircon U-Pb ages and heavy mineral analysis - Xingzong Yao; Congjun Feng; Wei Zhou; Pengfei Wu; Hongjun Qu; Jiahao Lei; Zhiqiang Chen; Yanlong Ge; Mengsi Sun (Marine and Petroleum Geology, 2025)

Earthworm intestine orchestrates dual host-microbiome detoxification of 6PPD-quinone - Ruiying Shi; Weitao Liu; Xinwei Shi; Xiang Li; Yichen Ge; Jinzheng Liu; Aurang Zeb; Yuexing Zhao; Yuebing Sun; Jing An (Journal of Hazardous Materials, 2025)

6PPD-Q driven rare and abundant taxa functional partitioning shapes soil ecological response - Xinwei Shi; Weitao Liu; Ruiying Shi; Yichen Ge; Xiang Li; Chuan Yin; Jinzheng Liu; Yuexing Zhao; Dasong Lin; Yuebing Sun (Journal of Hazardous Materials, 2025)

Unraveling polarity-dependent adsorption and charge transfer in charged droplet-dust interactions: Toward cleaner coal production - Weizhi Zhao; Shaocheng Ge; He Liu; Liying Sun; Tianyi Yang; Shuo Liu; Hongjie Zhang (Journal of Cleaner Production, 2025)

Analysis of the time-varying characteristics of the relationships and influence degrees among dam economic life influencing factors - Heqiang Sun; Wei Ge; Fuheng Ma; Zongkun Li; Yadong Zhang; Menglu Xia; Jianyou Wang; Pieter van Gelder (Journal of Cleaner Production, 2025)

Foliar exposure to 6PPD-Q disturbs photosynthetic processes and induces oxidative stress in Eichhornia crassipes - Yichen Ge; Ruiying Shi; Weitao Liu; Xiang Li; Xinwei Shi; Aurang Zeb; Yuexing Zhao; Jing An; Yuebing Sun (Journal of Environmental Management, 2025)

Enhanced humic acid removal via floc-based dynamic membrane for high-salinity water treatment - Jingqiu Sun; Haotong Ge; Yao Xu; Yixuan Ma; Sujie Shan; Songqi Liu; Dapeng Li (Journal of Environmental Chemical Engineering, 2025)

Developing a multi-scale adaptive generalized morphological filtering algorithm for denoising ocean wave-induced interference in marine electromagnetic data - Jianxin Pei; Yanyan Lu; Zhijun Du; Ming Luo; Gongyi Sun; Jiaqi Ge (Journal of Applied Geophysics, 2025)

Synchronized removal of non-rare earth ions (Al3+, Fe3+, Th4+, U6+, and F−) from rare earth leach solutions using lanthanum‑cerium oxides for pH adjustment - Di Wu; Xinjin Xiao; An Guo; Qiaofa Lan; Huijuan Wang; Liusheng Ge; Xiaoqiang Wen; Lingdong Sun; Chunsheng Liao (Hydrometallurgy, 2025)

Proteomic and flavor dynamics in irradiated scallop adductor muscle during refrigerated storage via 4D-DIA proteomics - Zhupeng Zhang; Peng Ge; Chaoqi Han; Jie Zhang; Richeng Yu; Wenxiu Wang; Ran Suo; Jianfeng Sun (Food Chemistry, 2025)

A comprehensive story of pea peptides and pea polyphenols: Research status, existing problems, and development trends - Xinyu Sun; Guocong Ma; Dan Hai; Ge Bai; Qi Guo; Tianlin Wang; Xianqing Huang; Lianjun Song (Food Chemistry, 2025)

Effect of electron beam irradiation on physicochemical and protein properties of scallop adductor muscles during cold storage - Zhupeng Zhang; Peng Ge; Chaoqi Han; Fan Zhang; Wenxiu Wang; Ran Suo; Qianyun Ma; Zhenzhen Wang; Jianfeng Sun (Food Chemistry, 2025)

Synthetic phenolic antioxidants in paddy soils from central China: Contamination characteristics and risk prioritization analysis - Mohan Ma; Meng Gao; Zixiao Zhao; Siyuan Li; Yimeng Si; Liman Wei; Yiting Ge; Yu Wang; Feng Li; Bing Li; Chunguang Liu; Fei Ge; et al. (Environmental Pollution, 2025)

Radiofrequency electromagnetic heating enhanced vitrification of viable large cartilage tissues - Haiyang Ma; Josh Wewerk; Ge Pan; A.J. Riffe; Peng Chen; Yaqian Sun; John M. Alford; Kristi Helke; Girish Srinivas; Hai Yao; David P. Eisenberg; Shangping Wang (Cryobiology, 2025)

Four-month evaluation of vitrified meniscal allograft transplantation in a pig model - Ge Pan; Haiyang Ma; Kristi Helke; William Michael Pullen; Meenakshi Mukherji; Daniel Eldridge; Peng Chen; Dustin Mueller; Shuchun Sun; Yongren Wua; Tong Ye; Hai Yao; et al. (Cryobiology, 2025)

Specific microenvironment modulation around Zr clusters via linker engineering in metal-organic frameworks for enhanced catalytic transfer hydrogenation - Mingwei Ma; Xuesong Wu; Xin Wang; Jing Sun; Ge Tian; Hui Liu; Zhongmin Su (Chemical Engineering Journal, 2025)

Fabrication of Ni-NiO@polyaniline for highly selective and fast room-temperature NH3 sensing: p-n response transition based on heterogeneous interface engineering - Yeguang Zhang; Zichang Zhang; Guangqiang Chen; Shuni Li; Feihu Li; Shuzhuang Sun; Peng Wang; Fang Fang; Jingmin Ge; Zili Zhan (Chemical Engineering Journal, 2025)

New uses for old drugs: Targeted paroxetine-loaded liposomes for effective inhibition of cardiac fibrosis - Yang An; Ge Sun; Zhenzhen Dong; Yang Liu; Yubiao Huang; Xiaoyu Cheng; Wentao Zheng; Jiarui Du; Na Li; Yinlong Zhang; Chengzhi Yang (Chemical Engineering Journal, 2025)

Decoding visual engagement in urban green spaces: A multisensory VR eye-tracking approach to vegetation-driven preference and perception - Baihe Zhao; Jianyi Yang; Ge Sun; Jiahui Hou; Ling Qiu; Tian Gao (Building and Environment, 2025)

Improvement and Recovery of Intestinal Flora Disorder Caused by Ciprofloxacin Using Lactic Acid Bacteria - Xiumin Su; Li Su; Mengyuan Cao; Yulu Sun; Jinghan Dai; Yuanjie He; Wei Li; Wupeng Ge; Xin Lv; Qiang Zhang; Shenghui Cui; Jia Chen; et al. (Probiotics and Antimicrobial Proteins, 2025)

Prevalence and molecular spectrum of thalassemia in infertile population among different ethnic groups in Hainan Province, China - Yongle Zhang; Jinyu Kang; Wenye Sun; Fei Sun; Ge Gao; Junhong Chen; Qi Li; Qiuling Jie; Yanlin Ma (Molecular Genetics and Genomics, 2025)

Deficiency of SCAMP5 causes Parkinson’s disease due to loss of dopamine neurons - Huihui Liu; Shunnan Ge; Zhenxing Liu; Meiqi Hou; Weimin Jia; Jinze Li; Guihua Wang; Nianyi Sun; Xuelian Wang; Xianqin Zhang (Human Genetics, 2025)

A novel PADI6 splice-site variant induces non-canonical GC-AG splicing and embryonic arrest in humans - Huiling Hu; Jiaqi Sun; Fei Meng; Fei Gong; Ge Lin; Lizhi Leng; Wei Zheng (Functional & Integrative Genomics, 2025)

Regional collaborative data harmonization: Building the next generation of global observations - Stephanie D. Jurburg; Clara Arboleda-Baena; An Xie; Rongxiao Che; Tida Ge; Yuyi Yang; Yanjiang Cai; Yongyu Zhang; Gang Li; Xin Sun (Soil Ecology Letters, 2025)

Ensemble Experiments in an AI-NWP Coupled Framework: A Typhoon Case - Yangjinxi Ge; Donghai Wang; Zheng Yang; Junying Sun; Yu Jiang; Jiangli Zuo; Sunyi Yuan; Fengxian Wang (Journal of Meteorological Research, 2025)

Limitation of the Application of Heat Tracer in Investigating Groundwater and River Interactions under Dynamic Flow Conditions - Mengyan Ge; Rui Ma; Ziyong Sun (Journal of Earth Science, 2025)

A Sediment Record from a Modern Glacial Lake in the Central Himalayas: Implications for Proxy Interpretation in Glacial Lake Studies - Zhe Sun; Kejia Ji; Can-Ge Li; Mingda Wang; Juzhi Hou (Journal of Earth Science, 2025)

Growth performance and RIG-I-like receptor expression modulation by dietary Sanghuangporus vaninii in juvenile Chinese soft-shelled turtle (Pelodiscus sinensis) - Yirong Wu; Tianxin Zhuang; Lingli Jiang; Shufeng Jin; Xuechen Zhang; Chenxi Shao; Wei Sun; Chutian Ge; Youling Gao (Aquaculture International, 2025)

Global, regional, and Chinese disease burden and trends of colorectal cancer, 1990–2021: An update from the GBD 2021 study and implications for predictive, preventive, and personalized medicine - Yanqi Kou; Yujie Lu; Renwei Huang; Bilan Sun; Shicai Ye; Qing Zhang; Ke Yang; Kun He; Tingting Wu; Xiang Dong; Yajuan Chen; Lei Ge; et al. (EPMA Journal, 2025)

A novel mycotoxin-degrading enzyme complex can biodegrade AFB1, DON, and ZEN co-contamination in both in vitro and in vivo experiments - Yan-Qi Ning; Zhe Peng; Yu Zhang; Alainaa Refaie; Jing-Hui Ge; Li-Jia Guo; Wen-Jie Yang; Lv-Hui Sun (Toxicon, 2025)

Selective interaction of BmNPV Bm65 with host proteins before and after ultraviolet radiation - Yutong Liu; Jiayin Huang; Guohui Li; Feifei Zhu; Qian Yu; Lindan Sun; Huiqing Chen; Liang Chen; Qi Ge; Shangshang Ma; Xiaoyong Liu; Keping Chen; et al. (Pesticide Biochemistry and Physiology, 2025)

From iron concentrate to clean steel: A green short-process production technology centered on preparing high-purity iron concentrate - Wencheng Ge; Jie Liu; Tianjiao Chang; Yanjun Li; Yongsheng Sun; Shumin Zhang; Yuexin Han; Yimin Zhu (Minerals Engineering, 2025)

Transcriptomic analysis reveals the role of MicroRNAs during Ecytonucleospora hepatopenaei infection in shrimp (Penaeus vannamei) - Tingyue Liu; Yi Qiao; Huiwen Jiang; Xiaohui Cao; Jie Cheng; Ge Jiang; Xiaoman Sun; Hui Shen (Journal of Invertebrate Pathology, 2025)

Parental permethrin exposure disrupts offspring metabolism via microbiota–tryptophan axis and is rescued by Lactobacillus plantarum Y1 - Jie Lin; Zexiu Qi; Ge Wang; Jusheng Zheng; Leqi Cui; Ye Peng; Quancai Sun (Journal of Hazardous Materials, 2025)

Nanozeolite-coupled biochar-based phosphorus fertilizer decreases soil N2O emissions in a subtropical Moso bamboo forest - Xinyong Sun; Shuokang Liu; Caixian Tang; Jiashu Zhou; Zhenhui Jiang; Chang Dong; Yu Luo; Tida Ge; Jason C. White; Yanjiang Cai; Bing Yu; Yongfu Li (Journal of Environmental Management, 2025)

Research Progress on the Exposure Risk and Formation Mechanism of Ethyl Carbamate in Chinese Baijiu - Yiwen Ge; Jungang Lv; Bowen Wang; Baoguo Sun; Jinyuan Sun (Food Chemistry, 2025)

Flexural performance of concrete beams hybrid reinforced with bundled stainless steel bars and BFRP bars - Yi Zheng; Zeyang Sun; Shichao Song; Liuzhen Yao; Jin Chen; Yu Tang; Hanbin Ge (Engineering Structures, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Damaged mitochondria targeted copper doped carbon dots as a fluorescent probe hitchhike on circulated neutrophils for precise treatment of ischemic stroke - Ge Zhang; Yan Sun; Fang Li; Yong Liu; Mengdi Sun; Mingzhu Song; Ruizhen Lv; Jia Dong; Yijie Shi; Liang Zhao (Chemical Engineering Journal, 2025)

Fluorinated poly(alkoxide magnesium) electrolyte derived favorable electrodes-electrolyte interphases enable high-temperature magnesium metal batteries - Gaohao Sun; Zhilin Yang; Xuesong Ge; Shu Zhang; Jinlei Zhang; Mingao Chen; Qingyun Liu; Guanglei Cui (Chemical Engineering Journal, 2025)

“Peeling egg” strategies for regenerating spent graphite with tailored surface/sub-surface and removed impurities towards high capacity - Tianjing Wu; Chen Liu; Mingjun Jing; Wei Sun; Yue Yang; Honghui Hu; Peng Ge (Chemical Engineering Journal, 2025)

Biomimetic priming of hMSC aggregates with cadherin-IL-1β synergistic microparticles enhances immune homeostasis in inflammatory bowel disease - Mengyuan Qian; Min Ge; Shanshan Liu; Xin Wen; Ning Liu; Qianqian Wang; Jiaxu Cao; Xiuyan Jiang; Yan Zhang; Jun Yang; Lingyun Sun (Chemical Engineering Journal, 2025)

Csde1 Mediates Neurogenesis via Post-transcriptional Regulation of the Cell Cycle - Xiangbin Jia; Wenqi Xie; Bing Du; Mei He; Jia Chen; Meilin Chen; Ge Zhang; Ke Wang; Wanjing Xu; Yuxin Liao; Senwei Tan; Yongqing Lyu; et al. (Neuroscience Bulletin, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

The Identification and Synthesis of New Sea Cucumber Peptides Leveraging Peptidomics Technology, along with their Anti-Parkinson’s Disease Efficacy - Jiawei Liu; Yusheng Shi; Lingling Jin; Baixue Sun; Ruonan Wang; Guangbo Ge; Guanghao Zhu; Xiaolin Cui; Jie Zhao; Yan Zhang; Sheng Li (Journal of Neuroimmune Pharmacology, 2025)

Synergistic enhancement of Pt electrocatalyst stability and activity in hydrogen oxidation reaction by polyoxometalate and carbon dot co-boosting - Fei-Yang Yu; Zhong-Ling Lang; Xian Wang; Jing Sun; Yu-Chen Liu; Hua-Qiao Tan; Jun-Jie Ge; Yang-Guang Li; Zhen-Hui Kang (Science Bulletin, 2025)

Paleoecology and paleoclimate across the Early Cretaceous Xing'anling Group: New palynological and radiometric data from the Hailar Basin (NE China) - Yan Zhang; Iván R. Barreiro; Chuan-biao Wan; Yue-wu Sun; Wen-chun Ge; Yun-fei Xue; Ti Li; Xin Zhang; Chun-yang Bu; Hao Zhu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A source-to-sink multiproxy analysis of late Eocene regional drainage evolution in the Beibuwan Basin of the South China Sea - Mingxuan Tan; Lianpu Sun; Mianpei Chen; Jiawang Ge; Ping Wang; Peigang Ren (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Global changes in potential evapotranspiration (1992–2020) and associated drivers: Shuttleworth-Wallace model-based analysis - Zaoying Bi; Shanlei Sun; Yi Liu; Ge Sun; Mengyuan Mu; Xiaoyuan Li; Jinjian Li; Yibo Liu; Yang Zhou; Botao Zhou; Haishan Chen (Journal of Hydrology, 2025)

Unraveling synergistic cascade inhibition of methane production in anaerobic digestion system by polyethylene microplastics and domestic sewage: Physical adsorption, metabolic disruption, and microbial community decoupling - Zhaoxuan Wang; Guoxu Ao; Yueqi Shi; Yuantong Liu; Kaiyu Wang; Minghui Yin; Xiyuan Sun; Jingping Ge; Hongzhi Ling; Shanshan Sun (Journal of Hazardous Materials, 2025)

Mercapto-modified layered double hydroxide: High-efficiency emerging amendment for cadmium immobilization in cadmium-contaminated acidic and alkaline soil - Xusheng Gao; Xilin Chen; Yifei Shu; Kexin Chen; Ge Gao; Xiaomin Liu; Qingqing Huang; Lin Wang; Yuebing Sun; Yujie Zhao; Xuefeng Liang (Journal of Hazardous Materials, 2025)

Occurrence, removal and ecotoxicological assessment of halogenated dissolved organic matter in waste leachates - Xian-Ge Wang; Wei He; Xiao-Song He; Xu Cao; Yue Sun; Xian-Jiang Zeng (Journal of Hazardous Materials, 2025)

Strengthening ecosystem services through industrial upgrading in city components: Insights from restaurants in China - Tianyi Zhou; Xiaoyu Hou; Yandong Tan; Wanhong Sun; Guofu Yang; Yuanyuan Du; Ying Ge; Yong Min (Journal of Cleaner Production, 2025)

Valorization of dredged sediment through Al³⁺-mediated C-A-S-H gel networks: Bridging mechanisms for enhanced structural bonding in non-autoclaved brick production - Shengya Zhou; Hongzhi Zhang; Jingjing Lv; Ke Sun; Kaixin Guo; Fangyu Chen; Yuanzhen Liu; Zhi Ge (Journal of Environmental Chemical Engineering, 2025)

Effects of replacing sucrose and blending extrusion modified flours on the eating quality of highland barley sugar-crisp cookies - Di Wu; Tongtong Xu; Yue Sun; Fei Ge; Yang Wang; Weiwei Cheng; Jun Liu; Peiqiang Yang; Xiaozhi Tang (Food Research International, 2025)

Smartphone-assisted ultrasensitive colorimetric strategy based on Cu-CN single-atom nanozyme for acrylamide detection in fried food - Jia Ge; Xiaoyu Sun; Xinxin Li; Yu Yang; Lin Zhang; Lingbo Qu; Zhaohui Li (Food Chemistry, 2025)

CuO2 and tannic acid mediated synergistic antimicrobial and antifouling coatings - Qiang Liu; Chenqing Xu; Liqi Pang; Xi Xiong; Hao Zhou; Jinyang Zheng; Zhou Chen; Dongtao Ge; Wei Shi; Yanan Sun (Chemical Engineering Journal, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Branched ligand-functionalized immuno-evasive PEGylation (BLIP) platform: Breaking through accelerated blood clearance and chemoresistance barriers with dual-targeting RNAi-chemotherapy synergy - Mengyang Liu; Ruijuan Xing; Ge Chen; Yuxiang Liang; Lu Huang; Yumeng Xi; Yue Li; Shifei Zhang; Yanan Sun; Yupin Song; Jintao Hao; Kexin Cong; et al. (Chemical Engineering Journal, 2025)

Association Between Folate Metabolism Risk, Collateral Circulation, and Hemorrhagic Risk in Moyamoya Disease - Junsheng Li; Qiheng He; Chenglong Liu; Chaofan Zeng; Zhiyao Zheng; Bojian Zhang; Siqi Mou; Wei Liu; Wei Sun; Peicong Ge; Dong Zhang; Jizong Zhao (Translational Stroke Research, 2025)

A novel method for predicting debris flow hazard: a multi-strategy fusion approach based on the light gradient boosting machine framework - Tianlong Wang; Qi Ge; Tianxing Ma; Hao Chen; Rui Luo; Xu Wang; Keying Zhang; Zhaowei Chu; Xiaohui Ni; Hongyue Sun (Stochastic Environmental Research and Risk Assessment, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Temporal dynamics of climate and needle litter chemistry in driving decomposition along the entire decomposition process for Norway spruce - Björn Berg; Tao Sun; Maj-Britt Johansson; Jielin Ge (Plant and Soil, 2025)

Neural Responses to Hypoxic Injury in a Vascularized Cerebral Organoid Model - Yang Li; Xin-Yao Sun; Peng-Ming Zeng; Zhen-Ge Luo (Neuroscience Bulletin, 2025)
Hypoxic injury (HI) in the prenatal period often causes neonatal neurological disabilities. Due to the difficulty in obtaining clinical samples, the molecular and cellular mechanisms remain unclear. Here we use vascularized cerebral organoids to investigate the hypoxic injury phenotype and explore the intercellular interactions between vascular and neural tissues under hypoxic conditions. Our results indicate that fused vascularized cerebral organoids exhibit broader hypoxic responses and larger decreases in panels of neural development-related genes when exposed to low oxygen levels compared to single cerebral organoids. Interestingly, vessels also exhibit neural protective effects on T-box brain protein 2 + intermediate progenitors (IPs), which are markedly lost in HI cerebral organoids. Furthermore, we identify the role of bone morphogenic protein signaling in protecting IPs. Thus, this study has established an in vitro organoid system that can be used to study the contribution of vessels to brain injury under hypoxic conditions and provides a strategy for the identification of intervention targets.

First Isolation of a Multi-azole-Resistant Aspergillus fumigatus cyp51A TR46/Y46F/F70L Mutant in a Patient with Fungal Keratitis - Xiang Han; Heng Zhang; Yuqi Mao; Wenhao Ling; Lu Ge; Menghua Tang; Yi Sun; Zhiqin Wu (Mycopathologia, 2025)

SPPF-CGA: Marine Garbage Detection and Image Enhancement in Turbid and High-Dynamic Underwater Environments - Jinhuan Wang; Qingbang Han; Kao Ge; Liujia Sun (Journal of Ocean University of China, 2025)

Low VTG1 levels trigger failed development of yellow follicles in ZZ female Chinese soft-shelled turtles - Jiequn Tang; An Huang; Jinni Wang; Yanyan Zhang; Wei Sun; Ling Xiao; Chutian Ge; Yin Guo (Aquaculture, 2025)

Sodium nitroprusside treatment affects energy metabolism and programmed cell death (PCD) of apple fruit during ripening - Yanxia Qiu; Jingyi Lv; Sijie Dong; Chenxu Sun; Yaxuan Wang; Yonghong Ge (Postharvest Biology and Technology, 2025)

Biodegradation of poly(butylene adipate-co-terephthalate) film by heat-tolerant bacterium Bacillus sp. PBAT4 - Yulong SUN; Lei GE; Ling WANG; Han WU; Michael Gatheru WAIGI; Juan LIU (Pedosphere, 2025)

The burden trend and projection of tracheal, bronchial, and lung cancer attributable to air pollution: Based on the global burden of disease study 2021 - Guojie Zhao; Yanlei Ge; Ye Jin; Junqing Gan; Weinan Yao; Yanna Bi; Guogui Sun (Next Research, 2025)

Climate-driven mercury dynamics in a tropical savanna: Low uptake, pulsed emissions, and weak sequestration - Ge Zhang; Wei Yuan; Longyu Jia; Meiqing Sun; Handong Wen; Chao Chen; Ruidong Yang; Xun Wang (Journal of Hazardous Materials, 2025)

Efficient extraction of platinum with benzo-18-crown-6 in a potassium halide based system - Chao Yao; Tao Ge; Liang Xu; Yan Sun; Ao Cai; Cheng Yang; Yongpan Tian; Zhuo Zhao (Journal of Environmental Management, 2025)

From error ellipse to Bayesian estimation: Strategies for optimizing T-W diagrams in UPb dating - Yao Mu; Can Ge; Fangyue Wang; Xiuyu Li; He Sun; Haiou Gu; Feng Yuan (Geochemistry, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Deciphering the microbial mechanisms underlying glucose induced soil priming effects under low and high nutrient levels - Jiaqi Wang; Xichang Zhang; Yingyi Fu; Lukas Van Zwieten; Han Sun; Georg Guggenberger; Lingfei Hu; Yu Luo; Tida Ge; Yakov Kuzyakov (European Journal of Soil Biology, 2025)

Alkyl chain engineering in β-linked dimer acceptors: Balancing crystallinity and phase separation for high-performance organic photovoltaics - Yun Li; Jiawei Fu; Hang Jiang; Zhongwei Ge; Haisheng Ma; Yinuo Yang; Xiaobo Sun; Shouchun Yin (Chemical Engineering Journal, 2025)

Engineering covalent surface donor-acceptor interactions via Schiff base reaction for enhanced photocatalytic CO2 reduction - Jingyu Sun; Zhuowen Jiang; Guangying Nie; Lie Ding; Peiyan Wang; Chengsheng Ge; Shuaishuai Ma (Chemical Engineering Journal, 2025)

Ultrasmall polylysine dendrimer nanodots for glutathione-responsive targeted chemotherapy and enhanced photodynamic/immunotherapy of metastatic cancer - Ruibing An; Qianting Zhang; Dehao Du; Cantong Sun; Shujun Zhang; Junle Wu; Muhammad Adnan Younis; Haiyan Ge; Kaiqi Wang; Muhammad Rizwan Younis; Jian Dong (Chemical Engineering Journal, 2025)

Thiazole-fused thiazoliniums with ketone warheads as covalent inhibitors targeting Cys44 of SARS-CoV-2 3CLpro - Qizhen Cao; Zhaoqin Zhang; Guanghao Zhu; Sanfeng Dong; Xue Sun; Yuqing Song; Ya Zhang; Tingting Cai; Xinben Zhang; Yong Zhang; Zhijian Xu; Ruisheng Xiong; et al. (Chemico-Biological Interactions, 2025)

Modified conductive additives based on pine needle-derived biomass carbon for high-performance lithium-ion batteries - Hao Ge; Zhonghai Xiu; Longhui Xie; Ruicong Pan; Bei Huang; Xiaoman Cao; Zhijia Sun (Biomass and Bioenergy, 2025)

The impact of assimilating FY-3D Microwave Humidity Sounder II radiance data on the analysis and forecast of two advection fog cases - Dongmei Xu; He Chen; Yifang Chen; Deqiang Liu; Fei Ge; Xinya Ye; Qilong Sun; Feifei Shen (Atmospheric Research, 2025)

Distribution patterns and driving forces of soil fungal communities along elevational gradients on two snow mountains in the Hengduan Mountain Range - Shiqi Zhang; Zhenjiao Cao; Wei Fu; Congcong Shen; Zhipeng Hao; Guoxin Sun; Yuan Ge; Limei Zhang; Xin Zhang; Baodong Chen (Soil Ecology Letters, 2025)

Triazole-amine metal-organic framework chiral stationary phases: A novel chiral separation approach for amino acids in capillary electrochromatography - Li Ge; Gege Zhu; Xinyu Li; Qin Chen; Bing Niu; Li Qi; Dan Zhong; Xiaodong Sun (Analytica Chimica Acta, 2025)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Thermodynamic and kinetic studies of CO2 hydrate stability in complex deep-oceanic environments - Lei Zhang; Ziming Yang; Yang Ge; Bingbing Chen; Huiru Sun; Yongchen Song; Mingjun Yang (Process Safety and Environmental Protection, 2025)

Shift in the distribution of native species Littoraria intermedia in response to Spartina alterniflora invasion - Baoming Ge; Wenlan Wang; Shuang Wang; Pushu Jia; Xiaoping Sun; Hongshan Li; Li Yang (Marine Environmental Research, 2025)

Tide to river-dominated changes in the early Miocene mixed-energy paralic western shelf of the Pearl River Mouth Basin, northern South China Sea - Mingxuan Tan; Yanlei Dong; Jiawang Ge; Lianpu Sun; Hehe Chen; Shunli Li (Marine and Petroleum Geology, 2025)

Biofilm-overproducing Bacillus amyloliquefaciens strain B9ΔywcC reduces cadmium uptake in lettuce by upregulating the expression of proteins associated with root surface biofilm formation and cell membrane homeostasis - Lijing Sun; Rongrong Gao; Qian Zeng; Zhanbiao Ge; Xiafang Sheng; Linyan He (Journal of Hazardous Materials, 2025)

Bean powders improved the quality characteristics of high-moisture extrudate prepared from pea protein isolate: Texture, structure and sensory - Jiao Ge; Rong Yang; Guanchen Liu; Cuixia Sun; Yapeng Fang (Food Hydrocolloids, 2025)

Targeting adenosine A2A receptors for early intervention of retinopathy of prematurity - Xuhao Chen; Xiaoting Sun; Yuanyuan Ge; Xuzhao Zhou; Jiang-Fan Chen (Purinergic Signalling, 2025)

The restoration of soil multifunctionality in the later stages of biocrust succession is related to bacterial niche expansion: a case study of ion-adsorption rare earth tailings in southern China - Sheng Xu; Shifeng Sun; Huimin Qiu; Dan Lu; Yizhen Liu; Jun Ye; Hui Zhong; Tao Wang; Yanan Zhang; Lan Wu; Chi Yao; Qiying Cai; et al. (Plant and Soil, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

Neonicotinoid pesticides: residue detection and dietary risk assessment in commercially available plant-based agricultural products in North China - Peng Sun; Danqi Ren; Guotao Ding; Ning Hao; Ge Shi; Weihao Li (Environmental Monitoring and Assessment, 2025)

Genetic mapping of quantitative trait loci conferring resistance to race 4 of Xanthomonas campestris pv. campestris in cabbage (Brassica oleracea var. capitata) - Qingguo Sun; Liang Yan; Changjun Ge; Jinlan Li; Junfen Dai; Hao Ding (Physiological and Molecular Plant Pathology, 2025)

Experimental study on the hydrodynamic behavior of a floating Fishery–Photovoltaic complementary structure - Sida Xie; Chao Ma; Zhan Zhang; Yun-Peng Zhao; Jia-Qing Shu; Xiao-Feng Ge; Yan-Qian Sun (Ocean Engineering, 2025)

Where does the wine go experiencing regulated deficit irrigation: the effect of RDI on volatile composition and the sensory properties of Cabernet Sauvignon wines - Guo Cheng; Jianing Li; Zhihao Deng; Ziyin Peng; Dong Li; Mengyuan Wei; Qian Ge; Caihong Li; Xiangyu Sun; Yulin Fang (Food Bioscience, 2025)

Elevation and seasonal variation patterns of soil respiration components and their influencing factors in Pinus taiwanensis forests in Wuyi mountain, China - Chenlu Zhu; Jinlong Li; Jun Sun; Xiaocai Ge; Dandan Hu; Quanlin Zhong; Dongliang Cheng (CATENA, 2025)

Seismic performance of multiple hardening wall: macro-element modelling, parametric analysis, and design - Hongbo Jiang; Haotian Liu; Tong Guo; Guangzhong Fan; Jian Sun; Hongxing Qiu; Wenjie Ge; Yanqing Xu; Kongyang Chen; Chunchao Chen (Bulletin of Earthquake Engineering, 2025)

Mechanism of rock magnetic susceptibility response in coal fire zone under high-temperature environment - Shihao Yuan; Qiang Sun; Yuyang Zhao; Xin Hu; Shaofei Wang; Zhenlong Ge; Kai Chen (Acta Geophysica, 2025)

The rabies virus matrix protein (RABV M) interacts with host histone deacetylase 6 (HDAC6) to activate the MEK/ ERK signaling pathway and enhance viral replication - Juanbin Yin; Shasha Wang; Zhixiong Zhang; Junwei Ge; Qiang Zhang; Yuefeng Sun; Xiangping Yin; Xiangwei Wang (Veterinary Microbiology, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Paired electrocatalysis for simultaneous anodic oxidation of tetracycline and cathodic nitrate reduction to ammonia - Chunhong Fu; Huizhong Wu; Jiangli Sun; Ge Song; Minghua Zhou (Journal of Hazardous Materials, 2025)

Study of enhanced nitrogen removal performance and mechanism of iron-modified activated carbon in low-temperature environments - Guangtao Li; Jinlong Han; Yunchang Wang; Shihong Wu; Liyan Ge; Xueqian An; Xiaoyang Liu; Wenfang Gao; Li Sun; Zhijun Ren; Kengo Kubota (Journal of Environmental Chemical Engineering, 2025)

One-step controllable synthesis of N-doped porous carbon derived from ZIF-8 for efficient capacitive deionization - Pin Hou; Jiaqi Yan; Xiaoyu Yang; Ridha Djellabi; Xinrui Ge; Xinyu Sun; Jianli Jia; Jianbing Wang (Journal of Environmental Chemical Engineering, 2025)

Catalytic ozonation of coal chemical wastewater using AlOOH-immobilized phosphotungstic acid - Mingzhu Chen; Tengfei Shao; Gangqiang Zhang; Weijun Zhen; Chunmei Ma; Pengtao Sun; Qing Ge; Yusheng Zhou; Buning Chen (Journal of Environmental Chemical Engineering, 2025)

Interspecies interactions promote dual-species biofilm formation by Lactiplantibacillus plantarum and Limosilactobacillus fermentum: Phenotypic and metabolomic insights - Bingxin Zhang; Yuxin Sun; Wenyu Han; Wenwen Ge; Zhenbo Xu; Shuo Wang; Zhenquan Yang; Lei Yuan (Food Research International, 2025)

A novel green plant protein from Lycium barbarum L. residue: Structure, physicochemical and functional properties - Haixuan Sun; Beiqi Wu; Weiben Ge; Yu Wang; Hongxin Wang (Food Bioscience, 2025)

Unraveling the ecological interactions between dairy strains Bacillus licheniformis and Bacillus cereus during the dual-species biofilm formation - Yang Liu; Wenwen Ge; Yuxin Sun; Hongchao Dai; Luyao Fan; Lei Yuan; Zhenquan Yang; Xinan Jiao (Food Microbiology, 2025)

Edible starch-based films modified by fruit and vegetable juices: Preparation, performance evaluation and seasoning bag design - Xinyu Sun; Guocong Ma; Xiaoling Tian; Dan Hai; Yan Ma; Ge Bai; Lianjun Song; Qinghua Yang; Xianqing Huang (Food Packaging and Shelf Life, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Rising temperature increases the response time of LAI and GPP to meteorological drought in China - Yufei Wang; Peng Sun; Rui Yao; Chenhao Ge (Atmospheric Research, 2025)

Dietary intervention enhances fertility in obese male mice by regulating SLC2As - Liujia Sun; Xiaoqi Hong; Qi Zhu; Yu Xiang; Cen Xu; Lingling Weng; Jieyu Cai; Na Liang; Mingrui Xue; Hongshan Ge (Journal of Molecular Histology, 2025)

Zonation characteristics of karst development in Taiyuan formation limestone and its implications for water-conserving mining: a case study of Zhangshuanglou coal mine, North China - Tianci Chen; Zhimin Xu; Xianfu Zhang; Weixiao Chen; Ge Chen; Yajun Sun (Carbonates and Evaporites, 2025)

Development of a PAS module in the ATHROC for simulation of passive containment air cooling system - Huifang Zhang; Yuntao Zheng; Yanyu Sun; Kui Ge; Shihao Wu; Yongkang Li; Yapei Zhang; Wenxi Tian; Suizheng Qiu; Guanghui Su (Annals of Nuclear Energy, 2025)

The glycocalyx: a key target for treatment of severe acute pancreatitis-associated multiple organ dysfunction syndrome - Huijuan Li; Haiyun Wen; Jie Liu; Xinyu Luo; Boliang Pei; Peng Ge; Zhenxuan Sun; Jin Liu; Junjie Wang; Hailong Chen (Human Cell, 2025)
The endothelial glycocalyx is a dynamic brush-like layer composed of proteoglycans and glycosaminoglycans, including heparan sulfate (HS) and hyaluronic acid (HA), and is an important regulator of vascular homeostasis. Its structure (thickness ranges from 20 to 6450 nm in different species) not only provides a charge-selective barrier but also serves to anchor mechanosensors such as the glypican-1 (GPC-1)/caveolin-1 (CAV-1) complex and buffers shear stress. In severe acute pancreatitis (SAP), inflammatory factors promote the expression of matrix metalloproteinases (MMPs) and heparinases, which degrade syndecan-1 (SDC-1) and HS, while oxidative stress disrupts HA-CD44 binding, leading to increased capillary leakage and neutrophil adhesion. This degradation process occurs before the onset of multiple organ dysfunction syndrome (MODS), highlighting the potential of the glycocalyx as an early biomarker. More importantly, the regeneration of glycocalyx through endothelial cell synthesis of glycosaminoglycans (GAGs) and shear stress-driven SDC recycling provides therapeutic prospects. This review redefines the pathophysiology of severe acute pancreatitis-associated multiple organ dysfunction (SAP-MODS) by exploring the glycocalyx’s central mechanistic role and proposes stabilizing glycocalyx structure as a potential strategy to prevent microcirculatory failure. Graphical Abstract

Spatial-temporal variations of kelp 129I contents in coastal waters of China before and after the Fukushima Daiichi Nuclear Power Plant accident - Xiaowen Liu; Jialin Liu; Yukun Fan; Guozhi Xie; Xiaole Sun; Luyuan Zhang; Qi Liu; Xiaoqi Yang; Delin Duan; Fangli Qiao; Chang Zhao; Baozhu Ge; et al. (Marine Pollution Bulletin, 2025)

Macrofaunal biodiversity and trophic structure varied in response to changing environmental properties along the Spartina alterniflora invasion stages - Li Yang; Rui Pan; Shuang Wang; Zhangyan Zhu; Hongshan Li; Ruiping Yang; Xiaoping Sun; Baoming Ge (Marine Pollution Bulletin, 2025)

Synthetic phenolic antioxidant contamination in farmland soils induced by mulching films: Distribution and transformation pathways - Shanxing Wu; Meng Gao; Bo Fang; Lili Rong; Zhanpeng Ge; Hao Chen; Yiming Yao; Yu Wang; Hongwen Sun (Journal of Hazardous Materials, 2025)

Strategies optimization to improve environmental benefit of chicken manure anaerobic digestion in China: Insight from life cycle assessment - Fangzhou Wang; Shunan Zhao; Yizhu Sun; Ge Song; Yifan Sun; Kai Zhao; Ruiping Liu; Yu-You Li (Journal of Cleaner Production, 2025)

Decoupling soil pH and geography: Universal drivers of cadmium bioavailability in rice across terrains - Qiang Liu; Shuyue Liu; Danling Wang; Dawei Sun; Yun Ge; Songwei Zhang; Guanlin Li; Eun Hea Jho; Jin Chul Joo; Xin Zhao; Mao Ye; Jian Hu (Journal of Environmental Management, 2025)

Permafrost thawing characterization in engineering scale by multi-geophysical methods: A case study from the Tibet Plateau - Junkai Ge; Huaifeng Sun; Rui Liu; Zhiyou Huang; Bo Tian; Lanbo Liu; Ziqiang Zheng (Engineering Geology, 2025)

Non-flammable phosphate-ester-based electrolyte with high concentration for high safety potassium-based anode-free dual ion battery - Ge Zhang; Sunfa Wang; Kanghou Ma; Caiyue Sun; Chen Wang; Fangshuo Zhou; Xinyue Zhao; Xiqiang Huang; Zhiguo Liu; Ningning Wu; Yaohui Zhang (Chemical Engineering Journal, 2025)

Doping-engineered regulation of Co(IV)=O enhanced Fenton-like activities via electronic structure modulation on CoSCN nanotubes - Liang Ge; Jian Wei; Junyong He; Rui Sun; Wenlong Wang; Dandan Yang; Jiandong Lu; Peidong Hong; Yulian Li; Yahui Li; Chao Xie; Zijian Wu; et al. (Chemical Engineering Journal, 2025)

Superior matching between electrochemical and non-electrochemical reactions to boost furfural electro-oxidation - Jianyuan Deng; Rui Li; Kun Xiang; Longzhou Zhang; Kaihang Sun; Young Dok Kim; Zhongyi Liu; Jingmin Ge; Zhikun Peng (Chemical Engineering Journal, 2025)

Efficient waste polyester plastics recycling in organic–inorganic acid catalytic system - Guohao Xu; Haobin Ge; Kai He; Zhaopeng Sun; Xinyue He; Jichang Liu; Bingjie Zhou; Yulin Deng; Jianfei Song; Wei Liu (Chemical Engineering Journal, 2025)

Stratified distribution of recycled components in the mantle of the South China Sea unveiled through magnesium isotopes - Zhen-Min Ge; Xiao-Long Huang; Fan Yang; Yang Yu; Guan-Hong Zhu; Le Zhang; Yu-Xin Cai; Guo-Hong Sun (Chemical Geology, 2025)

The Layout Optimization of low-impact Development Facilities is Based on a Multi-Objective Genetic Algorithm and the SWMM Model - Xiaoyue Wang; Wenzhuo Sun; Yumeng Lan; Xiaoyu Ge (Water Resources Management, 2025)

Amplifying population exposure of extreme precipitation across Yellow River Basin, China at 1.5° C, 2.0° C and 3.0° C global warming - Rui Yao; Zice Ma; Peng Sun; Chenhao Ge (Natural Hazards, 2025)

Urbanization has enhanced compound heatwaves - Peng Sun; Shifang Yu; Rui Yao; Zhongbao Sun; Vijay P. Singh; Yaojin Bian; Chenhao Ge; Qiang Zhang (Journal of Geographical Sciences, 2025)

Identification, genomic analysis, and pathogenicity of a novel highly virulent strain of infectious spleen and kidney necrosis virus isolated from the humpback grouper, Cromileptes altivelis - Cao-Ying Wei; Chen Zhang; Jin-ge Wang; Min Yang; Yong-Can Zhou; Yun Sun (Aquaculture, 2025)

Ultrathin zwitterionic COF membranes from colloidal 2D-COF towards precise molecular sieving - Xinliang Zhang; Xueting Zhao; Jinshan Sun; Yubin He; Bin Wu; Liang Ge; Jiefeng Pan (Water Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

Characterization of flavor profiles of water-boiled pork meatballs at different ultrasonic powers using solid-phase microextraction gas chromatography–mass spectrometry combined with electronic nose - Xinxin Zhao; Bangcheng Lai; Yunling Jiang; Xiankun Sun; Zixin Luo; Qingfeng Ge; Jiaxin Chen; Hai Yu (Meat Science, 2025)

Eco-hydrological recovery following large vegetation disturbances from a mega earthquake on the eastern Tibetan plateau - Jiehao Zhang; Yulong Zhang; Matthew P. Dannenberg; Qinfeng Guo; Jeff W. Atkins; Wenhong Li; Ge Sun (Journal of Hydrology, 2025)

Ultra broadband emission toward white LED based on dysprosium double perovskites CsxRb3-xDyCl6-xIx - Xue Bai; Zongqing Jin; Guanjun Xiao; Bo Zou; Qingqin Ge; Nannan Shi; Liwei Jiang; Cheng Sun; Tao Xiong; Yinan Zhang (Chemical Engineering Journal, 2025)

Anthill-Inspired bionic bone cement enhances bone regeneration by guiding angiogenesis and regulating BMSCs metabolism with anti-ROS capacity - Chen Qian; Gaoran Ge; Haifu Sun; Xiaoqin Yang; Yi Qin; Wenhao Li; Wentie Yang; Xuequan Zhao; Ye Gu; Yusen Qiao; Dechun Geng; Huilin Yang (Chemical Engineering Journal, 2025)

Microglial membrane-coated nanoparticles for ACSL4-siRNA delivery in Parkinson’s disease - Heyue Lu; Bo Zhang; Min Ge; Juncheng Yu; Fei Ju; Jie Sun; You Lang Zhou; Lei Wang; Zhongzheng Jia (Chemical Engineering Journal, 2025)

The response mechanisms of kelp Macrocystis pyrifera holobiont to elevated temperature and CO2 concentration - Tianle Xi; Yajing Liu; Xiaowen Zhang; Shanshan Ge; Yitao Wang; Ke Sun; Xiao Fan; Dong Xu; Pengyan Zhang; Chengwei Liang; Naihao Ye (Journal of Applied Phycology, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Determination of Antioxidant, Cytotoxicity, and Anti-human Lung Cancer Properties of Silver Nanoparticles Green-Formulated by Foeniculum vulgare Extract Combined with Radiotherapy - Qian Wu; Zifu Qin; Pei Sun; Fang Liu; Yin Ge; Pengbo Wang (Biological Trace Element Research, 2025)

TGF-β/SMAD Pathway Mediates Cadmium Poisoning-Induced Chicken Liver Fibrosis and Epithelial-Mesenchymal Transition - Jinyang Zhang; Yiming Sun; Miao Yu; Yihan Hu; Xiaodan Huang; Guijun Yang; Ruili Zhang; Ming Ge (Biological Trace Element Research, 2025)

Overexpression of PIK3CG in Cancer Cells Promotes Lung Cancer Cell Migration and Metastasis Through Enhanced MMPs Expression and Neutrophil Recruitment and Activation - Jinpeng Sun; Zhenshan Zhang; Binghui Xia; Tianyu Yao; Fengyue Ge; Fengmei Yan (Biochemical Genetics, 2025)

Polysaccharide metabolic pattern of Cytophagales and Flavobacteriales: a comprehensive genomics approach - Kuo-Jian Ma; Yong-Lian Ye; Yu-Kang Li; Ge-Yi Fu; Yue-Hong Wu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2025)
The complete metabolism of carbohydrates, as the most abundant and structurally diverse organic matter on earth, requires the involvement of different carbohydrate-active enzymes (CAZymes). Flavobacteriales and Cytophagales are two groups whose members specialize in polysaccharide metabolism, but research on their polysaccharide metabolic patterns based on the overall CAZymes is scarce. In this study, we analyzed 702 filtered genomes of Flavobacteriales and Cytophagales and obtained 100,445 CAZymes. According to their taxonomic status and living environment, we explored the impact of taxonomic status, isolation source, and environmental condition on their potential polysaccharide metabolic patterns. The results indicated significant differences in the CAZyme composition among different taxonomic statuses or environments. Compared with the Flavobacteriales genomes, the genomes of Cytophagales possess more abundant and diverse CAZymes, but have fewer unique CAZyme families. Genomes from different families vary greatly in terms of CAZyme family diversity and composition, but relatively small divergences were found from families in the same order. Furthermore, our findings indicated that genomes from the marine and tidal flat environments share more similarities in CAZyme family composition and diversity compared with the terrestrial genomes. Extreme environments greatly constrain the types of CAZyme families present, and certain CAZyme families are significantly lower than those in normal environments. Although significant differences were found among genomes from both different taxonomic statuses and environments, the dimensionality reduction and the clustering analysis based on CAZyme composition indicated that evolutionary status is the main factor influencing the polysaccharide metabolic patterns of these strains. The correlations among CAZyme families indicated that the majority of these families are synergistically involved in polysaccharide metabolism. This study provides a comprehensive profile of the CAZymes in Flavobacteriales and Cytophagales, highlighting the role of evolutionary status in shaping the polysaccharide metabolic patterns and the prevalence of synergism among CAZyme families. These findings have implications for understanding microbial carbohydrate metabolism in different environments.

An innovative method and model for calculating the mountain tunnels with sprayed waterproofing membrane - Xiaohe Sun; Chenghua Shi; Zhu Peng; Guoqing Xiao; Yangyang Ge (Tunnelling and Underground Space Technology, 2025)

A correlation-guided cooperative coevolutionary method for feature selection via interaction learning-based space division - Yaqing Hou; Huiyue Sun; Gonglin Yuan; Yijing Li; Zifan Che; Hongwei Ge (Swarm and Evolutionary Computation, 2025)

Effects of environmental factors and genotype on performance, soil physicochemical properties and endophytic fungi of Salvia miltiorrhiza - Xin Zheng; Wenjing Chen; Xianen Li; Wenyi Shi; Xiang Sun; Qieyun Ge; Chao He; Xueli He (Rhizosphere, 2025)

Development of a physicochemical proxy index system for surface sediments in the Gurbantunggut Desert and its application to regional oasis-desert evolution - Yujie Xu; Hui Zhao; Bing Liu; Aijun Sun; Keqi Wang; Dongxue Li; Junjie Wei; Jianhui Ge (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Interactions between the co-contamination system of oxcarbazepine-polypropylene microplastics and Chlorella sp. FACHB-9: Toxic effects and biodegradation - Hao Zhang; Baoming Liu; Fengjie Sun; Ziqi Zhang; Yifan Kong; Xiang Liu; Yulin Cui; Yuyang Ma; Yuyong Wu; Jianhua Fan; Baosheng Ge; Yan Cheng; et al. (Journal of Environmental Management, 2025)

Accumulation characteristics and fate modeling of phthalic acid esters in surface water from the Three Gorges Reservoir area, China - Shuai Sun; Bing Zhang; Junjie Hu; Wen Gu; Zhen Wang; Deling Fan; Feng Ge; Lili Shi; Lei Wang (Journal of Environmental Sciences, 2025)

Synergistic neurotoxicity of clothianidin and photoaged microplastics in zebrafish: Implications for neuroendocrine disruption - Ping Ding; Yajing Han; Yanan Sun; XiaoXia Chen; Qing Ge; Wei Huang; Lijuan Zhang; Adela Jing Li; Guocheng Hu; Yunjiang Yu (Environmental Pollution, 2025)

Corrigendum to “Cryopreservation of porcine skin-derived stem cells using melatonin or trehalose maintains their ability to self-renew and differentiate” [Cryobiology 107 (2022) 23–34] - Jia-Dong Sun; Yu Sun; Tian Qiao; Shu-Er Zhang; Paul W. Dyce; Yuan-Wei Geng; Ping Wang; Wei Ge; Wei Shen; Shun-Feng Cheng (Cryobiology, 2025)

LPA reduces the apoptosis of cryopreserved porcine skin-derived stem cells by inhibiting the regulatory factor TNF-α - Xin-Xiang Xie; Jia-Dong Sun; Ming-Xin Zang; Geng Zhang; Chun-Xiao Li; Xiang-Wei Zhai; Wei Shen; Wei Ge; Shun-Feng Cheng (Cryobiology, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

Mechanisms of phosphorus conversion in chicken manure and straw composting systems regulated by flax-retting wastewater and a combination of flax-retting wastewater and biochar - Shuo Li; Jie Kang; Zhenchao Wu; Yangcun Sun; Xiujun Tu; Yuhao Guo; Liangyang Mao; Ying Yang; Weige Yao; Jingping Ge (Chemical Engineering Journal, 2025)

Quaternary ammonium chitosan-functionalized mesoporous silica nanoparticles: A promising targeted drug delivery system for the treatment of intracellular MRSA infection - Junfeng Liu; Liying Zhang; Haodi Ma; Haoyang Sun; Shu-ai Ge; Jieyi Liu; Shengdi Fan; Chunshan Quan (Carbohydrate Polymers, 2025)

Production and Subsequent Application of Different Biochar-based Organic Fertilizers to Enhance Vegetable Quality and Soil Carbon Stability - Jining Zhang; Li-ao Ge; Yuxiang Yang; Xianxian Zhang; Cong Wang; Huifeng Sun; Honghui Chen; Jian Huang; Sheng Zhou (Journal of Soil Science and Plant Nutrition, 2025)

Evaluation of enzyme activity predictions for variants of unknown significance in Arylsulfatase A - Shantanu Jain; Marena Trinidad; Thanh Binh Nguyen; Kaiya Jones; Santiago Diaz Neto; Fang Ge; Ailin Glagovsky; Cameron Jones; Giankaleb Moran; Boqi Wang; Kobra Rahimi; Sümeyra Zeynep Çalıcı; et al. (Human Genetics, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Local considerations are the key to managing global forests for water - Xiaohua Wei; Julia Jones; Yiping Hou; Shirong Liu; Heidi Asbjornsen; Zhiqiang Zhang; Nadeem Shah; Yanhui Wang; Mingfang Zhang; Irena Creed; Ge Sun; Antonio del Campo; et al. (Science Bulletin, 2025)

Moxifloxacin plus Cordyceps polysaccharide ameliorate intestinal barrier damage due to abdominal infection via anti-inflammation and immune regulation under simulated microgravity - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Bing-Xin Xu; Hong-Wei Sun; Jian-Wu Yang; Shao-Yan Si; et al. (Life Sciences in Space Research, 2025)

Integrated spaceflight transcriptomic analyses and simulated space experiments reveal key molecular features and functional changes driven by space stressors in space-flown C. elegans - Ge Zhang; Lei Zhao; Zejun Li; Yeqing Sun (Life Sciences in Space Research, 2025)

A post-modified lanthanide metal-organic frameworks as ratiometric luminescent sensor for the visual detection of 5-hydroxytryptamine - Congmin Sun; Xiao Liu; Huimin Zhuo; Xu He; Zerong Ge; Ying Zhang; Zhiqiang Li; Qingqing Xiong (Journal of Hazardous Materials, 2025)

Experimental study of effective thermal conductivity of methane hydrate-bearing sediments in gas-rich and water-rich systems - Cunning Wang; Xingxun Li; Yang Ge; Weixin Pang; Qingping Li; Zhenbin Xu; Guangjin Chen; Changyu Sun (Fuel, 2025)

Dopamine-supported HPLC post-column derivatization to fluorescence: Simultaneous and sensitive detection of eight tea polyphenols - Hongchen Li; Jing Cheng; Hanbing Ge; Jingbo Sun; Zihan Chen; Jiali Ren; Yi Du; Dong Xu; Zhiqin Yuan (Food Chemistry, 2025)

Synergistic effect of 2′-Fucosyllactose or galactooligosaccharide with Bifidobacterium bifidum DNG6 improves the intestinal barrier by modulating the SCFAs-TLR4/NF-κB cascade response in DSS-induced colitis in mice - Cui-Cui Sun; Yu-Qi Wang; Xin-Yu Wang; Guo-Fang Zhang; Hong-Fang Cao; Ge Song; Li-Bo Liu; Chun Li; Irina Valeryevna Boyarineva; Peng Du (Food Bioscience, 2025)

Corrigendum to ‘Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure’ [Environ. Pollut. 347 (2024) 123742] - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2025)

Carbon emissions assessment of ultra-high performance concrete in construction industry: Calculation method and case study - Sheng Li; Ge Han; Boshi Du; Zhisheng Jiang; Linqi Sun (Energy and Buildings, 2025)

Intensifying bioconversion of rich-capsaicinoids food waste into fengycin by the tolerant-artificial consortium - Tian-Xu Duan; Kai-Ge Song; Hui-Zhong Sun; Wei Shang; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Engineering the microenvironment in Ba-doped Fe catalyst with alkali metal promoters for enhanced CO2 hydrogenation to α-olefins - Joshua Iseoluwa Orege; Yang Yu; Jian Wei; Qixin Fan; Jixin Zhang; Lifei Song; Qingjie Ge; Jian Sun (Chemical Engineering Journal, 2025)

Deciphering bioprocess responses in organic phosphorus mineralization to different antibiotic stresses: Interaction mechanisms mediated by microbial succession and extracellular polymeric substances and regulatory patterns - Zhenchao Wu; Jie Kang; Liangyang Mao; Rui Sun; Xiujun Tu; Yuhao Guo; Jingping Ge (Bioresource Technology, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Comprehensive Analysis and In Vitro Verification of Endothelial-Mesenchymal Transition-Related Genes in Moyamoya Disease - Junsheng Li; Qiheng He; Zhiyao Zheng; Chenglong Liu; Bojian Zhang; Siqi Mou; Chaofan Zeng; Wei Sun; Wei Liu; Peicong Ge; Dong Zhang; Jizong Zhao (Molecular Neurobiology, 2025)

Counting wheat heads using a simulation model - Xiaoyong Sun; Tianyou Jiang; Jiming Hu; Zuojie Song; Yuheng Ge; Yongzhen Wang; Xu Liu; Jianhao Bing; Jinshan Li; Ziyu Zhou; Zhongzhen Tang; Yan Zhao; et al. (Computers and Electronics in Agriculture, 2025)

2-Ethylhexyl diphenyl phosphate induces lung oxidative stress and pyroptosis in chicks - Yiming Sun; Ruili Zhang; Jiali Li; Yihan Hu; Haolin Zhang; Xiangjie Wang; Yi Yang; Haibin Wang; Ming Ge (Science of The Total Environment, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Drivers of ecological drought recovery: Insights from meteorological and soil drought impact - Chenhao Ge; Peng Sun; Rui Yao; Yayi Zhang; Han Shen; Huilin Yang (Journal of Hydrology, 2025)

Bio-Based aerogel beads with multistage pore network structure for Cr(VI) removal using ice template method - Ya-Ge Wu; Qi Cao; Shuang Dai; Jing Zhao; Ya-Juan Cai; Chuan-Zhe Zhao; Zi-Hao Yang; Yi-Xing Sun; Ting Yue; Ke-Xiao Sang; Jing-Gang Gai; Ming-Ju Tao (Chemical Engineering Journal, 2025)

Dissecting the cell microenvironment of ovarian endometrioma through single-cell RNA sequencing - Jiangpeng Wu; Siyu Xia; Wenting Ye; Yan Sun; Jing Cai; Fubing Yu; Haiping Wen; Xiuwei Yi; Taikang Li; Mingwei Chen; Jiayun Chen; Ge Song; et al. (Science China Life Sciences, 2025)

Contrasted phosphorus mobilization strategies between upland and paddy soils: insights from phosphorus biologically factions and functional gene profiling - Qi Sun; Hang Qiao; Xiangbi Chen; Xin Xia; Tida Ge; Yajun Hu; Yirong Su (Journal of Soils and Sediments, 2025)

Safflower picking points localization method during the full harvest period based on SBP-YOLOv8s-seg network - He Zhang; Yun Ge; Hao Xia; Chao Sun (Computers and Electronics in Agriculture, 2024)

Cadmium immobilization by mercapto-palygorskite in alkaline soil: Impacts on soil microbial communities and wheat rhizosphere metabolism - Wenyan Ma; Chenghao Ge; Yuebing Sun; Min Wang; Dongmei Zhou (Science of The Total Environment, 2024)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Influence of energy-saving devices on the hydrodynamic characteristics of a waterjet-propelled ship: Experimental and numerical investigation - Kewei Song; Pei Xu; Jie Gong; Cong Sun; Shenwei Ge (Ocean Engineering, 2024)

Phylogenomics resolves a 100-year-old debate regarding the evolutionary history of caddisflies (Insecta: Trichoptera) - Xinyu Ge; Lang Peng; John C. Morse; Jingyuan Wang; Haoming Zang; Lianfang Yang; Changhai Sun; Beixin Wang (Molecular Phylogenetics and Evolution, 2024)

Association between pyrrolizidine alkaloids exposure and risk of abnormal serum indices—Insights from a descriptive cross-sectional study in Yunnan Province - Xiaoxiang Sun; Zhengyuan Xie; Zheng He; Yisheng He; Zigao Zhao; Xuerong Yan; Xiangjing Song; Zijie Chen; Tao Wang; Quanrui Yue; Yiming Chen; Hanfeng Ye; et al. (Journal of Hazardous Materials, 2024)

Suitability evaluation of rural domestic sewage treatment processes in cold areas of Northeast China: Regional differences analysis and engineering application - Wenbin Zhao; Yuzhi Liu; Ge Yu; Shuang Zhong; Shuai Xia; Yang Sun; Donglei Zou (Journal of Environmental Management, 2024)

Effect of temperature on the radon release characteristics of red clay - Chao Gu; Qiang Sun; Lei Zhang; Liwei Zhang; Duoxing Yang; Boxing Yang; Zhenlong Ge (Journal of Environmental Radioactivity, 2024)

Air-sea CO2 exchange in the western Pacific influenced by monsoon and giant diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Journal of Asian Earth Sciences, 2024)

Quantitative contributions of different atmospheric circulation systems to Holocene aeolian activity in northwestern China: Evidence from a closed interdune lake in the Tengger Desert hinterland - Bing Liu; Yongtao Zhao; Aimin Liang; Aijun Sun; Zhengcai Zhang; Jianhui Ge; Hui Zhao; Fahu Chen (Global and Planetary Change, 2024)

Research progress in the preservation and packaging of fruits and vegetables: From traditional methods to innovative technologies - Vagish Dwibedi; Gursharan Kaur; Nancy George; Palak Rana; Yonghong Ge; Tong Sun (Food Packaging and Shelf Life, 2024)

Advancing the translation of vitrification strategies to whole porcine knee meniscus - Ge Pan; Peng Chen; Dustin Mueller; Marshall Wilson; Shuchun Sun; Zhenzhen Chen; Thomas Lee; Brooke Damon; Glenn Hepfer; Cherice Hill; Yongren Wu; Kelvin G.M. Brockbank; et al. (Cryobiology, 2024)

Study on the reactions of n-pentanal and n-hexanal with Br atoms: Kinetics, gas-phase products, and SOA formation - Cici Fan; Huijie Yan; Weigang Wang; Zheng Sun; Maofa Ge (Atmospheric Environment, 2024)

CMPK2 Promotes CD4+ T Cell Activation and Apoptosis through Modulation of Mitochondrial Dysfunction in Systemic Lupus Erythematosus - Ya-Nan Tan; Ge-Ge Jiang; Xiang-Wen Meng; Zhi-Yuan Lu; Yan-Ma; Jin Li; Nan-Xiang; Xiao-Ge Sun; Qian Wang; Xue Wang; Xiao-Yi Jia; Min Zhang (Cell Biochemistry and Biophysics, 2024)

Do Experimental Forests and Ranges of the Southeastern United States Represent the Climate, Ecosystem Structure, and Ecosystem Functions of the Region? - Jingfeng Xiao; Ge Sun; Kevin M Potter; Johnny Boggs; Qingyuan Zhang; Steven G McNulty (Journal of Forestry, 2024)
There are twenty experimental forest and range sites (EFRs) across the southeastern United States that are currently maintained by the USDA Forest Service (Forest Service) to conduct forest ecosystem research for addressing ecosystem management challenges. The overall objective of this study was to use multiple gridded datasets to assess the extent to which the twenty EFRs represent the climate, ecosystem structure, and ecosystem functions of southeastern forests. The EFRs represent the large variability of climate conditions across the region relatively well, but we identified small representation gaps. The representativeness of ecosystem structure by these EFRs can be improved by establishing EFRs in forests with relatively low tree cover, leaf area index, or tree canopy height. The current EFRs also represent the forest ecosystem functions of the region relatively well, although areas with intermediate and low aboveground biomass and water yield are not well represented. The trends in climate, ecosystem structure, and ecosystem functions were generally consistent between the region and the EFRs. Our study indicates that the current EFRs represent the region relatively well, but establishing additional EFRs in specific areas within the region could help more completely assess how southeastern forests respond to climate change, disturbance, and management practices. Study Implications: This study across the experimental forests and ranges (EFRs) and the southeastern forest region fills the knowledge gap regarding climate, ecosystem structure, and ecosystem functions of EFRs in the context of the broader southeastern forest region. Understanding ecosystem functions and structures across the EFR network can help the Southern Research Station to address new research questions. Our study indicates that the current EFRs represent the climate, ecosystem structure, and ecosystem functions of southeastern forests well. However, establishing additional EFRs in certain regions could help more completely assess how southeastern forests respond to climate change, disturbance, and management practices.

Impact of floods on the environment: A review of indicators, influencing factors, and evaluation methods - Yadong Zhang; Zongkun Li; Hongyin Xu; Wei Ge; Hui Qian; Jingjing Li; Heqiang Sun; Hua Zhang; Yutie Jiao (Science of The Total Environment, 2024)

Liver damage and lipid metabolic dysregulation in adult zebrafish (Danio rerio) induced by spirotetramat - Xunyue Liu; Haojie Zhu; Peng Liu; Junyao Ge; Qiong Rao; Wenze He; Jianqiang Sun (Science of The Total Environment, 2024)

Potassium persulfate enhances humification of chicken manure and straw composting: The perspective of rare and abundant microbial community structure and ecological interactions - Xiujun Tu; Bo Yin; Jie Kang; Zhenchao Wu; Yuhao Guo; Guoxu Ao; Yangcun Sun; Jingping Ge; Wenxiang Ping (Science of The Total Environment, 2024)

Fusion property prediction and mineral reaction mechanism of coal/biomass ash blends upon in-situ tests in the gasification process - Zefeng Ge; Yuqing Wu; Zenghui Hou; Lijuan Sun; Mingxun Zeng; Yuna Ma; Zhenting Zha; Qiuxiang Lu; Huiyan Zhang (Fuel, 2024)

Transcriptome and metabolome analyses reveal the effects of formula and breast milk on the growth and development of human small intestinal organoids - Xianli Wang; Yiming Zhong; Chengdong Zheng; Chenxuan Huang; Haiyang Yao; Zimo Guo; Yilun Wu; Zening Wang; Zhengyang Wu; Ruihong Ge; Wei Cheng; Yuanyuan Yan; et al. (Food Research International, 2024)

New insights into how freeze-drying and cryo-milling affects the fine structure and digestibility of gelatinized starch - Ruhui Xia; Tongtong Xu; Fei Ge; Yue Sun; Zhenjiong Wang; Weiwei Cheng; Di Wu; Xifeng Xia; Peiqiang Yang; Xiaozhi Tang (Food Chemistry, 2024)

Metagenomic analysis unveiled the response of microbial community and antimicrobial resistome in natural water body to duck farm sewage - Chang Fang; Kai-di Liu; Feng-jie Tian; Jin-ying Li; Si-jie Li; Rong-min Zhang; Jian Sun; Liang-xing Fang; Hao Ren; Min-ge Wang; Xiao-ping Liao (Environmental Pollution, 2024)

C C rupture in key monosaccharides and succedent redox in supercritical ethanol - Qianxin Sun; Chenyu Ge; Shanshan Feng; Qiufu Zeng; Guiying Li; Changwei Hu (Chemical Engineering Journal, 2024)

Dual optimization strategy assisted m-phenylenediamine-based hypercrosslinked polymer loaded ultrafine bimetallic nanoparticles for efficient formic acid dehydrogenation - Hongtan Cai; Qiaoyi Zhang; Xin Liu; Yulin Li; Meiyan Wang; Ge Gao; Zeshuo Meng; Haoteng Sun; Xiufeng Hao (Chemical Engineering Journal, 2024)

Polyimide-Coating-on-Aramid nanofiber strategy toward ultralight organic aerogels with multifunctional properties - Xiaolei Wang; Kunlong Zhao; Wenxin Cao; Dongchao Ji; Zhijie Ye; Zhenhua Su; Ge Gao; Zhuochao Wang; Chunqiang Sun; Yingqi Liu; Lan Zhang; Tianyu Zhang; et al. (Chemical Engineering Journal, 2024)

Regenerated spent LiFePO4 with tailored residual copper-atoms towards improved energy-storage capacity and reversibility - Zihao Zeng; Hai Lei; Jiexiang Li; Bing Wang; Shuya Lei; Xiaobo Ji; Wei Sun; Yue Yang; Peng Ge (Chemical Engineering Journal, 2024)

On the properties of lower mid-latitudes ionospheric scintillation observed over Chengdu, China - Shucan Ge; Hailong Li; Song Zhang; Mengyan Zhu; Jinghua Li; Bin Xu; Tong Xu; Shuji Sun; Lin Meng; Jian Wu (Advances in Space Research, 2024)

Coarse particulate air pollution and mortality in a multidrug-resistant tuberculosis cohort - Huiying Feng; Erjia Ge; Nicholas Grubic; Xin Liu; Hui Zhang; Qiang Sun; Xiaolin Wei; Fangjing Zhou; Shanshan Huang; Yuhui Chen; Huixin Guo; Jianwei Li; et al. (Science of The Total Environment, 2024)

The quorum sensing SinI/SinR-TraI/TraR systems promote Pb stabilization by Ensifer adhaerens S24 in the Pb-polluted aquatic environment - Yanyan Ge; Qi Sheng; Lijing Sun; Linyan He; Xiafang Sheng (Journal of Hazardous Materials, 2024)

Provincial equity and enhanced health are key drivers for China's 2060 carbon neutrality - Jiaxin Dong; Siwei Li; Yisheng Sun; Weishu Gong; Ge Song; Yu Ding; Jie Yang; Mengfan Teng; Ruilin Wang; Jia Xing; Yang Ou; Wei Gong (Journal of Cleaner Production, 2024)

Cost-effective degradation of ultra-high concentration polyvinyl alcohol through peroxymonosulfate based oxidation using nano spinel CoFe2O4 deposited acidified diatomite as the catalyst - Shuang Zhai; Yanyan Li; Xiaoyun Long; Haisang Liu; Mingqiao Ge; Qilong Sun; Yiwei Chen (Journal of Environmental Chemical Engineering, 2024)

3DOM Cu-Ce binary composite oxides for selective catalytic reduction of NO with CO - Ye Jiang; Zhuang Ji; Xin Sun; Hongwei Ge; Yinsheng Jiang; Yichao Xu; Zhengda Yang (Journal of Environmental Chemical Engineering, 2024)

Crosslinking ability of hydrolyzed distarch phosphate and its stabilizing effect on rehydrated sea cucumber - Jiaqi Yu; Wenhao Ge; Kaifeng Wang; Wenhui Hao; Shangju Yang; Ying Xu; Tingyu Feng; Peng Han; Xun Sun (Food Chemistry, 2024)

Structure, physicochemical and adsorption properties of insoluble dietary fiber from Lycium barbarum residue: A potential functional factor - Haixuan Sun; Weiben Ge; Deao Song; Yubing Li; Yu Wang; Hongxin Wang (Food Bioscience, 2024)

Study on the regulation of droplet motion behavior on superhydrophobic surfaces - Shiya Gu; Hongcheng Ge; Hengyi Wei; Yuanyuan Sun; Tianyi Zhang; Huan Wang; Liyan Wu; Xiaoguang Fan (Chemical Engineering Journal, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

Biogenic Selenium Nanoparticles Synthesized by L. brevis 23017 Enhance Aluminum Adjuvanticity and Make Up for its Disadvantage in Mice - Zheng Zhang; Xinqi De; Weijiao Sun; Runhang Liu; Yifan Li; Zaixing Yang; Ning Liu; Jingyi Wu; Yaxin Miao; Jiaqi Wang; Fang Wang; Junwei Ge (Biological Trace Element Research, 2024)

Effect of dietary vitamin D3 on growth performance and functional homeostasis of particular intestinal segments in grass carp fingerlings - Hao Sun; Pei Ge; Jiaxi Liu; Dan Xiong; Mingjun Zhu; Hong Zhou (Aquaculture International, 2024)

Deubiquitinating enzyme USP28 inhibitor AZ1 alone and in combination with cisplatin for the treatment of non-small cell lung cancer - Yiqiong Song; Longhao Wang; Yuanyuan Zheng; Lanqi Jia; Chunwei Li; Ke Chao; Lifeng Li; Shilong Sun; Yujie Wei; Yahao Ge; Yaqi Yang; Lili Zhu; et al. (Apoptosis, 2024)

Novel Sustained Release Azithromycin Resinate Fabricated by One-Pot Ion-exchange Performed in Hydro-alcoholic Solution - Hongyu Liang; Meihui Zhao; Shaoning Wang; Da Wang; Jingxin Gou; Yanjie Bai; Mingyue Shen; Junfeng Wang; Yujie Cheng; Ning Ge; Yi Zhao; Jie Zeng; et al. (AAPS PharmSciTech, 2024)

Explainable Ensemble Learning Approaches for Predicting the Compression Index of Clays - Qi Ge; Yijie Xia; Junwei Shu; Jin Li; Hongyue Sun (Journal of Marine Science and Engineering, 2024)
Accurate prediction of the compression index (cc) is essential for geotechnical infrastructure design, especially in clay-rich coastal regions. Traditional methods for determining cc are often time-consuming and inconsistent due to regional variability. This study presents an explainable ensemble learning framework for predicting the cc of clays. Using a comprehensive dataset of 1080 global samples, four key geotechnical input variables—liquid limit (LL), plasticity index (PI), initial void ratio (e0), and natural water content w—were leveraged for accurate cc prediction. Missing data were addressed with K-Nearest Neighbors (KNN) imputation, effectively filling data gaps while preserving the dataset’s distribution characteristics. Ensemble learning techniques, including Random Forest (RF), Gradient Boosting Decision Trees (GBDT), Extreme Gradient Boosting (XGBoost), and a Stacking model, were applied. Among these, the Stacking model demonstrated the highest predictive performance with a Root Mean Squared Error (RMSE) of 0.061, a Mean Absolute Error (MAE) of 0.043, and a Coefficient of Determination (R2) value of 0.848 on the test set. Model interpretability was ensured through SHapley Additive exPlanations (SHAP), with e0 identified as the most influential predictor. The proposed framework significantly improves both prediction accuracy and interpretability, offering a valuable tool to enhance geotechnical design efficiency in coastal and clay-rich environments.

Nonlinearly coupled electro-osmotic flow in variable charge soils - Xiaojuan Yang; Ge Shi; Chao Wu; Ye Yuan; Honglei Sun; Long Cang (Chemosphere, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Improving the sustainability of milk production across different climate regions in China - Zhaoping Wu; Yuanyuan Du; Guofu Yang; Linshan Lin; Xiaoyu Hou; Yandong Tan; Xing Fan; Yuan Ren; Bijie Wu; Shun Liu; Scott X. Chang; Wanhong Sun; et al. (Sustainable Production and Consumption, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Investigation of oxygen packaging to maintain beef color stability and microbiology safety after periods of long-term superchilled storage - Jun Yang; Xue Chen; Xinxin Duan; Ke Li; Haijian Cheng; Ge Sun; Xin Luo; David L. Hopkins; Benjamin W.B. Holman; Yimin Zhang; Enliang Song (Meat Science, 2024)

The coupling effect promotes superoxide radical production in the microalgal-fungal symbiosis systems: Production, mechanisms and implication for Hg(II) reduction - Dan Ai; Tao Wu; Zuhan Ge; Zeguo Ying; Shiqing Sun; Deying Huang; Jibiao Zhang (Journal of Hazardous Materials, 2024)

Multifunctional bacterial cellulose-bentonite@polyethylenimine composite membranes for enhanced water treatment: Sustainable dyes and metal ions adsorption and antibacterial properties - Xueqing Zhao; Mingbo Yang; Yucheng Shi; Liyuan Sun; Haolong Zheng; Mengmeng Wu; Ge Gao; Ting Ma; Guoqiang Li (Journal of Hazardous Materials, 2024)

Insighting the effect of lard-based diacylglycerol on the thermal gelation and rheological properties of myofibrillar protein influenced by soy protein isolate - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Mangang Wu; Qingfeng Ge; Xinyan Peng; Baohua Kong; Hai Yu (Food Hydrocolloids, 2024)

Ecotoxicological evaluation and regeneration impairment of planarians by dibutyl phthalate - Fan Wu; Zhihong Kong; Peng Ge; Dandan Sun; Dezeng Liu; Zimei Dong; Guangwen Chen (Environmental Research, 2024)

Valorization of agriculture waste: Preparation of alkoxysilanes from mixed rice straw and rice husk ash - Shanshan Feng; Chenyu Ge; Qianxin Sun; Wanping Zheng; Guiying Li; Changwei Hu (Chemical Engineering Journal, 2024)

Iodine/soluble starch cryogel: An iodine-based antiseptic with instant water-solubility, improved stability, and potent bactericidal activity - Wei Sun; Zi-Xi Wang; Yuxin Guo; Chengcheng Li; Ge Gao; Fu-Gen Wu (Carbohydrate Polymers, 2024)

Genome-wide association study and selective sweep analysis uncover candidate genes controlling curd branch length in cauliflower - Yingxia Yang; Yutong Guo; Jing Wang; Wenjuan Cheng; Mingjie Lyu; Qian Wang; Jianjin Wu; Mingyan Hua; Weihua Zhang; Deling Sun; Xianhong Ge; Xingwei Yao; et al. (Theoretical and Applied Genetics, 2024)

Biomolecular condensates and disease pathogenesis - Ke Ruan; Ge Bai; Yanshan Fang; Dan Li; Tingting Li; Xingguo Liu; Boxun Lu; Qing Lu; Zhou Songyang; Shuguo Sun; Zheng Wang; Xin Zhang; et al. (Science China Life Sciences, 2024)

Expression Analysis of Metacaspase (MC) Gene Family in Response to Ethylene Signal During Apple Fruit Ripening - Mingyu Sun; Jingyi Lv; Yingzhi Zhang; Liang Zhang; Jingxin Chen; Yonghong Ge; Jianrong Li (Plant Molecular Biology Reporter, 2024)

Dynamic Response of Roadbed Soil Under Various Dynamic Load Waveforms - Xin-Sheng Zhang; Yan-Ge Chen; Chang-Biao He; Zhen Li; Lei Liao; Yun Cheng; Yin-Lei Sun (Geotechnical and Geological Engineering, 2024)

Dynamic behavior of electro-osmosis in variable charge soils: Insights on termination and direction reversal - Xiaojuan Yang; Ge Shi; Min Yang; Ye Yuan; Honglei Sun (Chemosphere, 2024)

Exploring the biosynthetic possibilities of hydroxylated polybrominated diphenyl ethers from bromophenols in Prorocentrum donghaiense: Implications for bioremediation - Bin Li; Jianghong Shi; Xueling Xiang; Mengtao Zhang; Hui Ge; Shuhan Sun (Chemosphere, 2024)

Corrigendum to “Detrimental effect of bisphenol S in mouse germ cell cyst breakdown and primordial follicle assembly” [Chemosphere. 2021 Feb;264(Pt 1):128445] - Wen-Xiang Liu; Farini Donatella; Shao-Jing Tan; Wei Ge; Jun-Jie Wang; Xiao-Feng Sun; Shun-Feng Cheng; Wei Shen (Chemosphere, 2024)

Experimental investigation and cohesive zone modeling of the interface mechanical behavior in composite tunnel linings - Xiaohe Sun; Chenghua Shi; Yangyang Ge (Tunnelling and Underground Space Technology, 2024)

Multiscale experimental insights into vacuum drying of sludge for enhanced energy efficiency and emission control - Yang Yu; Xiaofeng Sun; Huarong Zhang; Weihong Wu; Tianxing Zhang; Shifu Ge (Science of The Total Environment, 2024)

Integrated analysis of miRNAome and transcriptome reveals that microgravity induces the alterations of critical functional gene modules via the regulation of miRNAs in short-term space-flown C. elegans - Xinye He; Lei Zhao; Baohang Huang; Ge Zhang; Ye Lu; Dong Mi; Yeqing Sun (Life Sciences in Space Research, 2024)

Understanding the effects of afforestation on water quantity and quality at watershed scale by considering the influences of tree species and local moisture recycling - Henrique Haas; Latif Kalin; Ge Sun; Sanjiv Kumar (Journal of Hydrology, 2024)

Economic life evaluation of reservoir dams based on comprehensive costs and benefits analysis considering potential dam breach: A case study of the Luhun reservoir in China - Wei Ge; Heqiang Sun; Laihong Jing; Zongkun Li; Yongchuang Li; Bo Cao; Te Wang; Yutie Jiao; Hua Zhang; Jianyou Wang; Pieter van Gelder (Journal of Hydrology, 2024)

Climate and vegetation change impacts on future conterminous United States water yield - Henrique F. Duarte; John B. Kim; Ge Sun; Steven G. McNulty; Jingfeng Xiao (Journal of Hydrology, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

Cactus-inspired moisture harvesting for sustainable and efficient high salinity desalination - Can Ge; Xianzhang Wu; Jiugang Li; Keshuai Liu; Duo Xu; Chong Gao; Yingcun Liu; Ping Sun; Ze Chen; Jian Fang (Desalination, 2024)

A robust and low-cost blended-fiber-based evaporator with high efficiency for solar desalination - Qianqian Liu; Xiangjun Liu; Ge Chen; Pei Feng; Yucheng Xiong; Meng An; Cheng Shao; Xiongfei Zhu; Renzong Wang; Jianshi Sun; Jisheng Sun; Chunfang Guo; et al. (Desalination, 2024)

Reactive oxygen species-responsive nanotherapy for the prevention and treatment of cerebral ischemia–reperfusion injury - Jianglong Kong; Runxuan Chu; Junjie Wen; Hongrui Yu; Jiawen Liu; Yuting Sun; Meiru Mao; Xiaohan Ge; Zixin Jin; Weimin Huang; Na Hu; Yi Zhang; et al. (Chemical Engineering Journal, 2024)

Coordination-induced amidated modified polyacrylonitrile loaded ultrafine palladium nanoparticles for thermocatalytic hydrogen evolution - Qiaoyi Zhang; Hongtan Cai; Xin Liu; Yulin Li; Meiyan Wang; Ge Gao; Zeshuo Meng; Haoteng Sun; Xiufeng Hao (Chemical Engineering Journal, 2024)

CT Angiography Radiomics Combining Traditional Risk Factors to Predict Brain Arteriovenous Malformation Rupture: a Machine Learning, Multicenter Study - Shaosen Zhang; Junjie Wang; Shengjun Sun; Qian Zhang; Yuanren Zhai; Xiaochen Wang; Peicong Ge; Zhiyong Shi; Dong Zhang (Translational Stroke Research, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Laboratory tests on the traffic-induced cyclic behavior of anisotropically overconsolidated clay under different drainage conditions - Xuan He; Honglei Sun; Chuan Gu; Junhao Yang; Jun Wang; Miaomiao Ge (Soil Dynamics and Earthquake Engineering, 2024)

Pilot analysis of tire tread characteristics and associated tire-wear particles in vehicles produced across distinct time periods - Mengzhu Zhang; Jiachen Li; Hang Yin; Xin Wang; Yechen Qin; Zhengjun Yang; Yi Wen; Jiaxin Luo; Dailin Yin; Yunshan Ge; Changhui Wang; Xingyu Sun; et al. (Science of The Total Environment, 2024)

East Asian Winter Monsoon and enhanced stratification in the western Pacific promoted giant marine diatom (Ethmodiscus rex) blooms during the last deglaciation - Huaineng Tang; Haoran Ye; Wenqing Yang; Yikang Huang; Tiantai Sun; Yangyuan Ge; Hongxin Zhang; Yuqing Sun; Shanying Lin; Zhonghui Liu; Wenhua Li; Zhouqing Xie (Quaternary Science Reviews, 2024)

Exploration of the shelf-life difference between chilled beef and pork with similar initial levels of bacterial contamination - Ge Sun; Jun Yang; Benjamin W.B. Holman; Chrysoula C. Tassou; Olga S. Papadopoulou; Xin Luo; Lixian Zhu; Yanwei Mao; Yimin Zhang (Meat Science, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

A non-covalent binding strategy for the stabilization of fish collagen triple helices to promote its applications - Zhening Sun; Yihao Ge; Xinhui Cai; Qian Liu; Zhiwei Yang; Xi Chen; Zhaojing Zheng (Food Hydrocolloids, 2024)

Corrigendum to “Transplantation of mitochondria encapsulated in hydrogel ameliorates myocardial ischemia-reperfusion injury” [Chem. Eng. J. 460 (2023) 141799] - Ya Huang; Xiaolei Sun; Rifeng Gao; Liwei Zhang; Hang Chen; Yang Lv; Xiang Wei; Yunzeng Zou; Kai Hu; Aijun Sun; Junbo Ge (Chemical Engineering Journal, 2024)

Membraneless organelles assembled by AuNPs-enzyme integration in non-photosynthetic bacteria: Achieving high specificity and selectivity for solar hydrogen production - Hui Li; Xiaoxuan Yu; Yaqi Wu; Cong Li; Zhengwei Xu; Wang Liu; Shuheng Chen; Hongcheng Sun; Yan Ge; Zhenhui Qi; Junqiu Liu (Chemical Engineering Journal, 2024)

For regenerated graphite: Tailoring sub-surface architecture with strong pre-storage abilities towards high-rate properties - Zhengqiao Yuan; Yu Dong; Zihao Zeng; Wenqing Zhao; Bin Wang; Hai Lei; Wei Sun; Xiaobo Ji; Yue Yang; Peng Ge (Chemical Engineering Journal, 2024)

Characteristics of propagation from meteorological drought to ecological drought in China: Lag and cumulative effects - Chenhao Ge; Peng Sun; Rui Yao; Yufei Wang; Wenhui Chen; Yaojin Bian; Qiang Zhang (Atmospheric Research, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Photosensitization of riboflavin reduces the susceptibility to gray mold in postharvest kiwifruit - Yuhan Long; Yue Sun; Bei Zhou; Ge Zhu; Xiaolong Chen; Yongjie Qi; Ke Wang (Postharvest Biology and Technology, 2024)

Examining nonlinear effects of socioecological drivers on urban solar energy development in China using machine learning and high-dimensional data - Yi Zhao; Weiting Ge; Yanwei Sun; Guanming Qiao; Danfeng Zhu; Hongying Ai (Journal of Environmental Management, 2024)

Preparation, characterization, stability, and controlled release of chitosan-coated zein/shellac nanoparticles for the delivery of quercetin - Jiawen Liu; Hongrui Yu; Jianglong Kong; Xiaohan Ge; Yuting Sun; Meiru Mao; David Y. Wang; Yi Wang (Food Chemistry, 2024)

All-natural plant-based HIPE-gels simultaneously stabilizing with Quillaja saponin and soy protein isolate: Influence of environmental stresses on stability - Xiao-Wei Chen; Tian-Ge Wang; Wen-Jun Yin; Lin-Shang Zhang; Shang-De Sun (Food Hydrocolloids, 2024)

Spatial-temporal-controlled NO gas and PARP1 siRNA delivery for alleviating the dilemma of deeper sonodynamic therapy in pancreatic cancer - Qingshuang Tang; Yuan Wang; Ruiqi Wu; Zexing Yu; Xue Shi; Yang Song; Lulu Zhang; Xin Li; Jinxia Zhang; Suhui Sun; Xiaotu Ma; Shuyu Xu; et al. (Chemical Engineering Journal, 2024)

Organized assembly of chitosan into mechanically strong bio-composite by introducing a recombinant insect structural protein OfCPH-1 - Lei Chen; Fei Shao; Kaiwen Chen; Nan Wu; Bingbing Sun; Dan Ge; Guirong Wang; Huanan Wang; Qing Yang (Carbohydrate Polymers, 2024)

Occupant behavioral adjustments and thermal comfort with torso and/or foot warming in two cold indoor environments - Faming Wang; Ying Ke; Qing Zheng; Xin'ge Han; Wei Su; Xiang Zhang; Tze-Huan Lei; Zhou Sun; Haiyan Zhou; Bin Yang (Building and Environment, 2024)

The Photocatalytic Ozonation Oxidation Synergistic Degradation on Organic Pollutants In Coal Chemical Phenol-Ammonia Wastewater by Two-Dimensional Nanosheets Bi2WO6 - Fei Li; Qiang Luo; Weijun Zhen; Qing Ge; Yushen Zhou; Chunmei Ma; Pengtao Sun; Jianbo Xu; Buning Chen (Water, Air, & Soil Pollution, 2024)

TLR2 Mediates Microglial Activation and Contributes to Central Sensitization in a Recurrent Nitroglycerin-induced Chronic Migraine Model - Xuejiao Liu; Wenping Yang; Chenlu Zhu; Songtang Sun; Bin Yang; Shouyi Wu; Longde Wang; Zhiyan Liu; Zhaoming Ge (Molecular Neurobiology, 2024)

Toward spectrally truthful models for gap-filling soil respiration and methane fluxes. A case study in coastal forested wetlands in North Carolina - Bhaskar Mitra; Kevan Minick; Michael Gavazzi; Prajaya Prajapati; Maricar Aguilos; Guofang Miao; Jean-Christophe Domec; Steve G. McNulty; Ge Sun; John S. King; Asko Noormets (Agricultural and Forest Meteorology, 2024)

A method for tight gas reservoir evaluation based on nuclear logging - Xinyue Fu; Wensheng Wu; Bowen Sun; Mingsong Wu; Hu Wang; Yunlong Ge (Acta Geophysica, 2024)

Research progress on improving the freeze-drying resistance of probiotics: A review - Sitong Ge; Jiarun Han; Qiaoyu Sun; Qingqing Zhou; Zhongdu Ye; Ping Li; Qing Gu (Trends in Food Science & Technology, 2024)

Overexpression of the Panax ginseng CyP gene enhances abiotic and biotic stress tolerance in transgenic Arabidopsis - Tianxia Sun; Miao Zhang; Huafeng Geng; Yuming Wang; Zhimei Liu; Dongming Xue; Wei Liu; Hongling Li; Shuaijun Li; Ge Hui; Yu Zhao (Physiological and Molecular Plant Pathology, 2024)

The effects of microgravity on stem cells and the new insights it brings to tissue engineering and regenerative medicine - Hong-Yun Nie; Jun Ge; Kai-Ge Liu; Yuan Yue; Hao Li; Hai-Guan Lin; Hong-Feng Yan; Tao Zhang; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Insights into the microbiome and metabolome assembly during short-term storage of native grass hay - Qiang Si; Zhijun Wang; Lin Sun; Mingjian Liu; Wei Liu; Gentu Ge; Yushan Jia; Shuai Du (Journal of Stored Products Research, 2024)

Effects of inter-basin transfers on watershed hydrology and vegetation greening in a large inland river basin - Lin Wang; Wei Wei; Ge Sun; Bojie Fu; Liding Chen; Xiaoming Feng; Philippe Ciais; Bhaskar Mitra; Lixin Wang (Journal of Hydrology, 2024)

The quorum sensing SinI/R system contributes to cadmium immobilization in Ensifer adhaerens NER9 in the cadmium-contaminated solution - Lijing Sun; Qi Sheng; Yanyan Ge; Linyan He; Xiafang Sheng (Journal of Hazardous Materials, 2024)

Adsorption of Cd(II) on mercapto-palygorskite functional materials with different proportions: Performance, mechanism and DFT study - Ge Gao; Tong Sun; Yuebing Sun; Yingming Xu; Xuefeng Liang (Journal of Cleaner Production, 2024)

Are longer and more intense heatwaves more prone to extreme precipitation? - Peng Sun; Yaojin Bian; Shifang Yu; Rui Yao; Zhongtian Wang; Qiang Zhang; Wenhui Chen; Chenhao Ge; Zice Ma; Wenying Du (Global and Planetary Change, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Exploring the relationship between starch structure and physicochemical properties: The impact of extrusion on highland barley flour - Fei Ge; Yue Sun; Chenxi Yang; Weiwei Cheng; Zhenjiong Wang; Xifeng Xia; Di Wu; Xiaozhi Tang (Food Research International, 2024)

Fhb7-GST catalyzed glutathionylation effectively detoxifies the trichothecene family - Bingqian Hou; Dawei Wang; Fangfang Yan; Xinxin Cheng; Yongchang Xu; Xuepeng Xi; Wenyang Ge; Silong Sun; Peisen Su; Lanfei Zhao; Zhongfan Lyu; Yongchao Hao; et al. (Food Chemistry, 2024)

Combined neurotoxicity of aged microplastics and thiamethoxam in the early developmental stages of zebrafish (Danio rerio) - Yanan Sun; Ping Ding; Jiayi Zhang; Kexin Sun; Xintong Li; Qing Ge; Yao Dang; Yunjiang Yu; Guocheng Hu (Environmental Pollution, 2024)

Bone tissue engineering based on sustained release of MiR29c-modified framework nucleic acids from an injectable hydrogel - Jiafei Sun; Yang Gao; Yangxue Yao; Yong Li; Maogeng Feng; Long Bai; Xingyu Chen; Yichen Ge; Yunfeng Lin; Xiaoxiao Cai (Chemical Engineering Journal, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

A quantitative composition calculation model of mine water source based on “emblematic ions” - Huiqing Yuan; Zhimin Xu; Yajun Sun; Li Zhang; Ge Chen (Hydrogeology Journal, 2024)

Analysis of the trigger conditions and activity trend in debris flow along Sichuan-Tibet traffic corridor (Xinduqiao-Changdu section) under environmental changes - Yuqing Sun; Yonggang Ge; Xingzhang Chen; Lu Zeng; Qin Tang; Xinyue Liang; Lianbin Yang (Bulletin of Engineering Geology and the Environment, 2024)

Visually evaluating drug efficacy in living cells using COF-based fluorescent nanoprobe via CHA amplified detection of miRNA and simultaneous apoptosis imaging - Chuandong Ge; Zhe Chen; Heming Sun; Ping Sun; Jiayin Zhao; Yanjuan Wu; Jing Xu; Mingyang Zhou; Mingming Luan (Analytica Chimica Acta, 2024)

Corrigendum to “Energy availability and leaf area dominate control of ecosystem evapotranspiration in the southeastern U.S” [Agriculture and Forest Meteorology Volume 349 (2024)/109960] - Maricar Aguilos; Ge Sun; Ning Liu; Yulong Zhang; Gregory Starr; Andrew Christopher Oishi; Thomas L O'Halloran; Jeremy Forsythe; Jingfeng Wang; Modi Zhu; Devendra Amatya; Benju Baniya; et al. (Agricultural and Forest Meteorology, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Pilot–scale vertical continuous–flow reactors applied to treat rural domestic wastewater at low temperature via aerobic granular sludge - Shibo Cong; Ge Yu; Shuai Xia; Haiyang Yu; Yang Sun; Yu Gao; Yuzhi Liu; Donglei Zou (Journal of Water Process Engineering, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

Forest fire susceptibility mapping based on precipitation-constrained cumulative dryness status information in Southeast China: A novel machine learning modeling approach - Longlong Zhao; Yuankai Ge; Shanxin Guo; Hongzhong Li; Xiaoli Li; Luyi Sun; Jinsong Chen (Forest Ecology and Management, 2024)

Mechanisms of imbalanced testicular homeostasis in infancy due to aberrant histone acetylation in undifferentiated spermatogonia under different concentrations of Di(2-ethylhexyl) phthalate (DEHP) exposure - Yu Tian; Jiachen Guo; Lei Hua; Yinuo Jiang; Wei Ge; Xiaoyuan Zhang; Diya Cai; Dongliang Lu; Bin Wang; Wei Shen; Zhongyi Sun; Baoquan Han (Environmental Pollution, 2024)

KOH-activated biochar and chitosan composites for efficient adsorption of industrial dye pollutants - Xu Su; Xuanming Wang; Ziyi Ge; Zhengrong Bao; Li Lin; Yixuan Chen; Wanning Dai; Yuanyuan Sun; Hechong Yuan; Wen Yang; Jun Meng; Hailong Wang; et al. (Chemical Engineering Journal, 2024)

A silver nanowires@Prussian blue composite aerogel-based wearable sensor for noninvasive and dynamic monitoring of sweat uric acid - Danfeng Jiang; Yajie Zhu; Zhe Sun; Zhelei Zhu; Qian He; Xi Huang; Ying Yang; Yuancai Ge; Qingwen Zhang; Yi Wang (Chemical Engineering Journal, 2024)

Development of a nonstationary Standardized Precipitation Evapotranspiration Index (NSPEI) and its application across China - Peng Sun; Chenhao Ge; Rui Yao; Yaojin Bian; Huilin Yang; Qiang Zhang; Chong-Yu Xu; Vijay P. Singh (Atmospheric Research, 2024)

Predictions of air quality and challenges for eliminating air pollution during the 2022 Olympic Winter Games - Wenyi Yang; Qizhong Wu; Jie Li; Xueshun Chen; Huiyun Du; Zhe Wang; Dongqing Li; Xiao Tang; Yele Sun; Zhilan Ye; Xiaole Pan; Baozhu Ge; et al. (Atmospheric Research, 2024)

Agarose amplification based sequencing characterization cell-free RNA in preimplantation spent embryo medium - Huajuan Shi; Qinyu Ge; Min Pan; Yuqi Sheng; Ting Qi; Ying Zhou; Yuqing Sun; Yunfei Bai; Lingbo Cai (Analytica Chimica Acta, 2024)

Energy availability and leaf area dominate control of ecosystem evapotranspiration in the southeastern U.S. - Maricar Aguilos; Ge Sun; Ning Liu; Yulong Zhang; Gregory Starr; Andrew Christopher Oishi; Thomas L O'Halloran; Jeremy Forsythe; Jingfeng Wang; Modi Zhu; Devendra Amatya; Benju Baniya; et al. (Agricultural and Forest Meteorology, 2024)

A study on siting of emergency shelters for dam failure floods considering population distribution and weather effects - Yutie Jiao; Zongkun Li; Wei Ge; Laihong Jing; Meimei Wu; Te Wang; Heqiang Sun; Jianyou Wang; Xiangyang Zhang; Pieter van Gelder (Science of The Total Environment, 2024)

Importance of forest stand structures for gross rainfall partitioning on China’s Loess Plateau - Xu Hu; Zhaoqi Fu; Ge Sun; Biao Wang; Keyan Liu; Churui Zhang; Lu Han; Lixin Chen; Zhiqiang Zhang (Journal of Hydrology, 2024)

Unveiling a novel mechanism for competitive advantage of ciprofloxacin-resistant bacteria in the environment through bacterial membrane vesicles - Zuye Fang; Xinlu Zhao; Ziyuan Zhang; Jiayi Wu; Jiliang Cheng; Dan Lei; Nan Li; Ruiguang Ge; Qing-Yu He; Xuesong Sun (Journal of Hazardous Materials, 2024)

Ecological succession of abundant and rare subcommunities during aerobic composting in the presence of residual amoxicillin - Liangyang Mao; Jie Kang; Rui Sun; Jiaxin Liu; Jingping Ge; Wenxiang Ping (Journal of Hazardous Materials, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Natural and anthropogenic dissolved organic matter in landfill leachate: Composition, transformation, and their coexistence characteristics - Jing Zheng; Xian-Ge Wang; Yue Sun; Yu-Xin Wang; Hao-Qun Sha; Xiao-Song He; Xiao-Jie Sun (Journal of Hazardous Materials, 2024)

The promoting effect of electron beam irradiation on enzymatic saccharification and alcohol fermentation of sorghum meal: Related mechanisms - Mengting Yan; Chenyang Sun; Jiangtao Yu; Junqing Bai; Huishan Shen; Xiuyun Zhang; Yifan Lu; Zhuangzhuang Sun; Xiangzhen Ge; Wei Liang; Jie Zeng; Haiyan Gao; et al. (Journal of Cereal Science, 2024)

GPR-TransUNet: An improved TransUNet based on self-attention mechanism for ground penetrating radar inversion - Ge Junkai; Sun Huaifeng; Shao Wei; Liu Dong; Yao Yuhong; Zhang Yi; Liu Rui; Liu Shangbin (Journal of Applied Geophysics, 2024)

Ionic liquid microwave-assisted hydrodistillation extraction of Angelica sinensis essential oil and its own anti-inflammatory and antioxidant activities - Taotao Li; Huanxian Shi; Wenfei Wang; Jia Li; Tiantian Tang; Yujiao Wang; Ding Liu; Kai Yang; Xuan Wang; Jie Wang; Ning Xia; Jinhui Wang; et al. (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Occurrence, dietary influence and risks of selected trace metals in different coastal predatory species - Le Chao; Gang Ni; Yunfeng Ge; Chi Zhang; Jingrui Chen; Jiachen Sun (Environmental Research, 2024)

LiteTransNet: An interpretable approach for landslide displacement prediction using transformer model with attention mechanism - Qi Ge; Jin Li; Xiaohong Wang; Yiyan Deng; Keying Zhang; Hongyue Sun (Engineering Geology, 2024)

Highly dispersed ultrasmall BiOCl nanoclusters on graphene sheets as high-performance anion-capture electrode for hybrid capacitive deionization - Weiqing Kong; Xu Ge; Desheng Kong; Chenmiao Liu; Jianpeng Sun; Xiao Zhu; Meng Zhang; Yuanyuan Feng (Desalination, 2024)

Feasibility of Injecting Pretreated Mine Water into a Deep Ordovician Aquifer in the Lilou Coal Mine, China - Xin Li; Ge Chen; Wei Wei; Xianfeng Tan; Zhimin Xu; Li Zhang; Feng Zhang; Qi Liu; Yajun Sun (Mine Water and the Environment, 2024)

Microstructure-dependent CO2-responsive microemulsions for deep-cleaning of oil-contaminated soils - Lingfei Liu; Mingshan Zhang; Yi Lu; Gaojian Chen; Binda Lu; Lingling Ge; Zhouguang Lu; Dejun Sun; Zhenghe Xu (Chemosphere, 2024)

Identification of organic pollutants and heavy metals in natural rubber wastewater and evaluation its phytotoxicity and cytogenotoxicity - Dayu Zhu; Chengjun Ge; Ying Sun; Huamei Yu; Jun Wang; Hongfei Sun (Chemosphere, 2024)

Flow-through electrode system (FES): An effective approach for biofouling control of reverse osmosis membranes for municipal wastewater reclamation - Hao-Bin Wang; Yin-Hu Wu; Yi-Ge Sun; Yu-Qing Xu; Zhuo Chen; Song Xue; Zhuo-Wei Zhang; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Water Research, 2024)

Measurement of perfluoroalkyl substances in drinking water sources by DGT sampler with a novel fluorinated graphite binding gel - Fan Dong; Fan Ge; Xinting Zhao; Daming Sun; Suyu Ren; Yan Wang; Feng Tan (Science of The Total Environment, 2024)

Application of carboxymethyl cellulose sodium (CMCNa) in maize–wheat cropping system (MWCS) in coastal saline-alkali soil - Ge Li; Yuyang Shan; Weibo Nie; Yan Sun; Lijun Su; Weiyi Mu; Zhi Qu; Ting Yang; Quanjiu Wang (Science of The Total Environment, 2024)

Comparison of three digestion methods for microplastic extraction from aquaculture feeds - Anqi Ge; Shasha Zhao; Cuizhu Sun; Zixi Yuan; Liuqingqing Liu; Lingyun Chen; Fengmin Li (Science of The Total Environment, 2024)

Effects of ultrasound-assisted cooking on the physicochemical properties and microstructure of pork meatballs - Xinxin Zhao; Xiankun Sun; Bangcheng Lai; Rui Liu; Mangang Wu; Qingfeng Ge; Hai Yu (Meat Science, 2024)

Simulated microgravity altered the gene expression profiles and inhibited the proliferation of Kupffer cells in the early phase by downregulating LMO2 and EZH2 - Jun Ge; Yuan Yue; Hong-Yun Nie; Kai-Ge Liu; Hao Li; Hai-Guan Lin; Tao Zhang; Hong-Feng Yan; Hong-Wei Sun; Jian-Wu Yang; Jin-Lian Zhou; Yan Cui (Life Sciences in Space Research, 2024)

Upcycling MSWI fly ash into green binders via flue gas-enhanced wet carbonation - Miao Lu; Weizhe Ge; Yan Xia; Chen Sun; Xiaoqing Lin; Daniel C.W. Tsang; Tung-Chai Ling; Yanjun Hu; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

Experimental and numerical research on the failure pattern and mechanisms of granite disc with a pre-crack after heating and liquid nitrogen cooling - Yuliang Zhang; Guowei Ma; Qiang Sun; Zhenlong Ge; Xindong Wei; Zhe Li; Fuxin Rui (International Journal of Rock Mechanics and Mining Sciences, 2024)

Optically stimulated luminescence dating of Paleolithic sites reveals population shifts in North China during the last glacial period - Junyi Ge; Xiao Sun; Yan Li; Chunxue Wang; Lishuang Sheng; Ke Hu; Jiequn Hua; Xiaoling Zhang; Faxiang Huan; Shixia Yang; John W. Olsen; Xing Gao; et al. (Global and Planetary Change, 2024)

Selective hydrogenation of furfural to tetrahydrofurfuryl alcohol in isopropanol over hydrotalcite-derived nickel-based catalyst - Zheng Li; Huiru Yang; Shanshan Feng; Qianxin Sun; Ge Gao; Zhicheng Jiang; Changwei Hu (Chemical Engineering Journal, 2024)

Mxene-based wearable self-powered and photothermal triboelectric nanogenerator patches for wound healing acceleration and tactile sensing - Meiru Mao; Jianglong Kong; Xiaohan Ge; Yuting Sun; Hongrui Yu; Jiawen Liu; Weimin Huang; David Y. Wang; Yi Wang (Chemical Engineering Journal, 2024)

The role of oxygen vacancy in CaO-Ca12Al14O33 materials derived from hydrocalumite for enhanced CO2 capture cyclic performance - Zheng Yuyuan; Ge Zhiwei; Sun Haocheng; Wang Liang; Zhang Shuang; Lin Xipeng; Chen Qicheng; Chen Haisheng (Chemical Engineering Journal, 2024)

Interactions between soil bacterial communities, assembly processes and microbial functions along the elevational gradient - Donghui Zhao; Congcong Shen; Zhi-Ming Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (CATENA, 2024)

Non-exhaust gas and particle emissions of light-duty vehicles – Quantification under driving conditions in a sealed cabin - Jiachen Li; Yunshan Ge; Xin Wang; Mengzhu Zhang; Zhengjun Yang; Chongzhi Zhong; Jiaxing Sun; Yachao Wang (Atmospheric Environment, 2024)

Stay in touch with the endoplasmic reticulum - Sha Sun; Gan Zhao; Mingkang Jia; Qing Jiang; Shulin Li; Haibin Wang; Wenjing Li; Yunyun Wang; Xin Bian; Yan G. Zhao; Xun Huang; Ge Yang; et al. (Science China Life Sciences, 2024)

Along-track Calibration of the Zhurong Rover Magnetometer - Hao Luo; Aimin Du; Yasong Ge; Ying Zhang; Haiying Li; Lin Tian; Kuixiang Zhang; Shuquan Sun; Lin Zhao; Zhi Li; Xiao Feng (Science China Earth Sciences, 2024)

IGF2BP1 facilitates non-small cell lung cancer progression by regulating the KIF2A-mediated Wnt/β-catenin pathway - Ming Sun; Ling Wang; Lei Ge; Daojun Xu; Renquan Zhang (Functional & Integrative Genomics, 2024)

Epidermal growth factor: Expression in goat endometrial epithelia during early pregnancy and regulation by interferon tau and FOXO1 - Bo Wang; Meng-Die Li; Hai-Yue Xu; Xin-Cheng Zhang; Li-Ge Bu; Ting-Yue Li; Ya Sun; Hua Ni (Animal Reproduction Science, 2024)

Benchmark of plant-based VOCs control effect for indoor air quality: Green wall case in smith campus at Harvard University - Xiwei Shen; Qingqing Sun; Grant Mosey; Junhong Ma; Ling Wang; Mengting Ge (Science of The Total Environment, 2024)

Efficient extraction of platinum(IV) using tertiary-amine groups functionalized thiacalix[4]arene as extractant - Tao Ge; Xiaowei Zhou; Liang Xu; Yan Sun; Cheng Yang; Yongpan Tian; Zhuo Zhao (Minerals Engineering, 2024)

Cooling and anti-friction effects of vortex tube cryogenic minimum quantity lubrication in milling of 3D printed iron-nickel alloy - Chengdong Wang; Yang Ge; Cheng Wang; Kedong Zhang; Chengfeng Sun; Junli Li (Journal of Cleaner Production, 2024)

A wearable self-powered microneedle system based on conductive drugs for infected wound healing: A new electrical stimulation delivery strategy - Shanguo Zhang; Tianyi Jiang; Fang Han; Liangyu Cao; Ming Li; Zhenyou Ge; Haoxiu Sun; Hao Wu; Wenlong Wu; Nannan Zhou; Muhammad Luqman Akhtar; Hongyuan Jiang (Chemical Engineering Journal, 2024)

Electrochemical advanced oxidation processes towards carbon neutral wastewater treatment: A review - Wenjing Li; Ge Song; Jiangli Sun; Minghua Zhou (Chemical Engineering Journal, 2024)

Interfacial synergy between Pt3Co nanoparticles and CoO for efficient ammonia borane hydrolysis - Ruichao Xu; Hongmei Li; LiuXin Xu; Ya Pan; Min Ge; Chao Wang; Zhihu Sun (Chemical Engineering Journal, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Health risk assessment of trace metal(loid)s in agricultural soils based on Monte Carlo simulation coupled with positive matrix factorization model in Chongqing, southwest China - Jie Ma; Lijuan Chu; Jing Sun; Shenglan Wang; Miao Ge; Li Deng (Journal of Mountain Science, 2024)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Association between combined exposure to dioxins and arthritis among US adults: a cross-sectional study - Qi Meng; Yi Wang; Tao Yuan; Yang Su; Jianxun Ge; Shankun Dong; Shui Sun (Environmental Science and Pollution Research, 2023)

Griseofulvin enantiomers and bromine-containing griseofulvin derivatives with antifungal activity produced by the mangrove endophytic fungus Nigrospora sp. QQYB1 - Ge Zou; Wencong Yang; Tao Chen; Zhaoming Liu; Yan Chen; Taobo Li; Gulab Said; Bing Sun; Bo Wang; Zhigang She (Marine Life Science & Technology, 2023)

Explaining nitrogen turnover in sediments and water through variations in microbial community composition and potential function - Shan Yang; Meijun Dong; Huibin Lu; Zhipeng Cai; Meng Ge; Jia Xing; Haobin Huang; Youda Huang; Guoping Sun; Shaofeng Zhou; Meiying Xu (Chemosphere, 2023)

Luteolin inhibits angiogenesis and enhances radiotherapy sensitivity of laryngeal cancer via downregulating Integrin β1 - Zhen Li; Hongzhou Ge; Yonggang Xie; Yueqin Zhang; Xiaoyan Zhao; Wen Sun; Meiyan Song (Tissue and Cell, 2023)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

RETRACTED: High-efficiency and low-carbon inactivation of UV resistant bacteria in reclaimed water by flow-through electrode system (FES) - Yi-Ge Sun; Hao-Bin Wang; Yin-Hu Wu; Ke-Fan Cao; Zhuo Chen; Nozomu Ikuno; Nakata Koji; Hong-Ying Hu (Science of The Total Environment, 2023)

Development of alantolactone-loaded zein and shellac nanoparticles for controlled release in simulated gastrointestinal digestion - Hongrui Yu; Xiaohan Ge; Jianglong Kong; Yuting Sun; Meiru Mao; Jiawen Liu; Jiaxing Ye; Amit Arora; Inthawoot Suppavorasatit; Yi Wang (Journal of Food Engineering, 2023)

pH-Responsive graphene oxide/poly (methacrylic acid) hybrid nanofiltration membrane performance for water treatment - Li-yue Sun; De-hao Yu; Zhao-ge Juan; Yao Wang; Yan-xin Wang; Matt J. Kipper; Lin-jun Huang; Jian-guo Tang (Journal of Environmental Chemical Engineering, 2023)

Recognizing iso-olefins as paramount intermediates for optimum isoparaffins production via CO hydrogenation - Haochen Qi; Cederick Cyril Amoo; Wuqiang Si; Jian Lou; Xuangan Liu; Chunyang Zeng; Qingjie Ge; Jian Sun; Chuang Xing; Xinhua Gao (Fuel, 2023)

The trait co-variation regulates the response of bryophytes to nitrogen deposition: A meta-analysis - Xu Sheng; Cai Qiying; Sun Shifeng; Liu Yizhen; Guan Bicai; Wu Lan; Ge Gang (Environmental Pollution, 2023)

Corrigendum to ‘Silica nanoparticles inhibiting the differentiation of round spermatid and chromatin remodeling of haploid period via MIWI in mice’[ Environ. Pollut. 284 (2021) 117446] - Jianhui Liu; Xiangyang Li; Guiqing Zhou; Yue Zhang; Yujian Sang; Ji Wang; Yanbo Li; Wei Ge; Zhiwei Sun; Xianqing Zhou (Environmental Pollution, 2023)

Highly sensitive miRNA detection of early-stage laryngeal carcinoma using a solid-state Au nanocone arrays fabricated LoC-SERS analysis system coupled with target-triggered dual cycle amplification strategy - Guang Li; Xinyu Zhou; Shengjie Ge; Xiaotao Bao; Xiaoyan Liu; Aidong Sun (Chemical Engineering Journal, 2023)

Comparative transcriptome analysis of eyes reveals the adaptive mechanism of mantis shrimp (oratosquilla oratoria) induced by a dark environment - Xiaoli Sun; Ling He; Bujin Ayi; Yuyang Qiu; Jiayue Xu; Wei Yu; Tinghao Yan; Ge Ding; Boping Tang; Gang Wang; Daizhen Zhang (Genetica, 2023)

Spatial distribution and risk assessment of polycyclic aromatic hydrocarbons in soils from contaminated sites in Eastern China - Xinhui Sun; Qi Zhao; Xuelin Li; Qiuyue Zhang; Meng Gao; Zhanpeng Ge; Yu Wang; Hongwen Sun (Environmental Geochemistry and Health, 2023)

Soil legacy nutrients contribute to the decreasing stoichiometric ratio of N and P loading from the Mississippi River Basin - Zihao Bian; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; Christopher Anderson; Wei‐Jun Cai; Charles S. Hopkinson; Dubravko Justic; Latif Kalin; Steven Lohrenz; Steven McNulty; et al. (Global Change Biology, 2023)
Human‐induced nitrogen–phosphorus (N, P) imbalance in terrestrial ecosystems can lead to disproportionate N and P loading to aquatic ecosystems, subsequently shifting the elemental ratio in estuaries and coastal oceans and impacting both the structure and functioning of aquatic ecosystems. The N:P ratio of nutrient loading to the Gulf of Mexico from the Mississippi River Basin increased before the late 1980s driven by the enhanced usage of N fertilizer over P fertilizer, whereafter the N:P loading ratio started to decrease although the N:P ratio of fertilizer application did not exhibit a similar trend. Here, we hypothesize that different release rates of soil legacy nutrients might contribute to the decreasing N:P loading ratio. Our study used a data‐model integration framework to evaluate N and P dynamics and the potential for long‐term accumulation or release of internal soil nutrient legacy stores to alter the ratio of N and P transported down the rivers. We show that the longer residence time of P in terrestrial ecosystems results in a much slower release of P to coastal oceans than N. If contemporary nutrient sources were reduced or suspended, P loading sustained by soil legacy P would decrease much slower than that of N, causing a decrease in the N and P loading ratio. The longer residence time of P in terrestrial ecosystems and the increasingly important role of soil legacy nutrients as a loading source may explain the decreasing N:P loading ratio in the Mississippi River Basin. Our study underscores a promising prospect for N loading control and the urgency to integrate soil P legacy into sustainable nutrient management strategies for aquatic ecosystem health and water security.

PuNAC100-like/PubHLH61 co-regulate PuLOX3 mediating ester biosynthesis in cold-stored ‘Nanguo’ pears - Manli Luo; Huajun Sun; Wanying Ge; Xin Zhou; Qian Zhou; Shujuan Ji (Postharvest Biology and Technology, 2023)

Ship energy-saving device: Influence of the scale effect and hull roughness on the resistance reduction effect of an interceptor - Kewei Song; Jie Gong; Shenwei Ge; Cong Sun; Haiyan Yang; Weiping Zhang (Ocean Engineering, 2023)

In vitro starch digestibility of maize flour and maize extruded noodles based on different particle-size effects - Rui Ge; Xiaojie Qian; Binghua Sun; Sen Ma; Xiaoxi Wang (Journal of Cereal Science, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

Efficient singlet oxygen nanogenerator with low-spin iron for selective contaminant decontamination - Jingjing Jiang; Shu Niu; Shengda Liu; Hao Zhang; Yansong Liu; Tongze Sun; Donglong Shi; Bowen Zhao; Ge Yan; Mingxin Huo; Dandan Zhou; Shuangshi Dong (Chemical Engineering Journal, 2023)

Quorum sensing in different subcommunities becomes the key factor affecting the humification of the aerobic composting system with sauerkraut fermentation wastewater - Jiaxin Liu; Song Gang; Xu Wang; Shanshan Sun; Jie Kang; Jingping Ge (Bioresource Technology, 2023)

Structural plane recognition from three-dimensional laser scanning points using an improved region-growing algorithm based on the robust randomized Hough transform - Zhi-hua Xu; Ge Guo; Qian-cheng Sun; Quan Wang; Guo-dong Zhang; Run-qing Ye (Journal of Mountain Science, 2023)

An approach for multi-objective optimization based on preliminary PSA and its applications for fusion reactors - Ming Sun; Jie Yu; Taosheng Li; Daochuan Ge (Annals of Nuclear Energy, 2023)

A Precursory Signal of June–July Precipitation over the Yangtze River Basin: December–January Tropospheric Temperature over the Tibetan Plateau - Xiaying Zhu; Mingzhu Yang; Ge Liu; Yanju Liu; Weijing Li; Sulan Nan; Linhai Sun (Advances in Atmospheric Sciences, 2023)

Protective effects of maternal administration of total saponins of Codonopsis pilosula in the mice offspring following diarrhea: role of immune function, antioxidant function, and intestinal inflammatory injury - Jiali Li; Yiming Sun; Naixi Yang; Haolin Zhang; Yihan Hu; Haibin Wang; Ruili Zhang; Ming Ge (Environmental Science and Pollution Research, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Chicken dendritic cell-targeting nanobodies mediated improved protective effects against H9N2 influenza virus challenge in a homologous sequential immunization study - Futing Jia; Chao Sun; Chongbo Ge; Zhannan Wang; Tongyu Zhang; Menglei Zhang; Wenfeng Wang; Yawen Tian; Yingkai He; Guilian Yang; Wentao Yang; Chunwei Shi; et al. (Veterinary Microbiology, 2023)

Novel and legacy brominated flame retardants in snakes and frogs: Tissue distribution, biomagnification, and maternal transfer - Guanzhen Sun; Xinyu Du; Yan Wu; Ge Yin; Luting Chen; Xiaojun Liu; Yihui Zhou; Yanling Qiu; Tian Lin (Science of The Total Environment, 2023)

Identifying driving hydrogeomorphic factors of coastal wetland downgrading using random forest classification models - Keqi He; Wenhong Li; Yu Zhang; Ge Sun; Steve G. McNulty; Neal E. Flanagan; Curtis J. Richardson (Science of The Total Environment, 2023)

Design and analysis of wire-driven tail fin for bionic underwater glider - Liming Ge; Wenda Ma; Shaoqiong Yang; Xiao Yu; Tongshuai Sun; Xuan Wang; Shuai Fa; Yanhui Wang (Ocean Engineering, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Suitable crop loading: An effective method to improve “Shine Muscat” grape quality - Jianing Li; Tingting Ma; Shihan Bao; Dingze Yin; Qian Ge; Caihong Li; Yulin Fang; Xiangyu Sun (Food Chemistry, 2023)

A point-of-care detection platform for Escherichia coli O157:H7 by integration of smartphone and the structural colour of photonic microsphere - Xiaomeng Liu; Wei Li; Jialong Sun; Shijie Dai; Xiu Wang; Jing Yang; Qianjin Li; Yao Li; Hongyu Ge; Jianning Zhao; Jianlin Li (Food Chemistry, 2023)

Corrigendum to “Decabromodiphenyl ether-induced PRKACA hypermethylation contributed to glycolipid metabolism disorder via regulating PKA/AMPK pathway in rat and L-02 cells” [Environ. Toxicol. Pharmacol., 2022, 90, 103808] - Yupeng Zhu; Li Jing; Xiangyang Li; Guiqing Zhou; Yue Zhang; Yujian Sang; Leqiang Gao; Sitong Liu; Zhixiong Shi; Zhiwei Sun; Wei Ge; Xianqing Zhou (Environmental Toxicology and Pharmacology, 2023)

High-performance Janus evaporator based on self-healing hydrogels for salt-rejecting interfacial solar desalination - Jiehui Li; Jinmei He; Jianwei Ge; Ruizhe Zhang; Yali Yao; Xuedan Zhu; Caili Sun; Mengnan Qu (Desalination, 2023)

Bio-inspired robust and highly thermal conductive BNNS/PBO nanofiber composite films with excellent thermal stability, wear resistance, and adjustable photothermal properties - Tingting Sun; Wenxin Cao; Kechen Zhao; Xiaolei Wang; Zhuochao Wang; Ge Gao; Zhijie Ye; Kunlong Zhao; Zhenhua Su; Bing Dai; Mingfu Zhang; Jiecai Han; et al. (Chemical Engineering Journal, 2023)

A dual receptor targeting and blood–brain barrier penetrating co-drug-loaded particle mediating inhibition of oxidative phosphorylation for targeted therapy of glioblastoma - Yuting Sun; Jianglong Kong; Xiaohan Ge; Meiru Mao; Hongrui Yu; Jiawen Liu; Yi Wang (Chemical Engineering Journal, 2023)

Beijing Children’s Hospital guidelines on the design and conduction of the first standardized database for medulloblastoma - Wei Yang; Wenping Ma; Jiansong Huang; Yingjie Cai; Xiaojiao Peng; Fengmao Zhao; Di Zhang; Zhewei Zou; Hailang Sun; Xiang Qi; Ming Ge (Metabolic Brain Disease, 2023)

Evidence for RA-dependent meiosis onset in a turtle embryo - Kaiyue Wu; Qiran Chen; Fang Li; Jiadong Shen; Wei Sun; Chutian Ge (Cell and Tissue Research, 2023)

Cascade signal amplification strategy by coupling chemical redox-cycling and Fenton-like reaction: Toward an ultrasensitive split-type fluorescent immunoassay - Lin-Ge Chen; Lu Sun; Ning-Ning Wu; Bei-Bei Tao; Hai-Bo Wang (Analytica Chimica Acta, 2023)

Precise tumor delineation in clinical tissues using a novel acidic tumor microenvironment activatable near-infrared fluorescent contrast agent - Chang-Chun Ling; Tiantian Sun; Fang Chen; Hongmei Wu; Weizhi Tao; Xudong Xie; Dongliang Ji; Ge Gao; Jun Chen; Yong Ling; Yanan Zhang (Analytica Chimica Acta, 2023)

The heterogeneity of microbial diversity and its drivers in two types of sediments from tidal flats in Beibu Gulf, China - Yong-Lian Ye; Kuo-Jian Ma; Yun-Han Fu; Zhi-Cheng Wu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Mudflats and sandflats are two common types of coastal tidal flats, the structure and function differences of microbial communities between them are still underappreciated. Beibu Gulf is a diurnal tidal regime located in China, the differences between the two type of tidal flats could be more distinct. In this study, we collected a total of 6 samples from Beibu Gulf, consisting of 3 sandflats samples and 3 mudflats samples, classified based on clay and silt content. Generally, the mudflats samples exhibited higher levels of NH 4 + _N and TOC, but lower in ORP and pH. The microbial diversity of the two types of tidal flats was investigated, revealing great differences existed and sandflats had higher microbial richness and diversity than mudflats. Furthermore, we analyzed the association between microbial communities and environmental factors, finding NH 4 + _N to have the highest contribution to the total variation in microbial community structure, and microbial groups such as Desulfobacterota, Campilobacterota, Chloroflexota, Calditrichota, Spirochaetota, Zixibacteria, Latescibacterota and Sva0485 group in mudflats were positively associated with NH 4 + _N. The functions of microbial community were predicted using metagenomic sequences and metagenome assembled genome (MAG). Mudflats contained more genes for carbon fixation. Nitrate and nitrite reduction were widely existed in mudflats and sandflats, but nitrogen fixation was only existed in mudflats, and Campilobacterota , Desulfobacterota and Gammaproteobacteria MAGs were mainly responsible for it. Sandflats composed more genes for ammonium oxidation, but no MAG was found whether in sandflats or mudflats. Microbes in mudflats exhibited a greater abundance of genes related to sulfur cycling, especially in reduction process, unique MAGs in mudflats such as Calditrichota, Chloroflexota, Desulfobacterota and Zixibacteria MAGs are responsible for sulfate and sulfite reduction. Finally, we predicted functions of ammonium related microbes in mudflats based on MAGs and found Campilobacterota and Desulfobacterota MAGs were important for high accumulation of ammonium in mudflats. This study illuminated the structural and functional differences of microbial communities in mudflats and sandflats, providing new insights into the relationship of microbial communities and environment in the tidal flat.

Aminotransferase Class I and II Gene Family in the Jinjiang Oyster (Crassostrea ariakensis): Genomewide Identification, Phylogenetic Analysis and Expression Profiles after Salinity Stress - Guangyu Ge; Zhihong Liu; Tao Yu; Liqing Zhou; Xiujun Sun; Zhuanzhuan Li; Yanxin Zheng (Fishes, 2023)
Aminotransferases are enzymes found in living organisms that catalyze transfer reactions between amino acids and keto acids, crucial for amino acid metabolism and synthesis. Aminotransferase classes I and II play a vital role in regulating osmolarity, protecting cells, and improving metabolic homeostasis and cellular fitness. To investigate the characteristics of the aminotransferase class I and II gene family and their roles in osmotic pressure regulation in the Jinjiang oyster (Crassostrea ariakensis), the gene structure, chromosomal localization, and phylogeny were characterized and the genes’ expression in the gill under high-salt stress was analyzed. In this study, eighteen Aminotransferase class I and II genes, including SPTLCa and SPTLCb, SPTa and SPTb, ALAT2a and ALAT2b, KAT3a and KAT3b, and ASTa, ASTb and ASTc, were identified. The physicochemical properties of 11 family members were stable, with their instability factors less than 40. Subcellular localization prediction showed that aminotransferase classes I and II were localized in the cytoplasm or mitochondria. Chromosomal localization results showed that the 18 aminotransferase class I and II genes were located on eight chromosomes. All members of this gene family had the Aminotran_1_2 structural domain which is associated with osmotic pressure regulation by adjusting the conversion reaction between amino acids and keto acids. Most gene expressions showed an initial increase followed by a decrease from 0 h to 12 h when the oysters were challenged by acute stress using artificial seawater with a salinity of 40. However, the expression of CarAGT2 and CarKAT3b genes showed an increased trend with increasing stress time. This study systematically investigated the bioinformatics characteristics of the aminotransferase class I and II gene family in C. ariakensis and their role in osmotic pressure regulation, which provides scientific data for understanding the potential functions of these genes in physiological adaptation, thereby expanding the research on osmoregulation in bivalves.

Efficacy of transplant insecticides against black cutworm Agrotis ipsilon (Lepidoptera: Noctuidae) in tobacco - Pingping Liu; Jingxin Zhang; Huifang Shen; Qiyun Yang; Xiaoming Pu; Dayuan Sun; Baiyi Ge; Birun Lin (Crop Protection, 2023)

Modeling and optimization of synergistic ozone-ultraviolet-chlorine process for reclaimed water disinfection: From laboratory tests to software simulation - Ke-Fan Cao; Zhuo Chen; Yi-Ge Sun; Bang-Hao Huang; Qi Shi; Yu Mao; Yin-Hu Wu; Yun Lu; Hong-Ying Hu (Water Research, 2023)

Structural and species diversity explain aboveground carbon storage in forests across the United States: Evidence from GEDI and forest inventory data - Erin T.H. Crockett; Jeff W. Atkins; Qinfeng Guo; Ge Sun; Kevin M. Potter; Scott Ollinger; Carlos A. Silva; Hao Tang; Christopher W. Woodall; Justin Holgerson; Jingfeng Xiao (Remote Sensing of Environment, 2023)

Melatonin induces resistance against Penicillium expansum in apple fruit through enhancing phenylpropanoid metabolism - Miao Wang; Yihan Li; Canying Li; Hengping Xu; Tong Sun; Yonghong Ge (Physiological and Molecular Plant Pathology, 2023)

Tecono-stratigraphy of Paleogene Zhu-3 depression of the Pearl River Mouth Basin, South China Sea: Implications for syn-rift architecture in multiphase rifts - Jiawang Ge; Yanlei Dong; Mingxuan Tan; Hehe Chen; Lianpu Sun; Shunli Li; Xiaoming Zhao (Marine and Petroleum Geology, 2023)

Practical application for legacy acid mine drainage (AMD) prevention and treatment technologies in karst-dominated regions: A case study - Xin Li; Hujun Ren; Zhimin Xu; Ge Chen; Shangguo Zhang; Li Zhang; Yajun Sun (Journal of Contaminant Hydrology, 2023)

Response of stream macroinvertebrate communities to forest harvesting in the Piedmont region of North Carolina - Zanethia C. Barnett; Johnny Boggs; Ge Sun (Forest Ecology and Management, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Exploiting the latency of carbon as catalyst in CO2 hydrogenation - Cederick Cyril Amoo; Joshua Iseoluwa Orege; Qingjie Ge; Jian Sun (Chemical Engineering Journal, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Piezo2 Channel Upregulation is Involved in Mechanical Allodynia in CYP-Induced Cystitis Rats - Lei Liu; Yan Zhao; Wenhan An; Mengmeng Zhao; Ning Ding; Hanwen Liu; Nan Ge; Jiliang Wen; Xiulin Zhang; Shulu Zu; Wendong Sun (Molecular Neurobiology, 2023)
Mechanical sensing Piezo2 channel in primary sensory neurons has been shown contribute to mechanical allodynia in somatic chronic pain conditions. Interstitial cystitis (IC)-associated pain is often triggered by bladder filling, a presentation that mimics the mechanical allodynia. In the present study, we aimed to examine the involvement of sensory Piezo2 channel in IC-associated mechanical allodynia using a commonly employed cyclophosphamide (CYP)-induced IC model rat. Piezo2 channels in dorsal root ganglia (DRGs) was knocked down by intrathecal injections of Piezo2 anti-sense oligodeoxynucleotides (ODNs) in CYP-induced cystitis rats, and mechanical stimulation–evoked referred bladder pain was measured in the lower abdomen overlying the bladder using von Frey filaments. Piezo2 expression at the mRNA, protein, and functional levels in DRG neurons innervating the bladder was detected by RNA-fluorescence in situ hybridization, western blotting, immunofluorescence, and Ca 2+ imaging, respectively. We found that Piezo2 channels were expressed on most (> 90%) of the bladder primary afferents, including afferents that express CGRP, TRPV1 and stained with isolectin B4. CYP-induced cystitis was associated with Piezo2 upregulation in bladder afferent neurons at the mRNA, protein, and functional levels. Knockdown of Piezo2 expression in DRG neurons significantly suppressed mechanical stimulation–evoked referred bladder pain as well as bladder hyperactivity in CYP rats compared to CYP rats treated with mismatched ODNs. Our results suggest upregulation of Piezo2 channels is involved in the development of bladder mechanical allodynia and bladder hyperactivity in CYP-induced cystitis. Targeting Piezo2 might be an attractive therapeutic approach for IC-related bladder pain.

Assessment of Joint Toxicity of Arsenate and Lead by Multiple Endpoints in Chlamydomonas reinhardtii - Danqing Sun; Zhongquan Jiang; Hangqi Yu; Zhen Li; Chunhua Zhang; Ying Ge (Bulletin of Environmental Contamination and Toxicology, 2023)

Multi-year nitrogen accumulation weakens the stabilizing effect of species asynchrony on drought resistance in a Tibetan alpine meadow - Ge Hou; Tiancai Zhou; Peili Shi; Jian Sun; Ning Zong; Jialuo Yu; Minghua Song (Agricultural and Forest Meteorology, 2023)

Long-term groundwater geochemical evolution induced by coal mining activities—a case study of floor confined limestone aquifer in Yaoqiao Coal Mine, Jiangsu, China - Ge Chen; Yajun Sun; Zhimin Xu; Huiqing Yuan; Haizhe Yi (Environmental Science and Pollution Research, 2023)

In-situ pyrolysis kinetic analysis and fixed-bed pyrolysis behavior of ex-service wind turbine blades - Yuqing Wu; Zefeng Ge; Chen Huang; Zhenting Zha; Mingxun Zeng; Yuna Ma; Lijuan Sun; Zenghui Hou; Sheng Chu; Huiyan Zhang (Waste Management, 2023)

Liquid metal microspheres with an eddy-thermal effect for magnetic hyperthermia-enhanced cancer embolization-immunotherapy - Nailin Yang; Xingwei Sun; Yangkai Zhou; Xiaoyuan Yang; Jiaxi You; Zepeng Yu; Jun Ge; Fei Gong; Zhisheng Xiao; Yong Jin; Zhuang Liu; Liang Cheng (Science Bulletin, 2023)

Designing low-carbon cement-free binders for stabilization/solidification of MSWI fly ash - Chen Sun; Weizhe Ge; Yuying Zhang; Lei Wang; Yan Xia; Xiaoqing Lin; Qunxing Huang; Shengyong Lu; Daniel C.W. Tsang; Jianhua Yan (Journal of Environmental Management, 2023)

Oxidative acid leaching of indium phosphide waste and recovery of indium metal by cementation with aluminum - Xiaofeng Zhang; Tao Ge; Liang Xu; Yan Sun; Cheng Yang; Yonglin Yao; Yongpan Tian; Zhuo Zhao (Hydrometallurgy, 2023)

Eating with peel or not: Investigation of the peel consumption situation and its nutrition, risk analysis, and dietary advice in China - Qinyu Zhao; Qian Ge; Yi Shang; Mingyuan Zheng; Xiangyu Sun; Shihan Bao; Yulin Fang; Zhenwen Zhang; Tingting Ma (Food Research International, 2023)

Molecularly imprinted polymers based on calcined rape pollen and deep eutectic solvents for efficient sinapic acid extraction from rapeseed meal extract - Yanhua Sun; Yange Zhang; Yujiao Hou; Hui Gong; Yifei Pang; Xiaoxiao Ge; Ming Li (Food Chemistry, 2023)

Dysfunction of the intestinal physical barrier in the intestinal inflammation of tongue sole, Cynoglossus semilaevis, induced by Shewanella algae infection - Zhuoran Han; Lunhua Ge; Siyi Wen; Jingfeng Sun (Fish & Shellfish Immunology, 2023)

Uranium uptake is mediated markedly by clathrin-mediated endocytosis and induce dose-dependent toxicity in HK-2 cells - Liqun Huang; Ge Sun; Wenli Xu; Shufang Li; Xiujun Qin; Quan An; Zhongwen Wang; Jianguo Li (Environmental Toxicology and Pharmacology, 2023)

Fabrication of submicron linewidth silver grid/ionogel hybrid films for highly stable flexible transparent electrodes via asymmetric wettability template-assisted self-assembly - Zhixin Wang; Xiaohan Sun; Zilong Guo; Rubing Xi; Lingyun Xu; Zhihao Zhao; Yinghao Ge; Ziquan Cao; Xiangyu Jiang; Wensheng Yang; Lei Jiang (Chemical Engineering Journal, 2023)

Response characteristics of flax retting liquid addition during chicken manure composting: Focusing on core bacteria in organic carbon mineralization and humification - Yangcun Sun; Shanshan Sun; Fangyi Pei; Chi Zhang; Xinbo Cao; Jie Kang; Zhenchao Wu; Hongzhi Ling; Jingping Ge (Bioresource Technology, 2023)

Role of Bmal1 in Type 2 Diabetes Mellitus-Related Glycolipid Metabolic Disorder and Neuropsychiatric Injury: Involved in the Regulation of Synaptic Plasticity and Circadian Rhythms - Xinran Gao; Yadong Wei; Huaizhi Sun; Shengwei Hao; Mengdie Ma; Huimin Sun; Dandan Zang; Congcong Qi; Jinfang Ge (Molecular Neurobiology, 2023)

Role of TPEN in Amyloid-β25–35-Induced Neuronal Damage Correlating with Recovery of Intracellular Zn2+ and Intracellular Ca2+ Overloading - Wen-bo Chen; Yu-xiang Wang; Hong-gang Wang; Di An; Dan Sun; Pan Li; Tao Zhang; Wan-ge Lu; Yan-qiang Liu (Molecular Neurobiology, 2023)

Large discrepancies among remote sensing indices for characterizing vegetation growth dynamics in Nepal - Decheng Zhou; Liangxia Zhang; Lu Hao; Ge Sun; Jingfeng Xiao; Xing Li (Agricultural and Forest Meteorology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Genomic and phylotypic properties of three novel marine Bacteroidota from bare tidal flats reveal insights into their potential of polysaccharide metabolism - Kuo-Jian Ma; Yong-Lian Ye; Yun-Han Fu; Ge-Yi Fu; Cong Sun; Xue-Wei Xu (Frontiers in Marine Science, 2023)
Special geographical location and abundant organic matter profiles in tidal flats have resulted in great microbial diversity, in which Bacteroidota strains are considered as one of the primary degraders of polysaccharides, playing a crucial role in the carbon cycle. In this study, we collected sediment or sand samples from 34 bare tidal flats in China and investigated the profile of culturable bacteria, selected three Bacteroidota for polyphasic taxonomic analysis and revealed their polysaccharide metabolic potential. Totally, we isolated 352 pure cultured bacteria and they mainly distributed in Bacteroidota , Pseudomonadota , Bacillota , and Actinomycetota . It is shown that the bare tidal flats contained a large number of potential novel species, mainly distributed in Flavobacteriales and Cytophagales within Bacteroidota . Three Bacteroidota strains, M17 T , M82 T , and M415 T , isolated from mudflat were selected for polyphasic taxonomic analysis. The 16S rRNA gene sequence similarity between strain M17 T and Mangrovivirga cuniculi KCTC 72349 T was 99.28%, and less than 90.09% with other species; strain M82 T shared the highest 16S rRNA gene sequence similarity of 97.85% with Pontibacter litorisediminis KCTC 52252 T , and less than 97.43% with other species; strain M415T had higher 16S rRNA gene sequence similarities with type species of genera Eudoraea (92.62-93.68%), Zeaxanthinibacter (92.02-92.91%), and Muriicola (92.21-92.83%). Phylogenetic analysis based on 16S rRNA gene sequences and single-copy orthologous clusters showed that strains M17 T and M82 T represent novel species within the genus Mangrovivirga and Pontibacter , respectively, and strain M415 T represents a novel species of a novel genus within the family Flavobacteriaceae . The potential in polysaccharide metabolism of all these three strains was analyzed by genomes. The analysis revealed that glycoside hydrolases and glycosyltransferases account for more than 70% of the total CAZymes. Additionally, the numbers of polysaccharide utilization loci (PULs) and annotated CAZymes in Cytophagales spp. M17 T and M82 T were found to be higher than those in Flavobacteriales sp. M415 T . Highly specialized saccharolytic systems and the presence of numerous diversified CAZymes for obtaining energy through polysaccharide metabolism were speculated to help the three novel strains adapt to the utilization of both terrestrial and marine polysaccharides.

Anti-ricin toxin human neutralizing antibodies and DMAbs protection against ricin toxin poisoning - Haotian Yu; Meng Wu; Na Zhao; Mingxin Dong; Yan Wang; Kaikai Yu; Chengbiao Sun; Na Xu; Liangpeng Ge; Wensen Liu (Toxicology Letters, 2023)

A stabilizing benders decomposition method for the accessibility-oriented charging station location problem - Maocan Song; Lin Cheng; Huimin Ge; Yan Li; Chao Sun (Sustainable Cities and Society, 2023)

Ambient temperature and major structural anomalies: A retrospective study of over 2 million newborns - Yangchang Zhang; Feng Sun; Kun Yuan; Ying Du; Lizhi Wu; Yang Ge; Zhenyu Zhang; Shengzhi Sun; Wangnan Cao (Science of The Total Environment, 2023)

Ecosystem sustainability of rice and aquatic animal co-culture systems and a synthesis of its underlying mechanisms - Lei Ge; Yu Sun; Yujie Li; Luyao Wang; Guanqing Guo; Lili Song; Cui Wang; Guogan Wu; Xiaoyun Zang; Xiaomei Cai; Shuangxi Li; Peng Li (Science of The Total Environment, 2023)

Distribution pattern of planktonic and benthic foraminifera in surface sediments near the equatorial western Indian Ocean and its indications of paleo-environment and productivity - Wei Shen; Shuqing Qiao; Rongtao Sun; Zhoutian He; Bin Wu; Lina Jin; Liang Chen; Zhengxin Yin; Chendong Ge; Xuefa Shi; Jie Sheng (Journal of Asian Earth Sciences, 2023)

Mechanistic insights into the supramolecular structure and physicochemical properties of twin-screw extruded high amylose corn starch with different amylose content by improved electron beam irradiation - Xiangzhen Ge; Hao Duan; Yaxi Zhou; Shiqi Zhou; Huishan Shen; Wei Liang; Zhuangzhuang Sun; Wenjie Yan (Innovative Food Science & Emerging Technologies, 2023)

Aroma correlation assisted volatilome coupled network analysis strategy to unveil main aroma-active volatiles of Rosa roxburghii - Ya-Hui Ge; Xue Li; Mingzheng Huang; Zhengxu Huang; Manman Wu; Baoqing Sun; Lishuang Wang; Jian-Lin Wu; Na Li (Food Research International, 2023)

Species-specific CgCaspase-Cg-5 in the pacific oyster induces haemocyte apoptosis by regulating the mRNA expression of apoptosis-related genes in the early stage of immune response - Lei Gao; Qingsong Li; Ziyang Zhang; Pingan Ge; Jiejie Sun; Xue Qiao; Lingling Wang; Linsheng Song (Fish & Shellfish Immunology, 2023)

Free-ranging livestock changes the acoustic properties of summer soundscapes in a Northeast Asian temperate forest - Yifei Sun; Shizheng Wang; Jiawei Feng; Jianping Ge; Tianming Wang (Biological Conservation, 2023)

Chemical looping reforming of toluene as bio-oil model compound via NiFe2O4@SBA-15 for hydrogen-rich syngas production - Ge Liu; Zhongshun Sun; Huirong Zhao; Xiangyang Mao; Bolun Yang; Jianxuan Shang; Zhiqiang Wu (Biomass and Bioenergy, 2023)

Microtremor-based analysis of the dynamic response characteristics of a site containing grouped earth fissures - Yahong Deng; You Xuan; Huandong Mu; Jiang Chang; Ge Cao; Nainan He; Xunchang Zhao; Longfei Sun (Earthquake Engineering and Engineering Vibration, 2023)

Dynamic response analysis of liquefiable ground due to sinusoidal waves of different frequencies of shield construction - Jingyue Wang; Xinsheng Ge; Jingyuan Sun; Yasheng Liu; Zhuo Shang; Zhiqiang Wang; Maoguo Tian (Earthquake Engineering and Engineering Vibration, 2023)

Compound and successive events of extreme precipitation and extreme runoff under heatwaves based on CMIP6 models - Peng Sun; Yifan Zou; Rui Yao; Zice Ma; Yaojin Bian; Chenhao Ge; Yinfeng Lv (Science of The Total Environment, 2023)

Quantified trend of photosynthetic rate along the depth of microalgae biofilm - Lin-Lan Zhuang; Wanqing Tian; Yanan Yang; Shuhan Ge; Peihua Li; Shuo Sun; Jian Zhang; Shuang Liang (Science of The Total Environment, 2023)

Relationship between Holocene lake water temperature and glacier meltwater on the northwestern Tibetan Plateau - Can-Ge Li; Mingda Wang; Zhe Sun; Mengmeng Cao; Juzhi Hou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Recycling of waste indium tin oxide target for In-Sn alloy production based on molten salt electrochemistry - Liang Xu; Tao Ge; Gaojie Chen; Yan Sun; Xiaofeng Zhang; Zhongsheng Hua; Yongpan Tian; Zhuo Zhao (Journal of Environmental Chemical Engineering, 2023)

Evaluation of a novel carbon-based micro-nano zero-valent iron composite for immobilization of heavy metals in soil - Song Guo; Huifen Yang; Qiwei Sun; Ge Zhang; Tong Zhao; Yichen Zhou; Xuan Li; Pu Gao (Journal of Environmental Chemical Engineering, 2023)

Heteroprotein complex between soy protein isolate and lysozyme: Protein conformation, lysozyme activity, and structural characterization - Jiabao Zheng; Chuan-he Tang; Jihong Wu; Ge Ge; Mouming Zhao; Weizheng Sun (Food Chemistry, 2023)

A study of long-term toxicity of multiple mixtures with hormetic effects by the characteristic parameter σ() and stepwise method - Na Wang; Jiajing Sun; Xiaoyan Ma; Xinyue Yang; Xiaochang Wang; Yujiao Zhang; Jinhong Zhou; Jiaxuan Wang; Chengmin Ge (Environmental Toxicology and Pharmacology, 2023)

A real-time hybrid testing based on shaking table and actuator for cable tray systems - Guoshan Xu; Lichang Zheng; Bin Wu; Zhen Wang; Guoliang Sun; Xuezhong Zhang; Dongjun Li; Ge Yang; Tao Wang (Engineering Structures, 2023)

Discovery of seven-membered ring berberine analogues as highly potent and specific hCES2A inhibitors - Yun Yang; Yuan Xiong; Guanghao Zhu; Mengru Sun; Kun Zou; Yitian Zhao; Yong Zhang; Zhijian Xu; Yiming Li; Weiliang Zhu; Qi Jia; Bo Li; et al. (Chemico-Biological Interactions, 2023)

Lysinibacillus capsici 38,328 isolated from agricultural soils as a promising probiotic candidate for intestinal health - Huinan Chen; Xiaoyi Sun; Huilin He; Hongkun Ren; Haoyuan Duan; Chuankun Zhang; Qingru Chang; Runxiang Zhang; Junwei Ge (Archives of Microbiology, 2023)

Parameters of dynamic compaction based on model test - Peixuan Li; Jingyuan Sun; Xinsheng Ge; Min Zhang; Jingyue Wang (Soil Dynamics and Earthquake Engineering, 2023)

Maternal exposure to ozone and risk of gestational hypertension and eclampsia in the United States - Kun Yuan; Feng Sun; Yangchang Zhang; Ying Du; Lizhi Wu; Yang Ge; Zhenyu Zhang; Wangnan Cao; Shengzhi Sun (Science of The Total Environment, 2023)

NH3 and N2O emission durability of the heavy-duty diesel engine with DOC, DPF, SCR, and ASC through the accelerated aging method - Liqun Lyu; Wenqiang Sun; Ping Feng; Huaiyu Wang; Lijun Hao; Jianwei Tan; Xin Wang; Chao Song; Haixia Li; Zhao Li; Jiaxing Wang; Yunshan Ge (Fuel, 2023)

Nicotine exposure exacerbates silica-induced pulmonary fibrosis via STAT3-BDNF-TrkB-mediated epithelial-mesenchymal transition in alveolar type II cells - Haoming Chen; Xinrong Tao; Hangbing Cao; Bing Li; Qixian Sun; Wenyang Wang; Yuanjie Zou; Min Mu; Huihui Tao; Yehong Zhao; Deyong Ge (Food and Chemical Toxicology, 2023)

Experimental investigation of the seismic performance of precast post-tensioned segmental bridge piers with stainless energy-dissipating bars - Jian-Yu Fu; Xiao Ge; Jian-Tao Li; Zhi-Guo Sun; Hui Qian; Dong-Sheng Wang (Engineering Structures, 2023)

Insights into the bacterial and archaeal population dynamics in the deep-sea hydrothermal sediments exposed to lights with different wavelengths - Ge Liu; Yeqi Shan; Rui Liu; Chaomin Sun (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Porous carbon nanofibers supported Zn@MnO sorbents with high dispersion and loading content for hot coal gas desulfurization - Yu Feng; Man Zhang; Yangjie Sun; Chunyan Cao; Jiancheng Wang; Mingzheng Ge; Weilong Cai; Jie Mi; Yuekun Lai (Chemical Engineering Journal, 2023)

Whole genome evaluation analysis and preliminary Assembly of Oratosquilla oratoria (Stomatopoda: Squillidae) - Xiaoli Sun; Gang Wang; Jie Yang; Wei Yu; Jiayue Xu; Boping Tang; Ge Ding; Daizhen Zhang (Molecular Biology Reports, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

Construction of ZnIn2S4/MOF-525 heterojunction system to enhance photocatalytic degradation of tetracycline - Xiansheng Zhang; Zhifeng Liu; Binbin Shao; Ting Wu; Yuan Pan; Songhao Luo; Miao He; Lin Ge; Jingwen Sun; Chunyun Cheng; Jian Huang (Environmental Science and Pollution Research, 2023)

A weighted contextual active fire detection algorithm based on Himawari-8 data - Han Zhang; Lin Sun; Chunkai Zheng; Shuai Ge; Jinpeng Chen; Jiayin Li (International Journal of Remote Sensing, 2023)

Dispersed cobalt embedded nitrogen-rich carbon framework activates peroxymonosulfate for carbamazepine degradation: cobalt leaching restriction and mechanism investigation - Yuesen Wang; Yanchun Huang; Ge Gou; Naiwen Li; Longguo Li; Yuxin He; Chao Liu; Bo Lai; Hailong Sun (Chemosphere, 2023)

Surface wave exploration technology for the tunnel overlying strata with vehicle vibration source - Yuefeng Yan; Chengyu Sun; Tengfei Lin; Jiao Wang; Xixi Huang; Qixin Ge; Dayong Zhou (Tunnelling and Underground Space Technology, 2023)

Evolving efficiency of inter-basin water transfers in regional water stress alleviation - Kai Duan; Shen Qu; Ning Liu; Gladys R. Dobbs; Peter V. Caldwell; Ge Sun (Resources, Conservation and Recycling, 2023)

Selective flotation of quartz from feldspar using hydroxypropyl starch as depressant - Ning Sun; Guodong Wang; Peng Ge; Wei Sun; Longhua Xu; Honghu Tang; Li Wang (Minerals Engineering, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Acid-promoted lignin reductive depolymerization under mild conditions via a condensation minimizing approach: From organosolv lignin to woody biomass - Ni Wei; Shuang Qi; Guanhua Wang; Jing Ge; Wenjie Sui; Hao Sun; Ashak Mahmud Parvez; Hongyu Jia; Chuanling Si (Fuel, 2023)

Forest water-use efficiency: Effects of climate change and management on the coupling of carbon and water processes - Zhiqiang Zhang; Lu Zhang; Hang Xu; Irena F. Creed; Juan A. Blanco; Xiaohua Wei; Ge Sun; Heidi Asbjornsen; Kevin Bishop (Forest Ecology and Management, 2023)

Corrigendum to “Quality changes of HHP orange juice during storage: Metabolomic data integration analyses” [Food Chemistry 404 Part B (2023) 134612] - Ruixue Sun; Ranran Xing; Jiukai Zhang; Tingting Deng; Yiqiang Ge; Weiwei Zhang; Ying Chen (Food Chemistry, 2023)

Structural, in vitro digestion, and fermentation characteristics of lotus leaf flavonoids - Jicai Feng; Jian Wang; Tingting Bu; Zhiwei Ge; Kai Yang; Peilong Sun; Liehong Wu; Ming Cai (Food Chemistry, 2023)

Investigating the role and mechanism of water in E-beam modified sweet potato starch: Multi-scale structure, physicochemical properties, and in vitro digestibility - Wei Liang; Wenqing Zhao; Xinyue Liu; Jiayu Zheng; Zhuangzhuang Sun; Xiangzhen Ge; Huishan Shen; Gulnazym Ospankulova; Marat Muratkhan; Wenhao Li (Food Hydrocolloids, 2023)

Antioxidant soy peptide can inhibit xanthine oxidase activity and improve LO2 cell damage - Yifei Dong; Na Sun; Qi Ge; Renzhi Lv; Songyi Lin (Food Bioscience, 2023)

Manganese dioxide eliminates the phytotoxicity of aerobic compost products and converts them into a plant friendly organic fertilizer - Fangyi Pei; Xinbo Cao; Yangcun Sun; Jie Kang; YanXin Ren; Jingping Ge (Bioresource Technology, 2023)

Characteristics, chemical transformation and source apportionment of volatile organic compounds (VOCs) during wintertime at a suburban site in a provincial capital city, east China - BaoLin Wang; ZhenGuo Liu; ZiAng Li; YuChun Sun; Chen Wang; ChuanYong Zhu; Lei Sun; Na Yang; Ge Bai; GuoLan Fan; XiaoYan Sun; ZhiYong Xia; et al. (Atmospheric Environment, 2023)

Isothermal exponential amplification reactions triggered by circular templates (cEXPAR) targeting miRNA - Xue-mei Qu; Xiao-dong Ren; Ning Su; Xian-ge Sun; Shao-li Deng; Wei-ping Lu; Qing Huang (Molecular Biology Reports, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

Reassessing the age of the Early Pleistocene Longgupo fauna, southern China: An updated magnetostratigraphic perspective - LU SUN; CHENGLONG DENG; CAICAI LIU; JUNYI GE; SHIXIA YANG; SHUAI ZHANG; FEI HAN; JEAN‐JACQUES BAHAIN; MICHEL RASSE; ÉRIC BOËDA; YAMEI HOU; GUANGBIAO WEI; et al. (Journal of Quaternary Science, 2023)
As the northernmost locality yielding one of the most representative Early Pleistocene Gigantopithecus – Sinomastodon faunas in southern China, the Longgupo site has preserved valuable geological archives that have significantly improved our understanding of Pleistocene biostratigraphy and biogeography. A convincing chronological framework of this locality is therefore important to elaborate on the evolution of Quaternary faunas as well as paleoenvironment. To reconcile the existing geochronological results with new advances in geochronology and biochronology, we present here a revised magnetostratigraphic age model based on detailed rock magnetic and paleomagnetic data and strengthened by biochronology as well as recently published electron spin resonance and uranium series (ESR/U‐series) age data. Two geomagnetic polarities were identified from the Longgupo sequence: the upper one is thin and normal, corresponding to the Olduvai normal subchron; and the lower one is distinctly thick and reversed, corresponding to the pre‐Olduvai Matuyama Chron. The age of the Longgupo fauna constrained by this refined magnetochronological framework is therefore estimated to be about 2.5–2.0 Ma, consistent with the newly published ESR/U‐series age of 2.5–2.2 Ma.

Cross-Layer Protocol Based on Directional Reception in Underwater Acoustic Wireless Sensor Networks - Yao Sun; Wei Ge; Yingsong Li; Jingwei Yin (Journal of Marine Science and Engineering, 2023)
The long propagation delay of acoustic links leads to the complex randomness of packet collision, which reduces the network packet delivery rate (PDR) and aggravates network congestion. A single vector hydrophone with directional reception characteristics can concentrate the reception gain on a certain direction, which can increase spatial reuse, reduce packet collision, and help to improve the performance of the underwater acoustic wireless sensor networks (UASNs). Herein, this paper proposes a cross-layer protocol with low interference and low congestion (CLIC) based on directional reception. An integrated routing-medium access control (MAC) design is also devised in the CLIC scheme to use the directional beams to create the least-interfering, highest-capacity data transmission links, weighing key factors affecting network performance to obtain routes with low collisions and low congestion. Simulation results show that the CLIC has a higher packet delivery rate (PDR) and higher energy efficiency compared to the QELAR, CITP, and VBF protocols.

The essentiality of dietary myo-inositol to oriental river prawn (Macrobrachium nipponense): Evidence in growth performance, lipid metabolism and mitochondrial function - Ming-Yang Liu; Miao Sun; Ling Zhang; Ya-Ping Ge; Bo Liu; Xiang-Fei Li (Aquaculture, 2023)

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Recent advances in the gut microbiome and microbial metabolites alterations of coronary artery disease - Yuxiang Dai; Zhonghan Sun; Yan Zheng; Junbo Ge (Science Bulletin, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Effects of various microwave intensities collaborated with different cold plasma duration time on structural, physicochemical, and digestive properties of lotus root starch - Xiangxiang Sun; Zhuangzhuang Sun; Ahmed S.M. Saleh; Yifan Lu; Xiuyun Zhang; Xiangzhen Ge; Huishan Shen; Xiuzhu Yu; Wenhao Li (Food Chemistry, 2023)

Multi-functional pH-sensitive active and intelligent packaging based on highly cross-linked zein for the monitoring of pork freshness - Jianglong Kong; Xiaohan Ge; Yuting Sun; Meiru Mao; Hongrui Yu; Runxuan Chu; Yi Wang (Food Chemistry, 2023)

Electron beam irradiation application for improving the multiscale structure and enhancing physicochemical and digestive properties of acetylated naked barley - Xiangzhen Ge; Yayun Hu; Huishan Shen; Wei Liang; Zhuangzhuang Sun; Xiuyun Zhang; Gulnazym Ospankulova; Marat Muratkhan; Kakimova Zhainagul Kh; Wenhao Li (Food Chemistry, 2023)

Quality changes of HHP orange juice during storage: Metabolomic data integration analyses - Ruixue Sun; Ranran Xing; Jiukai Zhang; Tingting Deng; Yiqiang Ge; Weiwei Zhang; Ying Chen (Food Chemistry, 2023)

UPLC-QTOF-MS coupled with machine learning to discriminate between NFC and FC orange juice - Ruixue Sun; Ranran Xing; Jiukai Zhang; Ning Yu; Yiqiang Ge; Weiwei Zhang; Ying Chen (Food Control, 2023)

Transplantation of mitochondria encapsulated in hydrogel ameliorates myocardial ischemia-reperfusion injury - Ya Huang; Xiaolei Sun; Rifeng Gao; Liwei Zhang; Hang Chen; Yang Lv; Xiang Wei; Yunzeng Zou; Kai Hu; Aijun Sun; Junbo Ge (Chemical Engineering Journal, 2023)

Microbial communities that drive the degradation of flax pectin and hemicellulose during dew retting with Bacillus licheniformis HDYM-04 and Bacillus subtilis ZC-01 addition - Chi Zhang; Baiyan Cai; Yangcun Sun; Jie Kang; Fangyi Pei; Jingping Ge (Bioresource Technology, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

A systematic review, meta-analysis and meta-regression of the global prevalence of foodborne Vibrio spp. infection in fishes: A persistent public health concern - Jun-Yang Ma; Xin-Kun Zhu; Ren-Ge Hu; Ze-Zheng Qi; Wen-Chao Sun; Zhi-Peng Hao; Wei Cong; Yuan-Huan Kang (Marine Pollution Bulletin, 2023)

Identification and localization of morphological feature-specific metabolites in Reynoutria multiflora roots - Meng-Ting Cai; Yu Zhou; Wen-Luan Ding; Yu-Hong Huang; Ying-Shan Ren; Zhi-You Yang; Lei Zhang; Fei Sun; Hai-Biao Guo; Liang-Yun Zhou; Zhi-Hong Gong; Xiu-Hong Piao; et al. (Phytochemistry, 2023)

Structural, physicochemical and biodegradable properties of composite plastics prepared with polyvinyl alcohol (PVA), OSA potato starch and gliadin - Jiayu Zheng; Yayun Hu; Chunyan Su; Wei Liang; Xinyue Liu; Wenqing Zhao; Zhuangzhuang Sun; Xiuyun Zhang; Yifan Lu; Huishan Shen; Xiangzhen Ge; Gulnazym Ospankulova; et al. (Journal of Food Engineering, 2023)

Forest hydrology modeling tools for watershed management: A review - Ge Sun; Xiaohua Wei; Lu Hao; María González Sanchis; Yiping Hou; Rasoul Yousefpour; Run Tang; Zhiqiang Zhang (Forest Ecology and Management, 2023)

Seismic response of prestressed precast reinforced concrete beam-column joints assembled by steel sleeves - Hanyang Xue; Ashraf Ashour; Wenjie Ge; Dafu Cao; Chuanzhi Sun; Siqi Cao (Engineering Structures, 2023)

Dopaminergic Dysfunction and Glucose Metabolism Characteristics in Parkin-Induced Early-Onset Parkinson’s Disease Compared to Genetically Undetermined Early-Onset Parkinson’s Disease - Feng-Tao Liu; Jia-Ying Lu; Yi-Min Sun; Ling Li; Yu-Jie Yang; Jue Zhao; Jing-Jie Ge; Ping Wu; Jie-Hui Jiang; Jian-Jun Wu; Chuan-Tao Zuo; Jian Wang (Phenomics, 2023)

Theoretical determination of zeta potential for the variable charge soil considering the pH variation based on the Stern-Gouy double-layer model - Xiaojuan Yang; Ge Shi; Chao Wu; Honglei Sun (Environmental Science and Pollution Research, 2023)

Insights into the characteristics and mechanism of vacuum drying technology for municipal sludge processing - Qixiang Zhu; Xiaofeng Sun; Shifu Ge; Yang Yu (Chemosphere, 2023)

Understanding the differences in heat-induced gel properties of twelve legume proteins: A comparative study - Jiao Ge; Cuixia Sun; Yuyang Chang; Saiya Li; Yin Zhang; Yapeng Fang (Food Research International, 2023)

A clarification of concepts related to the digestion and absorption of carotenoids and a new standardized carotenoids bioavailability evaluation system - Tonghui Geng; Shihan Bao; Xiangyu Sun; Dexue Ma; Hexin Zhang; Qian Ge; Xuebo Liu; Tingting Ma (Food Chemistry, 2023)

Numerical study on flexural and bond-slip behaviours of GFRP profiled-concrete composite beams with groove shear connector - Wenjie Ge; Zhiwen Zhang; Zhongwei Guan; Ashraf Ashour; Yue Ge; Yiwen Chen; Hongbo Jiang; Chuanzhi Sun; Shan Yao; Weihua Yan; Dafu Cao (Engineering Structures, 2023)

Debris flow susceptibility based on the connectivity of potential material sources in the Dadu River Basin - Xinyue Liang; Yonggang Ge; Lu Zeng; Liqun Lyu; Qingmin Sun; Yuqing Sun; Xi'an Wang (Engineering Geology, 2023)

Heat and moisture transfer in wall-to-floor thermal bridges and its influence on thermal performance - Yucong Xue; Yifan Fan; Shuqin Chen; Zitao Wang; Weijun Gao; Zhijian Sun; Jian Ge (Energy and Buildings, 2023)

Helical configuration channels boost performance in anion exchange membranes - Yang Zhang; Fan Zhang; Yiwen Chen; Lixuan Sun; Chengpeng Wei; Huaqing Zhang; Hongjun Zhang; Bangjiao Ye; Liang Wu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2023)

Trans-level multi-scale simulation of porous catalytic systems: Bridging reaction kinetics and reactor performance - Chengxiang Li; Ji Xu; Tianhao Qiu; Zikang Sun; Haolei Zhang; Wei Ge (Chemical Engineering Journal, 2023)

Ultralight carbon aerogel composites derived from MOFs and cross-linked chitosan: Synthesis, characterization, and U(VI) adsorption - Yanbing Sun; Jianfa Chen; Yixiao Kang; Haoyan Zhang; Yulin Ge; Nan Yuan; Yubo Xing; Wei Ma; Zhen Yang; Liping Zou; Liang Lu (Chemical Engineering Journal, 2023)

Engineered anti-cancer nanomedicine for synergistic ferroptosis-immunotherapy - Xinyu Zhang; Haiyan Ge; Yanling Ma; Linlin Song; Yansong Ma; Guanglong Tian; Lei Wang; Qingwei Meng; Xiao Sun (Chemical Engineering Journal, 2023)

Total hydrogenation of hydroxymethylfurfural via hydrothermally stable Ni catalysts and the mechanistic study - Fuzeyu Zhong; Xiaohu Ge; Weixiao Sun; Wei Du; Keng Sang; Chang Yao; Yueqiang Cao; Wenyao Chen; Gang Qian; Xuezhi Duan; Zhirong Yang; Xinggui Zhou; et al. (Chemical Engineering Journal, 2023)

Valence engineering at the interface of MoS2/Mo2C heterostructure for bionic nitrogen reduction - Tong Ye; Kun Ba; Xiaoyong Yang; Taishi Xiao; Yangye Sun; Hanqi Liu; Can Tang; Binghui Ge; Ping Zhang; Tao Duan; Zhengzong Sun (Chemical Engineering Journal, 2023)

Porous polydroxyalkanoates (PHA) scaffolds with antibacterial property for oral soft tissue regeneration - Fanfan Chen; Xinyi Liu; Xiyuan Ge; Yong Wang; Zifan Zhao; Xu Zhang; Guo-Qiang Chen; Yuchun Sun (Chemical Engineering Journal, 2023)

Risk assessment methods of cascade reservoir dams: a review and reflection - Te Wang; Zongkun Li; Wei Ge; Yadong Zhang; Yutie Jiao; Hua Zhang; Heqiang Sun; Pieter van Gelder (Natural Hazards, 2023)

Electrocatalytic degradation of methyl orange and 4-nitrophenol on a Ti/TiO2-NTA/La-PbO2 electrode: electrode characterization and operating parameters - Zepeng Sun; Yue Ni; Yuandong Wu; Wenqing Yue; Ge Zhang; Jianmei Bai (Environmental Science and Pollution Research, 2023)

An offshore subsurface thermal structure inversion method by coupling ensemble learning and tide model for the South Yellow Sea - Fangjie Yu; Fengzhi Sun; Jianchao Li; Ge Chen (Frontiers in Marine Science, 2022)
The South Yellow Sea Cold Water Mass (SYSCWM), which occurs in the South Yellow Sea (SYS) during summer, significantly impacts the hydrological characteristics and marine ecosystems but lacks fine interior data. With satellite observations, significant achievements have been made in reconstructing high-resolution ocean subsurface thermohaline structure based on machine learning. However, the accuracy of offshore subsurface parameter estimation will be affected due to the macro-tidal environment and fewer in situ observations. In this paper, we coupled the TPXO tide model and Light Gradient Boosting Machine algorithm to develop an inversion model of offshore subsurface thermal structure for the SYS using sea surface data and in situ observations. After light modelling, the subsurface temperature structure in the SYS is retrieved from sea surface parameters with a spatial resolution of 0.25° at depths of 0-55 m. Observation-based dataset (ARMOR3D) and in situ observations are used for model evaluation. According to the validation of the mooring buoy observations, the overall coefficient of determination (R 2 ), which determines the percentage of variance in the dependent variable that can be explained by the independent variable, is more than 0.95. Furthermore, the R 2 is improved by 12% due to coupling tide model below the thermocline during the maturity stage of SYSCWM, which is helpful for a better reconstruction of SYSCWM. Comparing with the cruise data, the average R 2 of the proposed model is 0.927 which is slightly better than the accuracy of the observation-based ARMOR3D dataset. Since the R 2 exceeds 0.8 in the most area of 121°E~123.5°E, 33°N~36°N, the reconstruction is reliable in this area. The method provides a new explorable direction for reconstructing the ocean thermal structure in offshore areas.

Hydrological Response and Ecological Flow Optimization in Water Diversion Area of Inter-basin Water Diversion Project - Tao Bai; Xian-Ge Sun; Jian Wei; Lianzhou Wu (Water Resources Management, 2022)

Self-assembling Bioadhesive Inspired by the Fourth Repetitive Sequence of Balanus albicostatus Cement Protein 20 kDa (Balcp-20 k) - Li Jia; Yabiao Yu; Jinyang Zheng; Hao Zhou; Qiang Liu; Wei Wang; Xinxin Liu; Xiuming Zhang; Dongtao Ge; Wei Shi; Yanan Sun (Marine Biotechnology, 2022)

The Pseudogene BMEA_B0173 Deficiency in Brucella melitensis Contributes to M-epitope Formation and Potentiates Virulence in a Mice Infection Model - Ge Zhang; Hao Dong; Yu Feng; Hui Jiang; Tonglei Wu; Jiali Sun; Xin Wang; Minghe Liu; Xiaowei Peng; Yinghui Zhang; Xiaoqian Zhang; Liangquan Zhu; et al. (Current Microbiology, 2022)

Synergistic removal of organic pollutants from water by CTF/BiVO4 heterojunction photocatalysts - Yan Yu; Yanan Sun; Beixiao Ge; Jiawen Yan; Kaili Zhang; Hui Chen; Jinxing Hu; Juntao Tang; Shuang Song; Tao Zeng (Environmental Science and Pollution Research, 2022)

Source and composition analysis of petroleum hydrocarbons in the refinery circulating water - Ge Ma; Han Xiao; Xinming Wei; Anshan Xiao; Xiaoying Sun; Xiang Gao (Environmental Science and Pollution Research, 2022)

Cerebellar injury induced by cadmium via disrupting the heat-shock response - Shao-Shuai Bi; Milton Talukder; Xue-Tong Sun; Mei-Wei Lv; Jing Ge; Cong Zhang; Jin-Long Li (Environmental Science and Pollution Research, 2022)

Two new alkaloids from Tibetan medicine of Hypecoum leptocarpum - Bo Sun; Israa Assani; Chun-Gu Wang; Mu-Xuan Wang; Ling-Fei Liu; Yan Li; Ge Yan; Yun-Ruo Yang; Zhi Chen; Zhi-Xin Liao (Natural Product Research, 2022)

Protective Effect of Levilactobacillus brevis Against Yersinia enterocolitica Infection in Mouse Model via Regulating MAPK and NF-κB Pathway - Ziqi Shi; Naiyu Guan; Weijiao Sun; Tianzhi Sun; Lingdi Niu; Jinyu Li; Junwei Ge (Probiotics and Antimicrobial Proteins, 2022)

Protective Effects of Astilbin Against Cadmium-Induced Apoptosis in Chicken Kidneys via Endoplasmic Reticulum Stress Signaling Pathway - Xiuyu Li; Ming Ge; Weifeng Zhu; Panpan Wang; Jiangfeng Wang; Tiange Tai; Yuxi Wang; Jianxu Sun; Guangliang Shi (Biological Trace Element Research, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Laboratory investigation on engineering mechanics properties of granite after various heating/cooling treatments - Fei Zhao; Qiang Sun; Zhenlong Ge; Chen Dang (Environmental Science and Pollution Research, 2022)

Novel Self-Assembled Micelles With Increased Tumor Penetration and Anti-Tumor Efficiency Against Breast Cancer - Yani Yang; Yuezhu Zhao; Jie Liu; Chen Ge; Weiwei Zhang; Yue Zhang; Junji Wang; Guohao Sun; Xiujun Lin; Xiaohong Lu; Xiang Tang; Jun He; et al. (Pharmaceutical Research, 2022)

Bioremediation of tetramethyl thiuram disulfide and resource utilization of natural rubber wastewater by WR-2 Bacillus-dominated microbial community - Dayu Zhu; Chengjun Ge; Hongfei Sun; Jun Wang; Liujing He (Environmental Science and Pollution Research, 2022)

Correction to: Antitumor effect of TRAIL on oral squamous cell carcinoma using magnetic nanoparticle-mediated gene expression - Leiying Miao; Chao Liu; Jiuyu Ge; Weidong Yang; Jinzhong Liu; Weibin Sun; Bai Yang; Changyu Zheng; Hongchen Sun; Qingang Hu (Cell Biochemistry and Biophysics, 2022)

Real wine or not? Protecting wine with traceability and authenticity for consumers: chemical and technical basis, technique applications, challenge, and perspectives - Xiangyu Sun; Fan Zhang; Gastón Gutiérrez-Gamboa; Qian Ge; Pingkang Xu; Qianwen Zhang; Yulin Fang; Tingting Ma (Critical Reviews in Food Science and Nutrition, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Influences of confining pressure, strain rate and temperature on crack damage stress thresholds and shape parameter m in sandstone: a review - Zhenlong Ge; Qiang Sun; Lei Xue; Haijun Zhao (Arabian Journal of Geosciences, 2022)

Male Predisposition in Cerebellar Mutism Syndrome: a Cohort Study - Wei Yang; Ming Ge; Kaiyi Zhu; Jiashu Chen; Ping Yang; Yingjie Cai; XiaoJiao Peng; Jia Wang; Hailang Sun; Yuanqi Ji; Fengmao Zhao; Hong Zhang (The Cerebellum, 2022)

Conditions of Mainland China’s Island Ecosystems and Associated Influencing Factors: Integrated Assessment of 42 Typical Island Ecosystems - Zhiyuan Ma; Weiwei Yu; Wanting Zhang; Feiyang Ge; Bin Chen; Wenjia Hu; Dian Zhang; Jianji Liao; Hao Huang; Yuanmin Sun; Haiping Huang (Frontiers in Marine Science, 2022)
Although China possesses a large number of islands, knowledge of their overall ecological condition is limited on a national scale. Accordingly, this study developed a comprehensive and quantitative island ecosystem assessment framework that incorporates environmental quality, biological structure, and landscape patterns. The framework was applied to 42 typical, representative islands within China’s coastal regions, including different climatic zones, area sizes, populations, and substratum lithologies. Results showed that the value range of the comprehensive index of island ecosystem condition ( CI island ) was significant (from 52.33 to 89.53, 71.72 average), and 85.4% of islands scored either “high” or “good,” indicative of their exceptional condition. However, conditions varied among different island components, indicating different challenges. Environmental quality index ( I env ) values ranged from 60.70 to 94.80 (79.72 average), where primary threats were seawater nutrient pollution, petroleum, and marine organism metal contamination. Biological structure index ( I bio ) values ranged from 43.50 to 89.40 (66.10 average), where primary threats were vegetation destruction and a reduction in marine biodiversity within intertidal and subtidal zones. Landscape pattern index ( I land ) values varied significantly (from 6 to 100, 72.36 average), where a key characteristic of highly developed islands was low natural landscape (vegetation) coverage. Conditions also varied among island climate zones, lithologies, area sizes, and levels of human habitation. Additionally, island ecosystem conditions were influenced by both natural and anthropogenic factors as well as area size, population, and GDP. Although distance to the mainland significantly correlated to ( I bio ), and ( CI island ), these parameters did not significantly correlate to ( I env ), which might be explained by that environmental quality was generally conditional on large-scale environments. This assessment is intended to provide a holistic perspective on island conditions in China while identifying key challenges and associated driving factors, which will greatly aid in establishing island-specific sustainable management practices.

Mechanical responses of igneous rocks to microwave irradiation: a review - Guogang Bai; Qiang Sun; Hailiang Jia; Zhenlong Ge; Liyun Tang; Shengze Xue (Acta Geophysica, 2022)

Experimental study on drainage mechanism of the self-starting drainage method for a slope - Fei-xiang Shuai; Qi Ge; Ze-yong Liu; Zhong-xuan Chen; Hong-yue Sun (European Journal of Environmental and Civil Engineering, 2022)

Recent advances in the structure, synthesis, and applications of natural polymeric hydrogels - Khalid Gul; Ren-You Gan; Cui-Xia Sun; Ge Jiao; Ding-Tao Wu; Hua-Bin Li; Ahmad Kenaan; Harold Corke; Ya-Peng Fang (Critical Reviews in Food Science and Nutrition, 2022)

Ultrasound-induced biophysical effects in controlled drug delivery - Lulu Zhang; Zhuohua Lin; Lan Zeng; Fan Zhang; Lihong Sun; Suhui Sun; Ping Wang; Menghong Xu; Jinxia Zhang; Xiaolong Liang; Huiyu Ge (Science China Life Sciences, 2022)

Changes in the waterbird community of the Yangtze River in the Three Gorges Reservoir Region, China, 2003–2013 - Xiuming Li; Wenfa Xiao; Ge Sun; Tian Ma; Fuguo Liu; Xiaoyun Liu; Hualong Su; Kaijun Pan; Ruimei Cheng; Fawen Qian (Biologia, 2022)

Long-term performance of the ventilation-enhanced embankment in permafrost regions - Hailin Wang; Hong Sun; Xiurun Ge; Dongpeng Zhu; Jianbing Chen (Arabian Journal of Geosciences, 2022)

Geochronology and geochemistry of the W-Mo-ore-related granitic rocks from eastern Ningzhen, lower Yangtze river belt, eastern China - Fangyue Wang; Yongjie Guo; Haiyang Yan; Haiou Gu; He Sun; Can Ge (Acta Geochimica, 2022)

An evolutionarily conserved mechanism that amplifies the effect of deleterious mutations in osteosarcoma - Yankai Jiang; Fuqun Ge; Guoyong Sun; Haibin Wang (Molecular Genetics and Genomics, 2022)

The role of currently used medicinal plants in aquaculture and their action mechanisms: A review - Dawit Adisu Tadese; Changyou Song; Cunxin Sun; Bo Liu; Bo Liu; Qunlan Zhou; Pao Xu; Xianping Ge; Mingyang Liu; Xiaodi Xu; Metekia Tamiru; Zhigang Zhou; et al. (Reviews in Aquaculture, 2022)
Global aquaculture development increased rapidly in recent years, and the sector has become one of the fastest‐growing industries in the animal‐derived food production system. However, disease outbreak remains a major challenge that hinders sustainable production through an advanced level of intensification. Recently, antibiotics applied have been restricted globally against aquatic disease outbreaks due to their apparent accumulation in the tissues, which imposes on the development of resistant bacteria. Naturally available medicinal plants were tested to combat some pathogens affecting humans and animals, as they contain a wide range of active substances that can induce biological functions. Currently, medicinal plants are being tested in aquaculture as a safe and eco‐friendly substance to modulate immune status, enhance growth performance and prevent fish disease. Moreover, different parts (e.g. leaf, flower and rhizome) and forms (e.g. crude, extract and active ingredient) of plants are used to modulate specific biological functions (e.g. growth promoter, anti‐stress, immunostimulants, appetite stimulation, antibacteria, anti‐parasite and anti‐virus). Medicinal plants are also used to defend the aquaculture animal from external stressors, such as poor water quality, high environmental temperature and overcrowding. This paper aims to provide information on the role of currently used medicinal plants on aquaculture animals and their action mechanisms. In conclusion, the current review suggested that the utilisation of medicinal plants remained untapped in uncovering the biological activities of active substances against a variety of diseases across diverse species of aquaculture animals.

miR-361-3p mitigates hypoxia-induced cardiomyocyte injury via targeting apoptosis initiators caspase-2/-8/-9 - Jinwei Zhang; Xiankun Zhou; Jing Sun; Mingzhou Li; Jideng Ma; Liangpeng Ge (In Vitro Cellular & Developmental Biology - Animal, 2022)

Is Doppler Echocardiography Adequate for Surgical Planning of Single Ventricle Patients? - Zhenglun Alan Wei; Biao Si; Xiaoqian Ge; Meng Zhu; Maria A. Cetatoiu; Chenze Tian; Lixin Sun; Bin Qiao (Cardiovascular Engineering and Technology, 2021)

Assessment of river ecosystem health in Tianjin City, China: index of ecological integrity and water comprehensive pollution approach - Yan Wang; Shang Zhao; Mingdong Sun; Xubo Lv; Wenqian Cai; Xiangqin Xu; Hongxiang Ge; Kun Lei (Frontiers of Earth Science, 2021)

Origin and Spread of the ALDH2 Glu504Lys Allele - Xiaokai Zhang; Aijun Sun; Junbo Ge (Phenomics, 2021)
Gene polymorphism of acetaldehyde dehydrogenase 2 (ALDH2), a key enzyme for alcohol metabolism in humans, can affect catalytic activity. The ALDH2 Glu504Lys mutant allele has a high-frequency distribution in East Asian populations and has been demonstrated to be associated with an increased risk of cardiovascular disease, stroke, and tumors. Available evidence suggests that the evolution of the ALDH2 gene has been influenced by multiple factors. Random mutations produce Glu504Lys, and genetic drift alters the frequency of this allele; additionally, environmental factors such as hepatitis B virus infection and high-elevation hypoxia affect its frequency through selective effects, ultimately resulting in a high frequency of this allele in East Asian populations. Here, the origin, selection, and spread of the ALDH2 Glu504Lys allele are discussed, and an outlook for further research is proposed to realize a precision medical strategy based on the genetic and environmental variations in ALDH2.

Integrated 16S rRNA Gene Sequencing and LC-MS Analysis Revealed the Interplay Between Gut Microbiota and Plasma Metabolites in Rats With Ischemic Stroke - Wanfeng Wu; Yihang Sun; Ning Luo; Cheng Cheng; Chengting Jiang; Qingping Yu; Shaowu Cheng; Jinwen Ge (Journal of Molecular Neuroscience, 2021)

The comprehensive measurement method of energy conservation and emission reduction in the whole process of urban sewage treatment based on carbon emission - Yue Zhang; Tonggang Ge; Jing Liu; Yongli Sun; Yu Liu; Qing Zhao; Tengfei Tian (Environmental Science and Pollution Research, 2021)

Influence of high-temperature thermal cycles on the pore structure of red sandstone - Xudong Jing; Qiang Sun; Hailiang Jia; Zhenlong Ge; Ting Wang (Bulletin of Engineering Geology and the Environment, 2021)

Extracting copper and cobalt from non-ferrous residues by iron- and sulfur-oxidizing bacteria - Jianxing Sun; Wenxian Liu; Ruichang Tang; Haina Cheng; Ronghui Liu; Kang Liu; Wenhao Zhan; Yang Ge; Hongbo Zhou; Yuguang Wang (Environmental Science and Pollution Research, 2021)

Aestuariibaculum sediminum sp. nov., a marine bacterium isolated from a tidal flat in Zhoushan - Zhi-Cheng Wu; Xin-Yin Zhang; Cong Sun; Lin Xu; Ge-Yi Fu; Xue-Wei Xu (Archives of Microbiology, 2021)

Molecular cloning and sequence characterization of common carp (Cyprinus carpio) integrin β1 (ITGβ1) and its temporal expression in response to CyHV-3 - Xiaona Jiang; Jiaxin Sun; Chitao Li; Xuesong Hu; Yanlong Ge; Bao Li; Lianyu Shi; Zhiying Jia (Aquaculture International, 2021)

Maribellus comscasis sp. nov., a novel deep‐sea Bacteroidetes bacterium, possessing a prominent capability of degrading cellulose - Rikuan Zheng; Ruining Cai; Rui Liu; Ge Liu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Bacteroidetes are thought to be specialized for the degradation of algae‐derived ocean polysaccharides. Here, we show that Bacteroidetes are the predominant phylum in deep‐sea sediments and possess more genes associated with polysaccharides degradation than other bacteria. We have isolated a novel Bacteroidetes species from the deep‐sea sediments by using a special polysaccharide containing medium, Maribellus comscasis WC007, which possesses 82 putative polysaccharide utilization loci (PULs) containing 374 glycoside hydrolases and 82 SusC/D pairs (Sus indicates s tarch u tilization s ystem; SusC represents the actual TonB‐dependent transporter, and SusD is an associated substrate‐binding outer membrane lipoprotein) together with 58 sigma/antisigma factors. Through an in‐depth analysis of these PULs, strain WC007 can efficiently degrade numerous different polysaccharides including cellulose, pectin, fucoidan, mannan, xylan and starch, which are verified by growth assays. Notably, we find that cellulose has the most significant growth‐promoting effect on M . comscasis WC007. And based on scanning electron microscope observation, transcriptomics and metabolomics, we further report on the underlying mechanisms of cellulose degradation and utilization, as well as potential contributions to the carbon cycle. Overall, our results suggest that Bacteroidetes may play key roles in the carbon cycle, likely due to their high abundance and prominent polysaccharide degradation capabilities.

Growth promotion of a deep‐sea bacterium by sensing infrared light through a bacteriophytochrome photoreceptor - Ge Liu; Yeqi Shan; Rikuan Zheng; Rui Liu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Photoreceptors are found in all kingdoms of life and bacteriophytochromes (Bphps) are the most abundant photo‐sensing receptors in bacteria. Interestingly, BphPs have been linked to some bacterial physiological responses, yet most of the biological processes they regulate are still elusive, especially in non‐photosynthetic bacteria. Here, we show that a bacteriophytochrome (CmoBphp) from a deep‐sea bacterium Croceicoccus marinus OT19 perceives infrared light (wavelength at 940 nm) and transduces photo‐sensing signals to a downstream intracellular transduction cascade for better growth. We discover that the infrared light‐mediated growth promotion of C. marinus OT19 is attributed partly to the enhancement of pyruvate and propanoate metabolism. Further study suggests that CmoBphp plays a crucial role in integrating infrared light with intracellular signalling to control the bacterial growth and metabolism. This is the first report that deep‐sea non‐photosynthetic bacteria can sense infrared light to control growth through a bacteriophytochrome photoreceptor, thus providing new understandings towards light energy utilization by microorganisms.

Dexmedetomidine alleviates cardiomyocyte apoptosis and cardiac dysfunction may be associated with inhibition of RhoA/ROCK pathway in mice with myocardial infarction - Tao Sun; Qian Gong; Ying Wu; Zhiming Shen; Yan Zhang; Shenglin Ge; Jing-Si Duan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Seismic performance of precast bridge columns connected with grouted corrugated-metal duct through biaxial quasi-static experiment and modeling - Xia Zhanghua; Lin Shangshun; He Yongbo; Ge Jiping; Sun Jinlei (Earthquake Engineering and Engineering Vibration, 2021)

Thermal effect on b-value of limestone subjected to uniaxial loading - Zhenlong Ge; Qiang Sun; Jishi Geng; He Zhang (Arabian Journal of Geosciences, 2021)

Changes in b-values due to sandstone failure after exposure to high temperatures - Zhenlong Ge; Qiang Sun; He Zhang (Arabian Journal of Geosciences, 2021)

Calcium protects bacteria against cadmium stress via reducing nitric oxide production and increasing iron acquisition - Zuodong Wu; Rikuan Zheng; Ge Liu; Rui Liu; Shimei Wu; Chaomin Sun (Environmental Microbiology, 2021)
Summary Cadmium (Cd) is a common toxic heavy metal in the environment, and bacteria have evolved different strategies against Cd‐toxicity. Here, we found that marine bacterium Bacillus sp. 98 could significantly alleviate Cd‐toxicity by recruiting calcium (Ca) for reducing excessive intracellular nitric oxide (NO) and enhancing iron acquisition. To investigate the underlying mechanisms, mass spectrometry‐based proteomic analysis was applied to Bacillus sp. 98 after treated with Cd supplemented with or without Ca. Compared with bacterial cells treated with Cd only, the proteomic results showed that the expression level of NO synthase was markedly down‐regulated, while the expression levels of NO dioxygenase, which is responsible for converting NO to nitrate, and proteins associated with iron uptake were profoundly enhanced when Ca was supplemented. Consistently, bacterial intracellular NO amount was dramatically increased after Bacillus sp. 98 was treated with Cd, and reversed to a normal level when Ca or iron was supplemented. Notably, Ca also protected bacteria against stresses from other heavy metals including Cu, Cr, Mn, Ni and Zn, and this self‐protection strategy was adopted as well in zebrafish, which encourages us to develop Ca‐associated products against heavy metals toxicity in the future.

Pyrolysis characteristics of organic-rich shale from the Chang 7 member of Triassic Yanhe Profile in Ordos Basin - Zhenlong Ge; Qiang Sun; Delu Li; Qingmin Shi; Shaoni Wei; Tian Yang (Arabian Journal of Geosciences, 2021)

Ring distribution patterns—diversification or speciation? Comparative phylogeography of two small mammals in the mountains surrounding the Sichuan Basin - Yanqun Wang; Anderson Feijó; Jilong Cheng; Lin Xia; Zhixin Wen; Deyan Ge; Jian Sun; Liang Lu; Song Li; Qisen Yang (Molecular Ecology, 2021)
Studying the genetic differentiation in a unique geographical area contributes to understanding the process of speciation. Here, we explore the spatial genetic structure and underlying formation mechanism of two congeneric small mammal species ( Apodemus draco and A. chevrieri ), which are mainly distributed in the mountains surrounding the lowland Sichuan Basin, southwest China. We applied a set of comparative phylogeographical analyses to determine their genetic diversification patterns, combining mitochondrial ( Cytb and COI ) and nuclear (microsatellite loci) markers, with dense sampling throughout the range (411 A . draco from 21 sites and 191 A . chevrieri from 22 sites). Moreover, we performed three complementary statistical methods to investigate the correlation between genotype and geographical and environmental components, and predicted the potential suitable distributional range under the present and historical climate conditions. Our results suggest that both species have experienced allopatric differentiation and admixture in historical periods, resulting in a ring‐shape diversification, under the barrier effect of the Sichuan Basin. We infer that the tectonic events of the Qinghai–Tibetan Plateau and climatic oscillations during the Quaternary played an important role on the genetic divergence of the two species by providing environmental heterogeneity and geographical variation. Our study reveals a case of two sympatric small mammals following a ring‐shaped diversification pattern and provides insight into the process of differentiation.

New U-Pb zircon ages document Late Triassic Tianqiaoling flora of eastern Jinlin, NE China - Yuhui Feng; Tao Yang; Fei Liang; Ge Sun (Science China Earth Sciences, 2021)

Divergent responses in morphology and life history to an Asplanchna kairomone between attached and free-swimming Brachionus dorcas (Rotifera) - Shan Jiang; Yan Bai; Fan Sun; Le-Le Ge; Yi-Long Xi (Hydrobiologia, 2021)

Efficient photocatalytic degradation of volatile organic compounds over carbon quantum dots decorated Bi2WO6 under visible light - Yangqing Liu; Changjun Zhu; Jingwen Sun; Yan Ge; Fujiao Song; Guanzhong Wang; Qi Xu (Environmental Science and Pollution Research, 2021)

A microstructural investigation on hydraulic conductivity of soft clay - Hailin Wang; Hong Sun; Zhaoxing Huang; Xiurun Ge (Bulletin of Engineering Geology and the Environment, 2021)

Cooling effect of a composite embankment for wide expressways in permafrost regions: a three-dimensional numerical analysis - Hailin Wang; Hong Sun; Xiurun Ge; Jianbing Chen; Dongpeng Zhu (European Journal of Environmental and Civil Engineering, 2021)

Robust design of self-starting drains using Random Forest - Qi Ge; Zhong-qiang Liu; Hong-yue Sun; Dominik Lang; Fei-xiang Shuai; Yue-quan Shang; Ying-qiu Zhang (Journal of Mountain Science, 2021)

Recent advances in the study of the ferns from Middle Jurassic Baiyanghe flora of Junggar Basin, Xinjiang, China - Ge Sun; Tao Yang; Xiao Tan; Yuyan Miao (Palaeobiodiversity and Palaeoenvironments, 2021)

Varying support for abundance‐centre and congeneric‐competition hypotheses along elevational transects of mammals - Zhixin Wen; Deyan Ge; Anderson Feijó; Yuanbao Du; Jilong Cheng; Jian Sun; Yanqun Wang; Lin Xia; Qisen Yang (Journal of Biogeography, 2021)
Aim Whether species are most abundant at their geographic range centre and increasingly rare towards range limits (the abundance‐centre hypothesis, ACH) has weak empirical support in birds along elevational gradients. This may be due to empirical limitations—most studies do not capture the multi‐faceted nature of elevational gradients or species interactions. We examine the ACH and an alternative that the abundance maximum of elevational sympatric congeners will occur at different elevations along a gradient (the congeneric‐competition hypothesis, CCH). Location Twelve elevational gradients in Central and Southwest China. Taxon Five small mammal species, including three congeneric species. Methods The ACH was tested by fitting abundance patterns to Huisman‐Olff‐Fresco (HOF) models and measuring the relative elevational distance between a species' abundance‐weighted range centre ( RC Abu ) and its elevational range centre. The CCH was tested by calculating the elevational overlap value of each congeneric pair and the relative elevational distance ( RC AbuDiff ) between the RC Abu s of congeners. Results Abundances of each species showed diverse patterns along different gradients. For all species, a unimodal symmetric pattern appeared at most once among the studied gradients and found in only four (8.7%) of the total cases. Most (90.9%) of the Apodemus congeneric pairs had a high elevational overlap (above 75%). For each of the three congeneric pairs, 40.0% to 50.0% of the cases showed RC AbuDiff values > 0.25, suggesting that the congeners’ RC Abu s were separated by at least one elevational climate zone. Main conclusions Species' elevational abundance patterns may vary among different elevational gradients in the same geographic region. The elevational abundance patterns of five mammalian species were rarely consistent with the ACH after the spatial variability of the patterns was considered. The abundance patterns of congeneric species showed moderate support for the CCH.

Transcriptome and Metabolome Analyses of Sea Cucumbers Apostichopus japonicus in Southern China During the Summer Aestivation Period - Qiuhua Yang; Xusheng Zhang; Zhen Lu; Ruifang Huang; Ngoc Tuan Tran; Jianshao Wu; Fuyuan Yang; Hui Ge; Chenhui Zhong; Qian Sun; Chen Zhou; Qi Lin (Journal of Ocean University of China, 2021)

A siphon drainage method for stabilizing bank slopes under water drawdown condition - Yang Yu; Chengcheng Lv; Dongfei Wang; Qi Ge; Hongyue Sun; Yuequan Shang (Natural Hazards, 2021)

A new self-starting drainage method for slope stabilization and its application - Hong-yue Sun; Qi Ge; Yang Yu; Fei-xiang Shuai; Cheng-cheng Lü (Bulletin of Engineering Geology and the Environment, 2021)

Protective effects of dihydromyricetin on primary hippocampal astrocytes from cytotoxicity induced by comorbid diabetic neuropathic pain and depression - Huixiang Ge; Mengyun Sun; Xingyu Wei; Mingming Zhang; Hongcheng Tu; Yuanzhen Hao; Ruxin Chen; Miao Ye; Yun Gao (Purinergic Signalling, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Protectin DX ameliorates inflammation in sepsis-induced acute lung injury through mediating PPARγ/NF-κB pathway - Haifa Xia; Yangyang Ge; Fuquan Wang; Yu Ming; Zhouyang Wu; Jingxu Wang; Shujun Sun; Shiqian Huang; Ming Chen; Weimin Xiao; Shanglong Yao (Immunologic Research, 2020)

The cyclic lipopeptides suppress the motility of Vibrio alginolyticus via targeting the Na + ‐driven flagellar motor component MotX - Rui Liu; Rikuan Zheng; Ge Liu; Chaomin Sun (Environmental Microbiology, 2020)
Summary In our previous study, we found that pumilacidin‐like cyclic lipopeptides (CLPs) derived from marine bacterium Bacillus sp. strain 176 significantly suppressed the mobile capability and virulence of Vibrio alginolyticus . Here, to further disclose the mechanism of CLPs inhibiting the motility of V . alginolyticus , we first applied transcriptomic analysis to V . alginolyticus treated with or without CLPs. The transcriptomic results showed that the expression of several important components of the Na + ‐driven flagellar motor closely related to bacterial motility were markedly suppressed, suggesting that the structure and function of Na + ‐driven flagellar motor might be disabled by CLPs. The transcriptomic data were further analysed by the protein–protein interaction network, and the results supported that MotX, one of the essential components of Na + ‐driven flagellar motor was most likely the action target of CLPs. In combination of gene knockout, electrophoretic mobility shift assay and immunoblotting techniques, CLPs were demonstrated to affect the rotation of flagella of Vibrio alginolyticus via direct interacting with the Na + ‐driven flagellar motor component MotX, which eventually inhibited the bacterial motility. Interestingly, homologues of MotX were found broadly distributed and highly conserved in different pathogenic species, which extends the application range of CLPs as an antibacterial drug targeting bacterial motility in many pathogens.

Prevalence of Autism Spectrum Disorder in China: A Nationwide Multi-center Population-based Study Among Children Aged 6 to 12 Years - Hao Zhou; Xiu Xu; Weili Yan; Xiaobing Zou; Lijie Wu; Xuerong Luo; Tingyu Li; Yi Huang; Hongyan Guan; Xiang Chen; Meng Mao; Kun Xia; et al. (Neuroscience Bulletin, 2020)

Effects of Microtopography on Absorptive and Transport Fine Root Biomass, Necromass, Production, Mortality and Decomposition in a Coastal Freshwater Forested Wetland, Southeastern USA - Xuefeng Li; Kevan J. Minick; Jordan Luff; Asko Noormets; Guofang Miao; Bhaskar Mitra; Jean-Christophe Domec; Ge Sun; Steven McNulty; John S. King (Ecosystems, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

Comparative Metabolomic and Transcriptome Analysis Reveal Distinct Flavonoid Biosynthesis Regulation Between Petals of White and Purple Phalaenopsis amabilis - Xiaoqing Meng; Ge Li; Lingya Gu; Yu Sun; Zongyun Li; Jingran Liu; Xiaoqing Wu; Tingting Dong; Mingku Zhu (Journal of Plant Growth Regulation, 2020)

Detection, genetic, and codon usage bias analyses of the VP2 gene of mink bocavirus - Weizhi Xin; Yuqi Liu; Yan Yang; Tianzhi Sun; Lingdi Niu; Junwei Ge (Virus Genes, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

A Novel Approach to Assess the Complexity of Contaminant Plume Transportation in the Aquifer Based on Hausdorff Fractal Dimension - Ge Chen; Yajun Sun; Zhimin Xu (Water, Air, & Soil Pollution, 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

Changes in surface roughness of sandstone after heating and cooling cycles - Zhenlong Ge; Qiang Sun; Ningning Zhang (Arabian Journal of Geosciences, 2020)

Analysis of the characteristics of magnetic properties change in the rock failure process - He Zhang; Qiang Sun; Zhenlong Ge (Acta Geophysica, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

ACT001 modulates the NF-κB/MnSOD/ROS axis by targeting IKKβ to inhibit glioblastoma cell growth - Qiuying Li; Yu Sun; Bowen Liu; Jiabo Li; Xin Hao; Weizhi Ge; Xuemei Zhang; Shiqi Bao; Jianmiao Gong; Zhenhuan Jiang; Chuanjiang Qiu; Liqing Zhao; et al. (Journal of Molecular Medicine, 2020)

How afforestation affects the water cycle in drylands: A process‐based comparative analysis - Kai Schwärzel; Lulu Zhang; Luca Montanarella; Yanhui Wang; Ge Sun (Global Change Biology, 2020)
The world's largest afforestation programs implemented by China made a great contribution to the global “greening up.” These programs have received worldwide attention due to its contribution toward achieving the United Nations Sustainable Development Goals. However, emerging studies have suggested that these campaigns, when not properly implemented, resulted in unintended ecological and water security concerns at the regional scale. While mounting evidence shows that afforestation causes substantial reduction in water yield at the watershed scale, process‐based studies on how forest plantations alter the partitioning of rainwater and affect water balance components in natural vegetation are still lacking at the plot scale. This lack of science‐based data prevents a comprehensive understanding of forest‐related ecosystem services such as soil conservation and water supply under climate change. The present study represents the first “Paired Plot” study of the water balance of afforestation on the Loess Plateau. We investigate the effects of forest structure and environmental factors on the full water cycle in a typical multilayer plantation forest composed of black locust, one of the most popular tree species for plantations worldwide. We measure the ecohydrological components of a black locust versus natural grassland on adjacent sites. The startling finding of this study is that, contrary to the general belief, the understory—instead of the overstory—was the main water consumer in this plantation. Moreover, there is a strict physiological regulation of forest transpiration. In contrast to grassland, annual seepage under the forest was minor in years with an average rainfall. We conclude that global long‐term greening efforts in drylands require careful ecohydrologic evaluation so that green and blue water trade‐offs are properly addressed. This is especially important for reforestation‐based watershed land management, that aims at carbon sequestration in mitigating climate change while maintaining regional water security, to be effective on a large scale.

A review of risk analysis methods for natural disasters - Ruiling Sun; Ge Gao; Zaiwu Gong; Jie Wu (Natural Hazards, 2020)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Investigation of low-temperature selective catalytic reduction of NOx with ammonia over Cr-promoted Fe/AC catalysts - Tingting Ge; Baozhong Zhu; Yunlan Sun; Weiyi Song; Qilong Fang; Yuxiu Zhong (Environmental Science and Pollution Research, 2019)

Neuroprotective effect of green tea extractives against oxidative stress by enhancing the survival and proliferation of PC12 cells - Zhenlu Cai; Xiaoxuan Hu; Ruolan Tan; Yunran Feng; Meiqi Sun; Ning Ma; Xingxing Li; Li Huang; Jing An; Qian Ge; Haixia Lu (Molecular & Cellular Toxicology, 2019)

Long-term stacking coal promoted soil bacterial richness associated with increased soil organic matter in coal yards of power plants - Congcong Shen; Dawei Ma; Ruibo Sun; Benyao Zhang; Delin Li; Yuan Ge (Journal of Soils and Sediments, 2019)

miRNA-21 promotes cell proliferation and invasion via VHL/PI3K/AKT in papillary thyroid carcinoma - Chuanshan Zang; Jian Sun; Wenyi Liu; Chunqin Chu; Liwei Jiang; Ruifeng Ge (Human Cell, 2019)

Choline, not folate, can attenuate the teratogenic effects ofdibutyl phthalate (DBP) during early chick embryo development - Rui Wang; Da-Guang Sun; Ge Song; Chun Yi Guan; Yi Cui; Xu Ma; Hong-Fei Xia (Environmental Science and Pollution Research, 2019)

Degradation induces changes in the soil C:N:P stoichiometry of alpine steppe on the Tibetan Plateau - Zhen-chao Zhang; Ge Hou; Miao Liu; Tian-xing Wei; Jian Sun (Journal of Mountain Science, 2019)

3D-Printed Wearable Personalized Orthodontic Retainers for Sustained Release of Clonidine Hydrochloride - Heliu Jiang; Junhui Fu; Mingguang Li; Shanshan Wang; Bo Zhuang; Haiyan Sun; Cheng Ge; Bin Feng; Yiguang Jin (AAPS PharmSciTech, 2019)

Comprehensive genetic diagnosis of patients with Duchenne/Becker muscular dystrophy (DMD/BMD) and pathogenicity analysis of splice site variants in the DMD gene - Yan-mei Yang; Kai Yan; Bei Liu; Min Chen; Li-ya Wang; Ying-zhi Huang; Ye-qing Qian; Yi-xi Sun; Hong-ge Li; Min-yue Dong (Journal of Zhejiang University-SCIENCE B, 2019)

Potential impacts of climate change on vegetation dynamics and ecosystem function in a mountain watershed on the Qinghai-Tibet Plateau - Decheng Zhou; Lu Hao; John B. Kim; Peilong Liu; Cen Pan; Yongqiang Liu; Ge Sun (Climatic Change, 2019)

Effects of soil environmental factors and UV aging on Cu2+ adsorption on microplastics - Jie Yang; Long Cang; Qian Sun; Ge Dong; Syed Tahir Ata-Ul-Karim; Dongmei Zhou (Environmental Science and Pollution Research, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Modified genetic algorithm with simulated annealing applied to optimal load dispatch of the Three Gorges Hydropower Plant in China - Yizi Shang; Qixiang Fan; Ling Shang; Zhiyu Sun; Ge Xiao (Hydrological Sciences Journal, 2019)

Characterization and comparison of gut microbiomes in nine species of parrots in captivity - Hongyi Liu; Zhiwei Chen; Ge Gao; Chenghe Sun; Yudong Li; Ying Zhu (Symbiosis, 2019)

Global trends and future prospects of e-waste research: a bibliometric analysis - Ya Gao; Long Ge; Shuzhen Shi; Yue Sun; Ming Liu; Bo Wang; Yi Shang; Jiarui Wu; Jinhui Tian (Environmental Science and Pollution Research, 2019)

Dietary leucine affects glucose metabolism and lipogenesis involved in TOR/PI3K/Akt signaling pathway for juvenile blunt snout bream Megalobrama amblycephala - Hualiang Liang; Ahmed Mokrani; Hopeson Chisomo-Kasiya; Ke Ji; Xianping Ge; Mingchun Ren; Bo Liu; Bingwen Xi; Ajun Sun (Fish Physiology and Biochemistry, 2019)

Promotional effect of Mn modification on DeNOx performance of Fe/nickel foam catalyst at low temperature - Zhaohui Zi; Baozhong Zhu; Yunlan Sun; Qilong Fang; Tingting Ge (Environmental Science and Pollution Research, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Enhanced transcriptome responses in herbivore-infested tea plants by the green leaf volatile (Z)-3-hexenol - Zhaojun Xin; Lingang Ge; Shenglong Chen; Xiaoling Sun (Journal of Plant Research, 2019)

Genomewide analysis of homeobox gene family in apple (Malus domestica Borkh.) and their response to abiotic stress - Rong Li; Hongjuan Ge; Yaqing Dai; Li Yuan; Xin Liu; Qinghua Sun; Xiaoyun Wang (Journal of Genetics, 2019)

Efficient removal of ethidium bromide from aqueous solution by using DNA-loaded Fe3O4 nanoparticles - Zhiqiang Ge; Tingting Sun; Jinfeng Xing; Xuejiao Fan (Environmental Science and Pollution Research, 2019)

Cellulose and lignin regulate partitioning of soil phosphorus fractions and alkaline phosphomonoesterase encoding bacterial community in phosphorus-deficient soils - Qi Sun; Husen Qiu; Yajun Hu; Xiaomeng Wei; Xiangbi Chen; Tida Ge; Jinshui Wu; Yirong Su (Biology and Fertility of Soils, 2019)

Chemical constituents from Alisma plantago - aquatica subsp . orientale (Sam.) Sam and their anti-inflammatory and antioxidant activities - Xin-Yu Zhao; Gang Wang; Yan Wang; Xiang-Ge Tian; Jian-Chao Zhao; Xiao-Kui Huo; Cheng-Peng Sun; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Xun Wang (Natural Product Research, 2018)

A new persistent luminescent composite for tracing toxic air particulate matter - Pinghui Ge; Yanjie Liang; Yuan Cheng; Kangning Sun; Rui Liu (Environmental Chemistry Letters, 2018)

MiR-429 improved the hypoxia tolerance of human amniotic cells by targeting HIF-1α - Lihao Ge; Yuyan Wang; Yang Cao; Gang Li; Rui Sun; Peng Teng; Yansong Wang; Yunlong Bi; Zhanpeng Guo; Yajiang Yuan; Deshui Yu (Biotechnology Letters, 2018)

Flavobacterium zaozhuangense sp. nov., a new member of the family Flavobacteriaceae, isolated from metolachlor-contaminated soil - Qing Chen; Hong-Mei Wang; Wen Zhuang; Zhong-Guan Sun; Jing Chen; Yan Ge; Ji-guo Qiu; Jian He (Antonie van Leeuwenhoek, 2018)

Hyperspectral unmixing employing l 1 −l 2 sparsity and total variation regularization - Le Sun; Weidong Ge; Yunjie Chen; Jianwei Zhang; Byeungwoo Jeon (International Journal of Remote Sensing, 2018)

Projected changes in population exposure to extreme heat in China under a RCP8.5 scenario - Dapeng Huang; Lei Zhang; Ge Gao; Shao Sun (Journal of Geographical Sciences, 2018)

Dependence of 3‐month Standardized Precipitation‐Evapotranspiration Index dryness/wetness sensitivity on climatological precipitation over southwest China - Shanlei Sun; Haishan Chen; Jinjian Li; Jiangfeng Wei; Guojie Wang; Ge Sun; Wenjian Hua; Shujia Zhou; Peng Deng (International Journal of Climatology, 2018)
In this study, we estimated the respective contributions of precipitation and reference evapotranspiration (ET 0 ) to annual SPEI‐3 (3‐month Standardized Precipitation‐Evapotranspiration Index) anomalies over southwest China (SWC) using numerical experiments. Results show that the dominant factor (i.e., precipitation or ET 0 ) for the dryness/wetness anomalies during 1961–2012 existed due to inter‐annual and inter‐decadal changes over SWC, which indicates the underlying mechanisms of dry/wet conditions have changed. On the other hand, we calculate the dryness/wetness sensitivity to precipitation or ET 0 (defined as changes in SPEI‐3 per millimetre) and find that the dryness/wetness sensitivity to ET 0 is higher than that to precipitation for the whole SWC and the overwhelming majority (99%) of the 269 sites. Overall, the above findings imply that the role of ET 0 in the dry/wet condition evolution is vital and should be paid more attentions. For the magnitude of the dryness/wetness sensitivity to precipitation or ET 0 , an evident increase from the southeast to northwest SWC is identified. Based on the analyses of the relationship between dryness/wetness sensitivity and climatological condition (i.e., precipitation, ET 0 , and aridity), the sensitivity magnitude is dependent on climatological precipitation and generally decreases with its increase. This study provides a wealth of quantitative information (e.g., dryness/wetness anomalies [sensitivity] caused by [to] precipitation and ET 0 ) for better understanding the underlying mechanisms of the dry/wet condition evolution.

An Improved Water Budget for the El Yunque National Forest, Puerto Rico, as Determined by the Water Supply Stress Index Model - Liangxia Zhang; Ge Sun; Erika Cohen; Steven G McNulty; Peter V Caldwell; Suzanne Krieger; Jason Christian; Decheng Zhou; Kai Duan; Keren J Cepero-Pérez (Forest Science, 2018)

Genetic analysis of the fiber quality and yield traits in G. hirsutum background using chromosome segments substitution lines (CSSLs) from Gossypium barbadense - Lixue Guo; Yuzhen Shi; Juwu Gong; Aiying Liu; Yunna Tan; Wankui Gong; Junwen Li; Tingting Chen; Haihong Shang; Qun Ge; Quanwei Lu; Jie Sun; et al. (Euphytica, 2018)

Identification, expression analysis, and function evaluation of 42 tomato DEAD-box RNA helicase genes in growth development and stress response - Jing Cai; Xiaoqing Meng; Ge Li; Tingting Dong; Jian Sun; Tao Xu; Zongyun Li; Yonghua Han; Mingku Zhu (Acta Physiologiae Plantarum, 2018)

Simulation of the osmosis-based drug encapsulation in erythrocytes - Duobiao Ge; Lili Zou; Chengpan Li; Sen Liu; Shibo Li; Sijie Sun; Weiping Ding (European Biophysics Journal, 2018)

Lead-induced changes of cytoskeletal protein is involved in the pathological basis in mice brain - Yaming Ge; Lingli Chen; Xianghe Sun; Zhihong Yin; Xiaochao Song; Chong Li; Junwei Liu; Zhixing An; Xuefeng Yang; Hongmei Ning (Environmental Science and Pollution Research, 2018)

An improved water budget for the El Yunque National Forest, Puerto Rico, as determined by the Water Supply Stress Index model - Liangxia Zhang; Ge Sun; Erika Cohen; Steven G McNulty; Peter V Caldwell; Suzanne Krieger; Jason Christian; Decheng Zhou; Kai Duan; Keren J Cepero-Pérez (Forest Science, 2018)

Urban resident energy-saving behavior: a case study under the A2SC framework - Licheng Sun; Qunwei Wang; Shilong Ge (Natural Hazards, 2018)

A novel Alu-mediated microdeletion in the RUNX2 gene in a Chinese patient with cleidocranial dysplasia - Yunzhu Qian; Yingying Zhang; Bin Wei; Mengshu Zhang; Jianxin Yang; Cuihua Leng; Zili Ge; Xingshun Xu; Miao Sun (Journal of Genetics, 2018)

Compounds with inhibitory activity on peristalsis from the seeds of Holarrhena antidysenterica - Hai-Hua Xie; Jian Su; Xiao-Lei Ge; Ting-Ting Dong; Xin Li; Hui-Min Wen; Bo-Hang Sun (Natural Product Research, 2018)

Two new protostane-type triterpenoids from Alisma orientalis - Xiu-Lan Xin; Xin-Yu Zhao; Xiao-Kui Huo; Xiang-Ge Tian; Cheng-Peng Sun; Hou-Li Zhang; Yan Tian; Yong Liu; Xun Wang (Natural Product Research, 2018)

Retinoid acid and taurine promote NeuroD1-induced differentiation of induced pluripotent stem cells into retinal ganglion cells - Li Huang; Mengfei Chen; Weizhong Zhang; Xuerong Sun; Bingqian Liu; Jian Ge (Molecular and Cellular Biochemistry, 2018)

Zoledronate dysregulates fatty acid metabolism in renal tubular epithelial cells to induce nephrotoxicity - Lili Cheng; Mengmeng Ge; Zhou Lan; Zhilong Ma; Wenna Chi; Wenhua Kuang; Kun Sun; Xinbin Zhao; Ye Liu; Yaqian Feng; Yuedong Huang; Maoguo Luo; et al. (Archives of Toxicology, 2018)

Comparison of white spot syndrome virus infection resistance between Exopalaemon carinicauda and Litopenaeus vannamei under different salinity stresses - Qianqian Ge; Ge Yu; Ming Sun; Jitao Li; Jian Li (Journal of Ocean University of China, 2017)

Identification and genetic characterization of a novel circular single-stranded DNA virus in a human upper respiratory tract sample - Lunbiao Cui; Binyao Wu; Xiaojuan Zhu; Xiling Guo; Yiyue Ge; Kangchen Zhao; Xian Qi; Zhiyang Shi; Fengcai Zhu; Lixin Sun; Minghao Zhou (Archives of Virology, 2017)

TRACC: an open source software for processing sap flux data from thermal dissipation probes - Eric J. Ward; Jean-Christophe Domec; John King; Ge Sun; Steve McNulty; Asko Noormets (Trees, 2017)

GhVLN4 is involved in cell elongation via regulation of actin organization - Fenni Lv; Mingya Han; Dongdong Ge; Hui Dong; Xiaotong Zhang; Lifeng Li; Peipei Zhang; Zhongqi Zhang; Jing Sun; Kang Liu; Youlu Yuan (Planta, 2017)

Influence of Micropatterned Silk Fibroin Films on Human Umbilical Endothelial Cell Behaviors - Danyan Wang; Yan Sun; Xili Ding; Ge Peng; Tongqiang Zou; Haifeng Liu; Yubo Fan (Journal of Medical and Biological Engineering, 2017)

Association Between Serum Zinc Levels and the Risk of Parkinson’s Disease: a Meta-Analysis - Hualei Sun; Xinxin Liu; Huina Ge; Teng Wang; Yan Wang; Wenjie Li (Biological Trace Element Research, 2017)

Conjugate gradient and cross-correlation based least-square reverse time migration and its application - Xiao-Dong Sun; Zhong-Hui Ge; Zhen-Chun Li (Applied Geophysics, 2017)

Adsorption-Desorption Characteristics of Nonylphenol on Two Different Origins of Black Carbon - Guanghuan Cheng; Mingyang Sun; Xinlei Ge; Yang Ou; Xinhua Xu; Qi Lin; Liping Lou (Water, Air, & Soil Pollution, 2017)

Impacts of inland boundary conditions on modeling seawater intrusion in coastal aquifers due to sea-level rise - Dong-mei Sun; Si-xiang Niu; Yong-ge Zang (Natural Hazards, 2017)

Seismic behaviors of soil slope in permafrost regions using a large-scale shaking table - Hong Sun; FuJun Niu; KaiJian Zhang; XiuRun Ge (Landslides, 2017)

Assessment of particulate emissions from a sinter plant in steelmaking works in China - Liang Zhao; Wenqiang Sun; Xiaoling Li; Zhu Ye; Jian Huang; Ge Zhang; Jiuju Cai (Environmental Monitoring and Assessment, 2017)

On the coupling between precipitation and potential evapotranspiration: contributions to decadal drought anomalies in the Southwest China - Shanlei Sun; Haishan Chen; Weimin Ju; Guojie Wang; Ge Sun; Jin Huang; Hedi Ma; Chujie Gao; Wenjian Hua; Guixia Yan (Climate Dynamics, 2017)

A new phenolic glycoside from the stem of Dendrobium nobile - Xue-Ming Zhou; Cai-Juan Zheng; Jia-Ting Wu; Guang-Ying Chen; Bin Zhang; Chong-Ge Sun (Natural Product Research, 2017)

Reversible Absorption and Emission Responses of Nile Blue and Azure A Derivatives in Extreme Acidic and Basic Conditions - Xiu-Li Wang; Ru Sun; Wei-Jin Zhu; Xin-Long Sha; Jian-Feng Ge (Journal of Fluorescence, 2017)

Functional effector memory T cells contribute to protection from superinfection with heterologous simian immunodeficiency virus or simian-human immunodeficiency virus isolates in Chinese rhesus macaques - Ming Sun; Huiwen Zheng; Yingpeng Xie; Bingxiang Li; Haiting Long; Ge Guo; Lei Guo; Jingjing Wang; Ruotong Ning; Yue Li; Longding Liu (Archives of Virology, 2017)

Neutrophil-To-Lymphocyte Ratio Predicts 3-Month Outcome of Acute Ischemic Stroke - Sen Qun; Yan Tang; Jing Sun; Zhaoxia Liu; Juncang Wu; Ji Zhang; Jidong Guo; Zhiqiang Xu; Dan Zhang; Zhengxu Chen; Fuyong Hu; Xingshun Xu; et al. (Neurotoxicity Research, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Physiological and anatomical responses of Phyllostachys vivax and Arundinaria fortunei (Gramineae) under salt stress - Wei Ge; Ying Zhang; Zhongyuan Sun; Juan Li; Guohua Liu; Yanjun Ma; Jian Gao (Brazilian Journal of Botany, 2017)

Characterization of the global transcriptome and microsatellite marker information for spotted halibut Verasper variegatus - Jianlong Ge; Siqing Chen; Changlin Liu; Li Bian; Huiling Sun; Jie Tan (Genes & Genomics, 2017)

Whole transcriptome analysis of three leaf stages in two cultivars and one of their F1 hybrid of Camellia sinensis L. with differing EGCG content - Jinke Lin; Iain W. Wilson; Guoping Ge; Guiling Sun; Fuliang Xie; Yanfang Yang; Liangyu Wu; Baohong Zhang; Jianqiang Wu; Yue Zhang; Deyou Qiu (Tree Genetics & Genomes, 2017)

Impact of air pollution induced climate change on water availability and ecosystem productivity in the conterminous United States - Kai Duan; Ge Sun; Yang Zhang; Khairunnisa Yahya; Kai Wang; James M. Madden; Peter V. Caldwell; Erika C. Cohen; Steven G. McNulty (Climatic Change, 2017)

DJ-1/PARK7, But Not Its L166P Mutant Linked to Autosomal Recessive Parkinsonism, Modulates the Transcriptional Activity of the Orphan Nuclear Receptor Nurr1 In Vitro and In Vivo - Lingling Lu; Shasha Zhao; Ge Gao; Xiaohong Sun; Huanying Zhao; Hui Yang (Molecular Neurobiology, 2016)

The stability problem of reverse time migration for viscoacoustic VTI media - Xiao-Dong Sun; Zhong-Hui Ge; Zhen-Chun Li; Ying Hong (Applied Geophysics, 2016)

Mitochondrial aldehyde dehydrogenase 2 deficiency aggravates energy metabolism disturbance and diastolic dysfunction in diabetic mice - Cong Wang; Fan Fan; Quan Cao; Cheng Shen; Hong Zhu; Peng Wang; Xiaona Zhao; Xiaolei Sun; Zhen Dong; Xin Ma; Xiangwei liu; Shasha Han; et al. (Journal of Molecular Medicine, 2016)

Osteoprotegerin deficiency leads to deformation of the articular cartilage in femoral head - Yi Liu; Jianping Ge; Danying Chen; Yuteng Weng; Haiming Du; Yao Sun; Qi Zhang (Journal of Molecular Histology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

The partitioning behavior of trace element and its distribution in the surrounding soil of a cement plant integrated utilization of hazardous wastes - Zhenzhou Yang; Yan Chen; Yongqi Sun; Lili Liu; Zuotai Zhang; Xinlei Ge (Environmental Science and Pollution Research, 2016)

CMIP5 model simulations of Ethiopian Kiremt-season precipitation: current climate and future changes - Laifang Li; Wenhong Li; Tristan Ballard; Ge Sun; Marc Jeuland (Climate Dynamics, 2016)

Combined Finite-Discrete Element Method for Simulation of Hydraulic Fracturing - Chengzeng Yan; Hong Zheng; Guanhua Sun; Xiurun Ge (Rock Mechanics and Rock Engineering, 2016)

Isolation of prawn (Exopalaemon carinicauda) lipopolysaccharide and β-1, 3-glucan binding protein gene and its expression in responding to bacterial and viral infections - Qianqian Ge; Jian Li; Yafei Duan; Jitao Li; Ming Sun; Fazhen Zhao (Journal of Ocean University of China, 2016)

Quasi-Saturated Zones Induced by Rainfall Infiltration - Sun Dong-mei; Zang Yong-ge; Feng Ping; Stephan Semprich (Transport in Porous Media, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

TCTP Expression After Rat Spinal Cord Injury: Implications for Astrocyte Proliferation and Migration - Jianbing Ren; Xingxing Mao; Minghao Chen; Weidong Zhang; Yang Liu; Chengwei Duan; Haiyan Zhang; Chi Sun; Weijie Wu; Xinjian Zhu; Jianbing Ge; Weidong Tao; et al. (Journal of Molecular Neuroscience, 2015)

Regulation of OPG and RANKL expressed by human dental follicle cells in osteoclastogenesis - Haiyan Sun; Qihong Li; Yongkuan Zhang; Yingchun Bi; Xia Li; Yao Shu; Xuepeng Chen; Zuolin Jin; Cheng Ge (Cell and Tissue Research, 2015)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Identification of defense-related genes in banana roots infected by Fusarium oxysporum f. sp. cubense tropical race 4 - Weiming Li; Xuejun Ge; Wei Wu; Wei Wang; Yulin Hu; Yiwei Mo; Dequan Sun; Shengyou Shi; Jianghui Xie (Euphytica, 2015)

Dinosaur teeth from the Jurassic Qigu and Shishugou Formations of the Junggar Basin (Xinjiang/China) and their paleoecologic implications - Oliver Wings; Thomas Tütken; Denver W. Fowler; Thomas Martin; Hans-Ulrich Pfretzschner; Ge Sun (PalZ, 2015)

Synergistic contribution of precipitation anomalies over northwestern India and the South China Sea to high temperature over the Yangtze River Valley - Ge Liu; Renguang Wu; Shuqing Sun; Huimei Wang (Advances in Atmospheric Sciences, 2015)

Exploring the synergistic use of multi-scale image object metrics for land-use/land-cover mapping using an object-based approach - Ning Han; Huaqiang Du; Guomo Zhou; Xiaojun Xu; Hongli Ge; Lijuan Liu; Guolong Gao; Shaobo Sun (International Journal of Remote Sensing, 2015)

Plant stomatal closure improves aphid feeding under elevated CO 2 - Yucheng Sun; Huijuan Guo; Liang Yuan; Jianing Wei; Wenhao Zhang; Feng Ge (Global Change Biology, 2015)
Stomata help plants regulate CO 2 absorption and water vapor release in response to various environmental changes, and plants decrease their stomatal apertures and enhance their water status under elevated CO 2 . Although the bottom‐up effect of elevated CO 2 on insect performance has been extensively studied, few reports have considered how insect fitness is altered by elevated CO 2 ‐induced changes in host plant water status. We tested the hypothesis that aphids induce stomatal closure and increase host water potential, which facilitates their passive feeding, and that this induction can be enhanced by elevated CO 2 . Our results showed that aphid infestation triggered the abscisic acid ( ABA ) signaling pathway to decrease the stomatal apertures of Medicago truncatula , which consequently decreased leaf transpiration and helped maintain leaf water potential. These effects increased xylem‐feeding time and decreased hemolymph osmolarity, which thereby enhanced phloem‐feeding time and increased aphid abundance. Furthermore, elevated CO 2 up‐regulated an ABA ‐independent enzyme, carbonic anhydrase, which led to further decrease in stomatal aperture for aphid‐infested plants. Thus, the effects of elevated CO 2 and aphid infestation on stomatal closure synergistically improved the water status of the host plant. The results indicate that aphid infestation enhances aphid feeding under ambient CO 2 and that this enhancement is increased under elevated CO 2 .

Membrane protein profiling of Acidovorax avenae subsp. avenae under various growth conditions - Bin Li; Li Wang; Muhammad Ibrahim; Mengyu Ge; Yanli Wang; Shazia Mannan; Muhammad Asif; Guochang Sun (Archives of Microbiology, 2015)

Effects of Airflow Induced by Rainfall Infiltration on Unsaturated Soil Slope Stability - Dong-mei Sun; Yong-ge Zang; Stephan Semprich (Transport in Porous Media, 2015)

Climatic variability, hydrologic anomaly, and methane emission can turn productive freshwater marshes into net carbon sources - Housen Chu; Johan F. Gottgens; Jiquan Chen; Ge Sun; Ankur R. Desai; Zutao Ouyang; Changliang Shao; Kevin Czajkowski (Global Change Biology, 2015)
Freshwater marshes are well‐known for their ecological functions in carbon sequestration, but complete carbon budgets that include both methane ( CH 4 ) and lateral carbon fluxes for these ecosystems are rarely available. To the best of our knowledge, this is the first full carbon balance for a freshwater marsh where vertical gaseous [carbon dioxide ( CO 2 ) and CH 4 ] and lateral hydrologic fluxes (dissolved and particulate organic carbon) have been simultaneously measured for multiple years (2011–2013). Carbon accumulation in the sediments suggested that the marsh was a long‐term carbon sink and accumulated ~96.9 ± 10.3 (±95% CI ) g C m −2 yr −1 during the last ~50 years. However, abnormal climate conditions in the last 3 years turned the marsh to a source of carbon (42.7 ± 23.4 g C m −2 yr −1 ). Gross ecosystem production and ecosystem respiration were the two largest fluxes in the annual carbon budget. Yet, these two fluxes compensated each other to a large extent and led to the marsh being a CO 2 sink in 2011 (−78.8 ± 33.6 g C m −2 yr −1 ), near CO 2 ‐neutral in 2012 (29.7 ± 37.2 g C m −2 yr −1 ), and a CO 2 source in 2013 (92.9 ± 28.0 g C m −2 yr −1 ). The CH 4 emission was consistently high with a three‐year average of 50.8 ± 1.0 g C m −2 yr −1 . Considerable hydrologic carbon flowed laterally both into and out of the marsh (108.3 ± 5.4 and 86.2 ± 10.5 g C m −2 yr −1 , respectively). In total, hydrologic carbon fluxes contributed ~23 ± 13 g C m −2 yr −1 to the three‐year carbon budget. Our findings highlight the importance of lateral hydrologic inflows/outflows in wetland carbon budgets, especially in those characterized by a flow‐through hydrologic regime. In addition, different carbon fluxes responded unequally to climate variability/anomalies and, thus, the total carbon budgets may vary drastically among years.

Arbuscular mycorrhizal symbiosis can mitigate the negative effects of night warming on physiological traits of Medicago truncatula L - Yajun Hu; Songlin Wu; Yuqing Sun; Tao Li; Xin Zhang; Caiyan Chen; Ge Lin; Baodong Chen (Mycorrhiza, 2015)

Application of carboxyphenylboronic acid-functionalized magnetic nanoparticles for extracting nucleic acid from seeds - Ning Sun; Congliang Deng; Guanglu Ge; Qiang Xia (Biotechnology Letters, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Characterisation of novel linear antigen epitopes on North American-type porcine reproductive and respiratory syndrome virus M protein - Qian Wang; Jiazeng Chen; Jinmei Peng; Tongqing An; Chaoliang Leng; Yan Sun; Xin Guo; Xinna Ge; Zhijun Tian; Hanchun Yang (Archives of Virology, 2014)

A nonlinear microseismic source location method based on Simplex method and its residual analysis - Nan Li; Enyuan Wang; Maochen Ge; Zhenyu Sun (Arabian Journal of Geosciences, 2014)

miR-210 over-expression enhances mesenchymal stem cell survival in an oxidative stress environment through antioxidation and c-Met pathway activation - JianFeng Xu; ZheYong Huang; Li Lin; MingQiang Fu; YanHua Gao; YunLi Shen; YunZeng Zou; AiJun Sun; JuYing Qian; JunBo Ge (Science China Life Sciences, 2014)

Analyses of the Similarity and Difference of Global Gene Expression Profiles in Cortex Regions of Three Neurodegenerative Diseases: Sporadic Creutzfeldt-Jakob Disease (sCJD), Fatal Familial Insomnia (FFI), and Alzheimer’s Disease (AD) - Chan Tian; Di Liu; Wei Xiang; Hans A. Kretzschmar; Qing-Lan Sun; Chen Gao; Yin Xu; Hui Wang; Xue-Yu Fan; Ge Meng; Wei Li; Xiao-Ping Dong (Molecular Neurobiology, 2014)

Distinct Promoters Affect Pyrroloquinoline Quinone Production in Recombinant Escherichia coli and Klebsiella pneumoniae - Jiguo Sun; Zengye Han; Xizhen Ge; Pingfang Tian (Current Microbiology, 2014)

Whole-genome analysis of porcine epidemic diarrhea virus (PEDV) from eastern China - De-Quan Yang; Fei-Fei Ge; Hou-Bin Ju; Jian Wang; Jian Liu; Kun Ning; Pei-Hong Liu; Jin-Ping Zhou; Quan-Yun Sun (Archives of Virology, 2014)

A DEAD-box RNA helicase produces two forms of transcript that differentially respond to cold stress in a cryophyte (Chorispora bungeana) - Yu Yang; Zhenglong Sun; Chenchen Ding; Linna Ge; Likun Sun; Muqun Bai; Yuan Song; Shuyan Chen; Lizhe An (Planta, 2014)

Terbium promotes adhesion and osteogenic differentiation of mesenchymal stem cells via activation of the Smad-dependent TGF-β/BMP signaling pathway - Dan-Dan Liu; Kun Ge; Yi Jin; Jing Sun; Shu-Xiang Wang; Meng-Su Yang; Jin-Chao Zhang (JBIC Journal of Biological Inorganic Chemistry, 2014)

Antitumor Effect of TRAIL on Oral Squamous Cell Carcinoma using Magnetic Nanoparticle-Mediated Gene Expression - Leiying Miao; Chao Liu; Jiuyu Ge; Weidong Yang; Jinzhong Liu; Weibin Sun; Bai Yang; Changyu Zheng; Hongchen Sun; Qingang Hu (Cell Biochemistry and Biophysics, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

Elevation‐induced climate change as a dominant factor causing the late Miocene C 4 plant expansion in the Himalayan foreland - Haibin Wu; Zhengtang Guo; Joël Guiot; Christine Hatté; Changhui Peng; Yanyan Yu; Junyi Ge; Qin Li; Aizhi Sun; Deai Zhao (Global Change Biology, 2014)
During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

The rise of the mediocre forest: why chronically stressed trees may better survive extreme episodic climate variability - Steven G. McNulty; Johnny L. Boggs; Ge Sun (New Forests, 2014)

Object-based classification using SPOT-5 imagery for Moso bamboo forest mapping - Ning Han; Huaqiang Du; Guomo Zhou; Xiaoyan Sun; Hongli Ge; Xiaojun Xu (International Journal of Remote Sensing, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

Genetic diversity and population structure of the marbled rockfish, Sebastiscus marmoratus, revealed by SSR markers - DIAN-QIAO SUN; GE SHI; XUE-ZHU LIU; RI-XIN WANG; TIAN-JUN XU (Journal of Genetics, 2013)

Sorption Behavior of Phosphate on an MSWI Bottom Slag and Sewage Sludge Co-sintered Adsorbent - Suyang Ge; Hui Zhang; Hai Ye; Houhu Zhang; Keqiang Zhao; Qinfang Sun; Rui Wu; Wenping Cao (Water, Air, & Soil Pollution, 2013)

Rapid development of 36 polymorphic microsatellite markers for Tetranychus truncatus by transferring from Tetranychus urticae - Cheng Ge; Jing-Tao Sun; Yu-Nan Cui; Xiao-Yue Hong (Experimental and Applied Acarology, 2013)

Pea aphid promotes amino acid metabolism both in M edicago truncatula and bacteriocytes to favor aphid population growth under elevated CO 2 - Huijuan Guo; Yucheng Sun; Yuefei Li; Bin Tong; Marvin Harris; Keyan Zhu‐Salzman; Feng Ge (Global Change Biology, 2013)
Rising atmospheric CO 2 levels can dilute the nitrogen ( N ) resource in plant tissue, which is disadvantageous to many herbivorous insects. Aphids appear to be an exception that warrants further study. The effects of elevated CO 2 (750 ppm vs. 390 ppm) were evaluated on N assimilation and transamination by two M edicago truncatula genotypes, a N‐fixing‐deficient mutant ( dnf1 ) and its wild‐type control (Jemalong), with and without pea aphid ( Acyrthosiphon pisum ) infestation. Elevated CO 2 increased population abundance and feeding efficiency of aphids fed on Jemalong, but reduced those on dnf1 . Without aphid infestation, elevated CO 2 increased photosynthetic rate, chlorophyll content, nodule number, biomass, and pod number for Jemalong, but only increased pod number and chlorophyll content for dnf1 . Furthermore, aphid infested Jemalong plants had enhanced activities of N assimilation‐related enzymes (glutamine synthetase, Glutamate synthase) and transamination‐related enzymes (glutamate oxalate transaminase, glutamine phenylpyruvate transaminase), which presumably increased amino acid concentration in leaves and phloem sap under elevated CO 2 . In contrast, aphid infested dnf1 plants had decreased activities of N assimilation‐related enzymes and transmination‐related enzymes and amino acid concentrations under elevated CO 2 . Furthermore, elevated CO 2 up‐regulated expression of genes relevant to amino acid metabolism in bacteriocytes of aphids associated with Jemalong, but down‐regulated those associated with dnf1 . Our results suggest that pea aphids actively elicit host responses that promote amino acid metabolism in both the host plant and in its bacteriocytes to favor the population growth of the aphid under elevated CO 2 .

Dynamic expression profiles of MMPs/TIMPs and collagen deposition in mechanically unloaded rat heart: implications for left ventricular assist device support-induced cardiac alterations - Lu Wang; Yu-Xian Xu; Xiao-Jie Du; Quan-Ge Sun; Ying-Jun Tian (Journal of Physiology and Biochemistry, 2013)

Microparameter Prediction for a Triaxial Compression PFC3D Model of Rock Using Full Factorial Designs and Artificial Neural Networks - Miao-jun Sun; Hui-ming Tang; Xin-li Hu; Yun-feng Ge; Sha Lu (Geotechnical and Geological Engineering, 2013)

Investigation on pretreatment of centrifugal mother liquid produced in the production of polyvinyl chloride by air-Fenton technique - Yingying Sun; Xiuyi Hua; Rui Ge; Aitong Guo; Zhiyong Guo; Deming Dong; Wentian Sun (Environmental Science and Pollution Research, 2013)

Dynamic analysis for gene expression profiles of endothelial colony forming cells under hypoxia - De-Cai Yu; Wen-Du Feng; Xian-Biao Shi; Zhi-Yong Wang; Wei Ge; Chun-Ping Jiang; Xi-Tai Sun; Yi-Tao Ding (Genes & Genomics, 2013)

Different mechanisms lead to convergence of reproductive strategies in two lacertid lizards (Takydromus wolteri and Eremias argus) - Bao-Jun Sun; Shu-Ran Li; Xue-Feng Xu; Wen-Ge Zhao; Lai-Gao Luo; Xiang Ji; Wei-Guo Du (Oecologia, 2013)

Combinational biosynthesis of phycocyanobilin using genetically-engineered Escherichia coli - Baosheng Ge; Yan Li; Haixiang Sun; Shuai Zhang; Peijie Hu; Song Qin; Fang Huang (Biotechnology Letters, 2013)

Sea ice disasters and their impacts since 2000 in Laizhou Bay of Bohai Sea, China - Xu-Liang Zhang; Zhao-Hui Zhang; Zong-Jun Xu; Ge Li; Qing Sun; Xue-Jing Hou (Natural Hazards, 2013)

Molecular cloning, characterization and expression analysis of a CC chemokine gene from miiuy croaker (Miichthys miiuy) - Yuanzhi Cheng; Yuena Sun; Ge Shi; Rixin Wang; Tianjun Xu (Fish Physiology and Biochemistry, 2012)

Study on estimation method of rock mass discontinuity shear strength based on three-dimensional laser scanning and image technique - Huiming Tang; Yunfeng Ge; Liangqing Wang; Yi Yuan; Lei Huang; Miaojun Sun (Journal of Earth Science, 2012)

An enormous Jurassic turtle bone bed from the Turpan Basin of Xinjiang, China - Oliver Wings; Márton Rabi; Jörg W. Schneider; Leonie Schwermann; Ge Sun; Chang-Fu Zhou; Walter G. Joyce (The Science of Nature, 2012)

Effects of drought stress on phosphorus and potassium uptake dynamics in summer maize (Zea mays) throughout the growth cycle - Ti-Da Ge; Ning-Bo Sun; Li-Ping Bai; Chen-Li Tong; Fang-Gong Sui (Acta Physiologiae Plantarum, 2012)

Interactive influences of ozone and climate on streamflow of forested watersheds - GE Sun; Samuel B. McLaughlin; John H. Porter; Johan Uddling; Patrick J. Mulholland; Mary B. Adams; Neil Pederson (Global Change Biology, 2012)
The capacity of forests to mitigate global climate change can be negatively influenced by tropospheric ozone that impairs both photosynthesis and stomatal control of plant transpiration, thus affecting ecosystem productivity and watershed hydrology. We have evaluated individual and interactive effects of ozone and climate on late season streamflow for six forested watersheds (38–970 000 ha) located in the Southeastern United States. Models were based on 18–26 year data records for each watershed and involved multivariate analysis of interannual variability of late season streamflow in response to physical and chemical climate during the growing season. In all cases, some combination of ozone variables significantly improved model performance over climate‐only models. Effects of ozone and ozone × climate interactions were also consistently negative and were proportional to variations in actual ozone exposures, both spatially across the region and over time. Conservative estimates of the influence of ozone on the variability ( R 2 ) of observed flow ranged from 7% in the area of lowest ozone exposure in West Virginia to 23% in the areas of highest exposure in Tennessee. Our results are supported by a controlled field study using free‐air concentration enrichment methodology which indicated progressive ozone‐induced loss of stomatal control over tree transpiration during the summer in mixed aspen‐birch stands. Despite the frequent assumption that ozone reduces tree water loss, our findings support increasing evidence that ozone at near ambient concentrations can reduce stomatal control of leaf transpiration, and increase water use. Increases in evapotranspiration and associated streamflow reductions in response to ambient ozone exposures are expected to episodically increase the frequency and severity of drought and affect flow‐dependent aquatic biota in forested watersheds. Regional and global models of hydrologic cycles and related ecosystem functions should consider potential interactions of ozone with climate under both current and future warmer and ozone‐enriched climatic conditions.

The role of harvest residue in rotation cycle carbon balance in loblolly pine plantations. Respiration partitioning approach - Asko Noormets; Steve G. McNulty; Jean‐Christophe Domec; Michael Gavazzi; Ge Sun; John S. King (Global Change Biology, 2012)
Timber harvests remove a significant portion of ecosystem carbon. While some of the wood products moved off‐site may last past the harvest cycle of the particular forest crop, the effect of the episodic disturbances on long‐term on‐site carbon sequestration is unclear. The current study presents a 25 year carbon budget estimate for a typical commercial loblolly pine plantation in N orth C arolina, USA , spanning the entire rotation cycle. We use a chronosequence approach, based on 5 years of data from two adjacent loblolly pine plantations. We found that while the ecosystem is very productive ( GEP up to 2900 g m −2 yr −1 , NEE at maturity about 900 g C m −2 yr −1 ), the production of detritus does not offset the loss of soil C through heterotrophic respiration ( R H ) on an annual basis. The input of dead roots at harvest may offset the losses, but there remain significant uncertainties about both the size and decomposition dynamics of this pool. The pulse of detritus produced at harvest resulted in a more than 60% increase in R H . Contrary to expectations, the peak of R H in relation to soil respiration ( SR ) did not occur immediately after the harvest disturbance, but in years 3 and 4, suggesting that a pool of roots may have remained alive for the first few years. On the other hand, the pulse of aboveground R H from coarse woody debris lasted only 2 years. The postharvest increase in R H was offset by a decrease in autotrophic respiration such that the total ecosystem respiration changed little. The observed flux rates show that even though the soil C pool may not necessarily decrease in the long‐term, old soil C is definitely an active component in the site C cycle, contributing about 25–30% of the R H over the rotation cycle.

Elevated O3 reduces the fitness of Bemisia tabaci via enhancement of the SA-dependent defense of the tomato plant - Hongying Cui; Yucheng Sun; Jianwei Su; Qin Ren; Chuanyou Li; Feng Ge (Arthropod-Plant Interactions, 2012)

Comparison between CBR and CA methods for estimating land use change in Dongguan, China - Yunyan Du; Yong Ge; V. Chris Lakhan; Yeran Sun; Feng Cao (Journal of Geographical Sciences, 2012)

Relationship of summer soil moisture with early winter monsoon and air temperature over eastern China - Ge Liu; Jun‐Ming Chen; Li‐Ren Ji; Shu‐Qing Sun (International Journal of Climatology, 2012)
The time‐lagged effect of summer soil moisture (SM) on ensuing winter climate in eastern China is examined. The East Asian winter monsoon (EAWM) in early winter (November) and associated air temperature over eastern China are shown to significantly correlate with the previous summer (June–August) SM in eastern China with a center located at the lower reaches of the Yellow River (LRYR). The positive anomalies of summer SM, persisting for a few months, may act as a buffer to defer the ground cooling of eastern China in early winter mainly through modulating thermal capacity. And the warmer ground of eastern China could lead to a warmer air temperature above the ground through direct land–air interactions and through indirectly adjusting the EAWM which is sensitive to the land–sea thermal contrast. These results provide an empirical predictor for the EAWM and for the variability of air temperature over eastern China in early winter. Copyright © 2011 Royal Meteorological Society

Effect of the calcium sensing receptor on rat bone marrow-derived mesenchymal stem cell proliferation through the ERK1/2 pathway - Zhihui Xu; Ling Yan; Yingbing Ge; Qing Zhang; Naiquan Yang; Min Zhang; Yingming Zhao; Peng Sun; Jinghong Gao; Zhengxian Tao; Zhijian Yang (Molecular Biology Reports, 2012)

(−)-Epigallocatechin-3-gallate inhibits the replication cycle of hepatitis C virus - Chao Chen; Hui Qiu; Jian Gong; Qing Liu; Han Xiao; Xin-Wen Chen; Bin-Lian Sun; Rong-Ge Yang (Archives of Virology, 2012)

The role of SDF-1α/Rac pathway in the regulation of endothelial progenitor cell polarity; homing and expression of Rac1, Rac2 during endothelial repair - Li Shen; Yongxing Gao; Juying Qian; Yizhe Wu; Mingming Zhou; Aijun Sun; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Century-Scale Responses of Ecosystem Carbon Storage and Flux to Multiple Environmental Changes in the Southern United States - Hanqin Tian; Guangsheng Chen; Chi Zhang; Mingliang Liu; Ge Sun; Arthur Chappelka; Wei Ren; Xiaofeng Xu; Chaoqun Lu; Shufen Pan; Hua Chen; Dafeng Hui; et al. (Ecosystems, 2012)

Effects of water stress on growth, biomass partitioning, and water-use efficiency in summer maize (Zea mays L.) throughout the growth cycle - Tida Ge; Fanggong Sui; Liping Bai; Chengli Tong; Ningbo Sun (Acta Physiologiae Plantarum, 2012)

Iron trafficking system in Helicobacter pylori - Ruiguang Ge; Xuesong Sun (BioMetals, 2012)

Biomechanism of adhesion in gecko setae - Ce Guo; JiuRong Sun; YingBin Ge; WenBo Wang; DaPeng Wang; ZhenDong Dai (Science China Life Sciences, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Effect of Assessment Scale on Spatial and Temporal Variations in CH4, CO2, and N2O Fluxes in a Forested Wetland - Zhaohua Dai; Carl C. Trettin; Changsheng Li; Harbin Li; Ge Sun; Devendra M. Amatya (Water, Air, & Soil Pollution, 2012)

Structure and variable numbers of tandem repeats (VNTRs) of the mitochondrial control region in mitten crab Eriocheir (Crustacean: Brachyura) - Daizhen Zhang; Ge Ding; Guangyue Wang; Boping Tang; Hongying Sun (Molecular Biology Reports, 2011)

Impact of long-range transport and under-cloud scavenging on precipitation chemistry in East China - Yuhua Li; Yan Wang; Aijun Ding; Xiaohuan Liu; Jia Guo; Penghui Li; Minghu Sun; Fuling Ge; Wenxing Wang (Environmental Science and Pollution Research, 2011)

Greening China Naturally - Shixiong Cao; Ge Sun; Zhiqiang Zhang; Liding Chen; Qi Feng; Bojie Fu; Steve McNulty; David Shankman; Jianwu Tang; Yanhui Wang; Xiaohua Wei (Ambio, 2011)

The complete mitochondrial genome of bighead croaker, Collichthys niveatus (Perciformes, Sciaenidae): structure of control region and phylogenetic considerations - Tian-jun Xu; Yuan-zhi Cheng; Yue-na Sun; Ge Shi; Ri-xin Wang (Molecular Biology Reports, 2011)

Spectroscopic and Molecular Modeling Studies on the Interaction Between a Fluorine-Containing Triazole Derivative and Human Serum Albumin - Jia-Xin Fu; Yu-Shu Ge; Feng-Lei Jiang; Xiao-Hong Sun; Yang Liu; Yi Liu (Biological Trace Element Research, 2011)

Involvement of auxin and nitric oxide in plant Cd-stress responses - Jin Xu; Wenying Wang; Jianhang Sun; Yuan Zhang; Qing Ge; Liguo Du; Hengxia Yin; Xiaojing Liu (Plant and Soil, 2011)

Effects of Preconditioning with Sevoflurane on TNF-α-Induced Permeability and Activation of p38 MAPK in Rat Pulmonary Microvascular Endothelial Cells - Shao-Xiao Sun; Bao-Xue Ge; Chang-Hong Miao (Cell Biochemistry and Biophysics, 2011)

Simultaneous determination of malachite green, enrofloxacin and ciprofloxacin in fish farming water and fish feed by liquid chromatography with solid-phase extraction - Hanwen Sun; Lixin Wang; Xiaolan Qin; Xusheng Ge (Environmental Monitoring and Assessment, 2011)

Two new compounds from Semen celosiae and their protective effects against CCl 4 -induced hepatotoxicity - Qian Xue; Zhen-Liang Sun; Mei-Li Guo; Ying Wang; Ge Zhang; Xiao-Kang Wang (Natural Product Research, 2011)

Phytoliths in woody plants from the northern slope of the Changbai Mountain (Northeast China), and their implication - Yong Ge; Dong Mei Jie; Yan Lei Sun; Hong Mei Liu (Plant Systematics and Evolution, 2011)

China’s Bureaucracy Hinders Environmental Recovery - Lixin Guan; Ge Sun; Shixiong Cao (Ambio, 2011)

Iron-containing lipoprotein SiaA in SiaABC, the primary heme transporter of Streptococcus pyogenes - Xuesong Sun; Ruiguang Ge; Dongmei Zhang; Hongzhe Sun; Qing-Yu He (JBIC Journal of Biological Inorganic Chemistry, 2010)

The Upper Triassic to Middle Jurassic strata and floras of the Junggar Basin, Xinjiang, Northwest China - Ge Sun; Yuyan Miao; Volker Mosbrugger; Abdul R. Ashraf (Palaeobiodiversity and Palaeoenvironments, 2010)

A high-resolution three-dimensional reconstruction of a fossil forest (Upper Jurassic Shishugou Formation, Junggar Basin, Northwest China) - Juliane K Hinz; Ian Smith; Hans-Ulrich Pfretzschner; Oliver Wings; Ge Sun (Palaeobiodiversity and Palaeoenvironments, 2010)

Triassic and Jurassic palaeoclimate development in the Junggar Basin, Xinjiang, Northwest China—a review and additional lithological data - A. Rahman Ashraf; Yuewu Sun; Ge Sun; Dieter Uhl; Volker Mosbrugger; Jie Li; Mark Herrmann (Palaeobiodiversity and Palaeoenvironments, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Overexpression of Trpp5 contributes to cell proliferation and apoptosis probably through involving calcium homeostasis - Yan Xiao; Xiaoyan Lv; Ge Cao; Guohui Bian; Jingjing Duan; Jianzhong Ai; Huan Sun; Qingwei Li; Qiutan Yang; Tielin Chen; Danhua Zhao; Ruizhi Tan; et al. (Molecular and Cellular Biochemistry, 2010)

Cholinergic neuronal differentiation of bone marrow mesenchymal stem cells in rhesus monkeys - Ying Qi; FengYan Zhang; Ge Song; XueRong Sun; RuZhang Jiang; MengFei Chen; Jian Ge (Science China Life Sciences, 2010)

An inter-hemispheric teleconnection and a possible mechanism for its formation - Ge Liu; Liren Ji; Shuqing Sun; Qingyun Zhang (Advances in Atmospheric Sciences, 2010)

Determination of Endocrine Disrupting Chemicals in Surface Water and Industrial Wastewater from Beijing, China - Jing Ge; Jian Cong; Ying Sun; Guoxue Li; Zhiqiang Zhou; Chuanfan Qian; Fengmao Liu (Bulletin of Environmental Contamination and Toxicology, 2010)

Response of carbon fluxes to drought in a coastal plain loblolly pine forest - ASKO NOORMETS; MICHAEL J. GAVAZZI; STEVE G. MCNULTY; JEAN‐CHRISTOPHE DOMEC; GE SUN; JOHN S. KING; JIQUAN CHEN (Global Change Biology, 2010)
Full accounting of ecosystem carbon (C) pools and fluxes in coastal plain ecosystems remains less studied compared with upland systems, even though the C stocks in these systems may be up to an order of magnitude higher, making them a potentially important component in regional C cycle. Here, we report C pools and CO 2 exchange rates during three hydrologically contrasting years (i.e. 2005–2007) in a coastal plain loblolly pine plantation in North Carolina, USA. The daily temperatures were similar among the study years and to the long‐term (1971–2000) average, whereas the amount and timing of precipitation differed significantly. Precipitation was the largest in 2005 (147 mm above normal), intermediate in 2006 (48 mm below) and lowest in 2007 (486 mm below normal). The forest was a strong C sink during all years, sequestering 361 ± 67 (2005), 835 ± 55 (2006) and 724 ± 55 (2007) g C m −2 yr −1 according to eddy covariance measurements of net ecosystem CO 2 exchange (NEE). The interannual differences in NEE were traced to drought‐induced declines in canopy and whole tree hydraulic conductances, which declined with growing precipitation deficit and decreasing soil volumetric water content (VWC). In contrast, the interannual differences were small in gross ecosystem productivity (GEP) and ecosystem respiration (ER), both seemingly insensitive to drought. However, the drought sensitivity of GEP was masked by higher leaf area index and higher photosynthetically active radiation during the dry year. Normalizing GEP by these factors enhanced interannual differences, but there were no signs of suppressed GEP at low VWC during any given year. Although ER was very consistent across the 3 years, and not suppressed by low VWC, the total respiratory cost as a fraction of net primary production increased with annual precipitation and the contribution of heterotrophic respiration ( R h ) was significantly higher during the wettest year, exceeding new litter inputs by 58%. Although the difference was smaller during the other 2 years ( R h : litterfall ratio was 1.05 in 2006 and 1.10 in 2007), the soils lost about 109 g C m −2 yr −1 , outlining their potential vulnerability to decomposition, and pointing to potential management considerations to protect existing soil C stocks.

Sensitivity of pine flatwoods hydrology to climate change and forest management in Florida, USA - Jianbiao Lu; Ge Sun; Steven G. McNulty; Nicholas B. Comerford (Wetlands, 2009)

Evidence for Tibetan plateau uplift in Qaidam basin before Eocene-Oligocene boundary and its climatic implications - Junling Pei; Zhiming Sun; Xisheng Wang; Yue Zhao; Xiaohong Ge; Xinzhuan Guo; Haibing Li; Jialiang Si (Journal of Earth Science, 2009)

Cyclooxygenase-2 inhibitor inhibits hippocampal synaptic reorganization in pilocarpine-induced status epilepticus rats - Hai-ju Zhang; Ruo-peng Sun; Ge-fei Lei; Lu Yang; Chun-xi Liu (Journal of Zhejiang University-SCIENCE B, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

Development of strain-specific SCAR markers for authentication of Ganoderma lucidum - Hongyan Su; Lei Wang; Yihe Ge; Ermei Feng; Jie Sun; Linde Liu (World Journal of Microbiology and Biotechnology, 2008)

Genetic diversity analysis and conservation of the endangered Chinese endemic herb Dendrobium officinale Kimura et Migo (Orchidaceae) based on AFLP - Xuexia Li; Xiaoyu Ding; Bihai Chu; Qi Zhou; Ge Ding; Sun Gu (Genetica, 2008)

Vacuolar-type H+-ATPase with the a3 isoform is the proton pump on premature melanosomes - Hiroyuki Tabata; Nobuyuki Kawamura; Ge-Hong Sun-Wada; Yoh Wada (Cell and Tissue Research, 2008)

Production and characterization of intertribal somatic hybrids of Raphanus sativus and Brassica rapa with dye and medicinal plant Isatis indigotica - Yuqin Tu; Jian Sun; Yan Liu; Xianhong Ge; Zhigang Zhao; Xingcheng Yao; Zaiyun Li (Plant Cell Reports, 2008)

The endoplasmic reticulum (ER)-target protein Bik induces Hep3B cells apoptosis by the depletion of the ER Ca2+ stores - Xiaoping Zhao; Li Wang; Yan Sun; Ling Ye; Jian Lu; Yaozong Yuan; Guanxiang Qian; Shengfang Ge (Molecular and Cellular Biochemistry, 2008)

Transgenic Bacillus thuringiensis (Bt) cotton (Gossypium hirsutum) allomone response to cotton aphid, Aphis gossypii, in a closed-dynamics CO2 chamber (CDCC) - Gang Wu; Fa Jun Chen; Feng Ge; Yu-Cheng Sun (Journal of Plant Research, 2007)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)

Differential expression of a subunit isoforms of the vacuolar-type proton pump ATPase in mouse endocrine tissues - Ge-Hong Sun-Wada; Hiroyuki Tabata; Nobuyuki Kawamura; Masamitsu Futai; Yoh Wada (Cell and Tissue Research, 2007)

A proteomic approach for the identification of bismuth-binding proteins in Helicobacter pylori - Ruiguang Ge; Xuesong Sun; Qing Gu; Rory M. Watt; Julian A. Tanner; Benjamin Chun Yu Wong; Harry Huaxiang Xia; Jian-Dong Huang; Qing-Yu He; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2007)

Production of a novel raw-starch-digesting glucoamylase by Penicillium sp. X-1 under solid state fermentation and its use in direct hydrolysis of raw starch - Haiyan Sun; Xiangyang Ge; Weiguo Zhang (World Journal of Microbiology and Biotechnology, 2007)

Morphological and behavioral consequences of recurrent seizures in neonatal rats are associated with glucocorticoid levels - Xiu-Yu Shi; Ji-Wen Wang; Ge-Fei Lei; Ruo-Peng Sun (Neuroscience Bulletin, 2007)

Phenophases alter the soil respiration–temperature relationship in an oak-dominated forest - Jared L. DeForest; Asko Noormets; Steve G. McNulty; Ge Sun; Gwen Tenney; Jiquan Chen (International Journal of Biometeorology, 2006)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)

Improved production of an enzyme that hydrolyses raw yam starch by Penicillium sp. S-22 using fed-batch fermentation - Hai-Yan Sun; Xiang-Yang Ge; Wei-Guo Zhang (Biotechnology Letters, 2006)

Modeling the climatic and subsurface stratigraphy controls on the hydrology of a Carolina bay wetland in South Carolina, USA - Ge Sun; Timothy J. Callahan; Jennifer E. Pyzoha; Carl C. Trettin (Wetlands, 2006)

The first haramiyoid mammal from Asia - Michael W. Maisch; Andreas T. Matzke; Franziska Grossmann; Henrik Sthr; Hans-Ulrich Pfretzschner; Ge Sun (The Science of Nature, 2005)

A relict trematosauroid (Amphibia: Temnospondyli) from the Middle Jurassic of the Junggar Basin (NW China) - Michael W. Maisch; Andreas T. Matzke; Ge Sun (The Science of Nature, 2004)

Modeling Impacts of Management on Carbon Sequestration and Trace Gas Emissions in Forested Wetland Ecosystems - Changsheng Li; Jianbo Cui; Ge Sun; Carl Trettin (Environmental Management, 2004)

Geochemical and Sm–Nd isotopic characteristics of metabasites from central Hainan Island, South China and their tectonic significance - Xian‐Hua Li; Hanwen Zhou; Sun‐Lin Chung; Shijiang Ding; Ying Liu; Chi‐Yu Lee; Wenchun Ge; Yeming Zhang; Renjie Zhang (Island Arc, 2002)
Major and trace elements and Sm–Nd isotopic data are presented for metabasites that are present as lenses within Paleozoic metasediments in the Chenxing and Bangxi regions, central Hainan Island, Southeast (SE) China. Most metabasites are metamorphosed cumulated gabbroic rocks tholeiitic in nature, and characterized by varying degrees of depletion in Th, Nb, Ta and light rare earth elements (LREE). Moreover, they show high positive ∈Nd(T) values of approximately +7, similar to those of mid‐ocean ridge basalts (MORB). A Sm–Nd isochron age of 333 ± 12 Ma obtained for the metabasites is interpreted as their crystallization age. The combined geochemical and Sm–Nd isotopic data suggest that the metabasites were generated by dynamic partial melting from a MORB‐like mantle source in an oceanic regime. These rocks probably represent remnants of fragmented oceanic crust of the eastern part of Paleo‐Tethys. They were obducted onto the continental crust as part of the ‘Shilu Mélange’ in earliest Mesozoic time when southern Hainan (part of the Indochina block) collided with northern Hainan (part of South China). Alternatively, they could be formed in a volcanic rifted passive margin at the sea‐floor spreading stage as part of MORB‐like seaward‐dipping reflector break‐up packages.

Population genetic structure of Ceriops tagal (Rhizophoraceae) in Thailand and China - Xue-Jun Ge; Mei Sun (Wetlands Ecology and Management, 2001)

Ground-water-table rise after forest harvesting on cypress-pine flatwoods in Florida - Ge Sun; Hans Riekerk; Larry V. Kornhak (Wetlands, 2000)

Reproductive biology and genetic diversity of a cryptoviviparous mangrove Aegiceras corniculatum (Myrsinaceae) using allozyme and intersimple sequence repeat (ISSR) analysis - X. J. Ge; M. Sun (Molecular Ecology, 1999)
Mangroves consist of a group of taxonomically diverse species representing about 20 families of angiosperms. However, little is known about their reproductive biology, genetic structure, and the ecological and genetic factors affecting this structure. Comparative studies of various mangrove species are needed to fill such gaps in our knowledge. The pollination biology, outcrossing rate, and genetic diversity of Aegiceras corniculatum were investigated in this study. Pollination experiments suggested that the species is predominantly pollinator‐dependent in fruit setting. A quantitative analysis of the mating system was performed using progeny arrays assayed for intersimple sequence repeat (ISSR) markers. The multilocus outcrossing rate ( t m ) was estimated to be 0.653 in a wild population. Both allozyme and ISSR were used to investigate genetic variation within and among populations. The combined effects of founder events and enhanced local gene flow through seedling dispersal by ocean currents apparently played an important role in shaping the population genetic structure in this mangrove species. Both allozyme variation ( P = 4.76%, A = 1.05, H E = 0.024) and ISSR diversity ( P = 16.18%, A = 1.061, H E = 0.039) were very low at the species level, in comparison with other woody plants with mixed‐mating or outcrossing systems. Gene differentiation among populations was also low: allozyme G ST = 0.106 and ISSR G ST = 0.178. The unusually high genetic identities (0.997 for allozyme and 0.992 for ISSR loci), however, suggest that these populations are probably all descended from a common ancestral population with low polymorphism.

Pollen‐based biome reconstructions for China at 0 and 6000 years - Ge Yu; I. Colin Prentice; Sandy P. Harrison; Xiangjun Sun (Journal of Biogeography, 1998)
Biomization provides an objective and robust method of assigning pollen spectra to biomes so that pollen data can be mapped and compared directly with the output of biomgeographic models. We have tested the applicability of this procedure, originally developed for Europe, to assign modern surface samples from China to biomes. The procedure successfully delineated the major vegetation types of China. When the same procedure was applied to fossil pollen samples for 6000 years ago, the reconstructions showed systematic differences from present, consistent with previous interpretations of vegetation changes since the mid‐Holocene. In eastern China, the forest zones were systematically shifted northwards, such that cool mixed forests displaced taiga in northeastern China, while broad‐leaved evergreen forest extended c . 300 km and temperate deciduous forest c . 500–600 km beyond their present northern limits. In northwestern China, the area of desert and steppe vegetation was reduced compared to present. On the Tibetan Plateau, forest vegetation extended to higher elevations than today and the area of tundra was reduced. These shifts in biome distributions imply significant changes in climate since 6000 years ago that can be interpreted qualitatively as a response to orbital forcing and its secondary effects on the Asian monsoon.